Simulation and experimental research on the electromagnetic bionic vine killing mechanism inspired by biological joints - Min Li; Tao He; Zihe Xu; Miao He; Bin Hu; Lining Wang; Yunhai Ma (Computers and Electronics in Agriculture, 2026)

Co-pyrolysis of bamboo and bovine bone for heteroatom Co-doped porous carbons: Synergistic templating-activation effect and enhanced cycling stability - Junjie Li; Weike Li; Yongchun Fan; Afeng Wu; Zhangwei Sun; Tao Shi; Xiaoqian Ma; Zhaosheng Yu (Biomass and Bioenergy, 2026)

Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Genomic characterization of historical Jinlingnan individuals: insights into genetic continuity and trans-Eurasian signals in eastern China - Shuyi Li; Yuchun Wang; Qu Shen; Jinguo Zan; Mengying Han; Zishuai Huang; Rui Wang; Xinyi Wang; Haifeng He; Le Tao; Hao Ma; Kongyang Zhu; et al. (Human Genetics, 2026)

Self-healing materials for food packaging: Design principles, activation mechanisms and implications for food safety - Mengzi Nie; Runkang Qiu; Huihui Yang; Xiangyu Liang; Ziqian Li; Long Li; Bei Fan; Li-Tao Tong; Peihua Ma; Fengzhong Wang (Food Research International, 2026)

Gradient heat transfer optimized porous foam evaporator for enhanced photoelectric synergistic evaporation - Qingxia Tao; Jialiang Ma; Juan Du; Shikuo Li; Fangzhi Huang (Chemical Engineering Journal, 2026)

Converting greenhouse gas methane to microbial Protein: The state-of-the-art and future prospects - Yicheng Ma; Tao Liu; Chunxing Li; Jianhua Guo (Bioresource Technology, 2026)

Hydrogeochemical formation of travertine morphological differences in typical geothermal waters on the southeastern margin of the Qinghai–Tibet Plateau - Guangbin Tao; Xun Zhou; Binghua Chen; Zhe Jiang; Ruwen Cao; Zhuang Li; Jingru Ma; Yixuan Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Elucidating time-resolved salt stress response mode of salt-tolerant microalgae under simulated seawater salinity: Molecular strategies for algal cultivation and bioproducts production - Meng Ma; Bing Guo; Xinhao Gao; Ran Li; Zichao Zhao; Tao Sun; Li Yao (Journal of Environmental Chemical Engineering, 2026)

Synergistic enhancement of Fe(II)-activated persulfate by visible light and citric acid for trimethoprim degradation: Reaction mechanisms and toxicity evolution - Tao Xu; Nan Li; Xiaohui Jiang; Yongxin Cai; Anlei Wei; Dehua Zhao; Xinying Zhang; Haixia Ma (Journal of Environmental Chemical Engineering, 2026)

Pillar stability in horizontal salt cavern energy storage: Model development and field application - Dong Chen; Hongling Ma; Wei Liang; Xuan Wang; Wentao Li; Siheng Li; Mengjiao Wang; Ronghui Xu; Xiaomeng Sun; Tao Xiong; Changdong Shao (International Journal of Rock Mechanics and Mining Sciences, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Data-driven intelligent modeling for superheater wall temperature prediction and operational optimization of 1000 MW deep peak shaving coal-fired power plants - Xingliang Ji; Yanming Wang; Xiang Ma; Liming Cui; Jiawei Wang; Yongzhong Ni; Hongyuan Li; Tao Wang; Yongsheng Zhang; Hong Xu (Fuel, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Probiotic lactic acid bacteria with hypoglycemic activity: screening, functional evaluation and mechanistic insights - Fang Ma; Tao Wei; Xiaoyan Xu; Huiyu Li; Shijin Xiong; Yazhou Xu; Tao Xiong; Mingyong Xie (Food Bioscience, 2026)

Probabilistic modeling of failure mechanisms of sensitive clay slopes with non-stationary heterogeneity - Shui-Hua Jiang; Jian-Ping Li; Guo-Tao Ma; Lu-Lu Zhang; Mohammad Rezania; Mohaddeseh Mousavi Nezhad (Computers and Geotechnics, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Corrigendum to “Anaerobic treatment of nitrogenous industrial organic wastewater by carbon–neutral processes integrated with anaerobic digestion and partial nitritation/anammox: Critical review of current advances and future directions” [Bioresour. Technol. 415 (2025) 131648] - Zixuan Deng; Chengde Sun; Guangyi Ma; Xinzheng Zhang; Hongbo Guo; Tao Zhang; Yalei Zhang; Yong Hu; Dapeng Li; Yu-You Li; Zhe Kong (Bioresource Technology, 2026)

Two-phase removal kinetics of antimicrobial resistance in collaborative composting: Thermophilic enhancement and rebound suppression - Ruonan Ma; Xuyan Li; Ruolan Tang; Yan Liu; Jiani Wang; Guoxue Li; Si Li; Shenzhong Tian; Tao Jiang; Jiali Chang; Jing Yuan (Bioresource Technology, 2026)

Brown carbon optical emissions from residential coal combustion in china: Dominance of solvent-insoluble components - Fan Li; Qiaoqiao Wang; Nan Ma; Zechao Hu; Xiaocong Zhao; Ning Yang; Zheng Yang; Guangjin Liu; Yuanwei Zhong; Jiangchuan Tao; Juan Hong; Yaqing Zhou; et al. (Atmospheric Research, 2026)

Temporal trends in toxicities and major drivers of polycyclic aromatic hydrocarbon emissions in China from 1960 to 2019 - Xiao Yun; Huizhong Shen; Jin Li; Yuanzheng Zhang; Shuxiu Zheng; Rong Dai; Jinghang Wang; Haoran Xu; Wenxiao Zhang; Guofeng Shen; Jianmin Ma; Shu Tao (Atmospheric Environment, 2026)

New multisource data-driven gap-filling approaches for meteorological data measured at eddy flux sites - Tao Li; Zhi Chen; Yong Lin; Lexin Ma; Fubo Yu; Hyun Seok Kim; Kazuhito Ichii; Yoshiyuki Takahashi; Guirui Yu (Agricultural and Forest Meteorology, 2026)

From fermentation to function: a critical review of lactic acid bacteria redesign for functional foods and precision nutrition - Jianwei Zang; Luyao Xiao; Xiaogan Zhao; Yibo Shi; Kai Ma; Changliang Zhang; Shuo Geng; Xin Rui; Tao Lin; Wei Li (Critical Reviews in Food Science and Nutrition, 2026)

Optimized retrievals of aerosol optical properties from directional polarimetric camera using optimal linear mixture of basis aerosol models supported by the non-negative matrix factorization - Shikuan Jin; Yingying Ma; Deren Li; Wei Gong; Oleg Dubovik; Jin Hong; Zhenghai Liu; Cheng Chen; Zhongting Wang; Tao He; Yunduan Li; Boming Liu; et al. (Remote Sensing of Environment, 2026)

Synergistic performance and mechanism of organosilicon and short-chain fluorocarbon surfactants with electrolyte enhancement for coal dust suppression and explosion prevention - Xuhan Ding; Minjun Ma; Kai Wang; Yuting Wang; Yongzhe Zhang; Jitong Li; Yike Niu; Jiuzhu Wang; Tao Wang; Zhenmin Luo (Process Safety and Environmental Protection, 2026)

Stronger actions are needed to advance PM2.5 mitigation and its health benefits under population aging in China: Evidence from China’s Clean Air Actions - Jian Qian; Ruoyu Li; You Zou; Jiayi Chen; Junyu Wang; Sheng Li; Na Yang; Tianyue Han; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; et al. (Journal of Hazardous Materials, 2026)

The independent and joint effects of short-term exposure to ambient air pollutants on eczema in two cities of China - Tianjing Ouyang; Zhuoxuan Liang; Shujie Huang; Yingyin Liu; Ziqiang Lin; Qijiong Zhu; Weiquan Zeng; Yu Wang; Changchang Li; Jianxiong Hu; Guanhao He; Tao Liu; et al. (Journal of Hazardous Materials, 2026)

Effective density of exhaled submicron particles and its impacts on particle indoor airborne transmission - Yanpei Li; Nan Ma; Alfred Wiedensohler; Lingyun Guo; Chao Zhang; Shaowen Zhu; Zheng Yang; Biao Luo; Zonghan Xue; Linhong Xie; Yaqing Zhou; Juan Hong; et al. (Journal of Aerosol Science, 2026)

Long-term stability of the low-relief landscape in southeastern Tibet revealed by detrital fission track thermochronometry - Yaling Tao; Jianzhang Pang; Yizhou Wang; Leyi Li; Xudong Zhao; Zifa Ma; Hong Chang; Huiping Zhang (Geomorphology, 2026)

Heterologous expression and functional characterization of Bacillus subtilis natto MenA in Escherichia coli and its role in Vitamin K2 Biosynthesis - Said Nawab; Chuanchao Wu; Zhangbing Ge; Wei Tao; Yuqi Li; Yuexin Ma; Yaqing Zhao; Jie Song; Yi-Feng Jiang; Yan Liu (Food Bioscience, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Three-dimensional crosslinked nanofiber membrane enhances biocompatibility and wastewater treatment performance in MABR - Jinxin Yao; Yanbo Ma; Wenyang Di; Yuchen Li; Tao Zhang; Wei Wang (Environmental Research, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Redox-sensitive genetic circuits enhance microbial stress tolerance to complex inhibitors in lignocellulose biorefinery - Wen-Tao Wang; Qi Feng; Ting-Ting Li; Muhammad Aamer Mehmood; Hui Zhu; Ning Wang; Yi Ma; Chen-Guang Liu; Feng-Wu Bai (Chemical Engineering Journal, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

Correction: Effect of environmental regulation on agricultural green total factor productivity: evidence from China - Yuan Ma; Jiulong Zhu; Bing Wang; Xiaoyan Tao; Xiaofang Li (Environment, Development and Sustainability, 2026)

ZO-1-dependent fibrotic scar border formation impedes axon regeneration after spinal cord injury - Ziyu Li; Shuisheng Yu; Xu Wang; Xiaoyang Yu; Daobao Tao; Yongqing Ma; Jiaqi Xu; Zhonghan Wu; Zhida Ma; Dasheng Tian; Xin Ding; Meige Zheng; et al. (Science China Life Sciences, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Hydrogen radical is also a critical reductive defluorination species in the Far-UVC-activated sulfite process - Xiangyang Hou; Shu Xu; Qiuling Lu; Kai Wang; Haonan Lu; Haochen Zhang; Yuying Li; Minchao Liu; Jin Jiang; Shuo Li; Jun Ma; Tiangang Luan; et al. (Journal of Hazardous Materials, 2026)

New insight into mercury sources and trophic transfer in the Bohai Sea food web using carbon, nitrogen, and mercury stable isotopes - Xiaowei Qiao; Shuangxu Zhou; Lin Yang; Hua Guo; Tao Yang; Wenjing Li; Zhuo Ma; Deming Han; Jianbo Shi; Guibin Jiang (Journal of Hazardous Materials, 2026)

MXene sediment/AgNW-filled PVA-PAAm aerogels for efficient solar-driven seawater desalination - Zhanwei Guo; Minming Zou; Wenxing Luo; Chao Qiang; Jue Wang; Wenjing Chen; Yan Ma; Qinglin Li; Xiongxin Jiang; Tao Xu; Xiaowu Hu (Journal of Cleaner Production, 2026)

Microplastics (PET and PVC) disrupt palygorskite-mediated cadmium stabilization in paddy soil: Polymer-specific rhizosphere mechanisms and ecological consequences - Huan-Zhan Zhou; Tao He; Zhen Song; Zhe Li; Jia-Wei Huang; Jie Min; Zhi-Min Xu; Kang Ma (Journal of Environmental Management, 2026)

Suppression characteristics and mechanisms of five typical powder suppressants in large-scale enclosed spaces for hydrogen-blended natural gas/air explosions - Kaiyuan Zhao; Xueqing Wan; Zhenyi Liu; Shuhong Li; Mingzhi Li; Qiqi Liu; Jianbo Ma; Chenze Xu; Tao Wang (Fuel, 2026)

The role of Campylobacter group II phages in mitigating Campylobacter contamination across the poultry food chain: Current applications and future prospects - Muhammad Shahzad Rafiq; Syed Sami Haider; Ziyi Li; Muhammad Sarmad; Dongxin Ma; Muhammad Ali Khan; Junhao Wang; Shuaifeng Gu; Pan Tao; Muhammad Tanweer Khan; Haihong Hao (Food Research International, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Metal-phenolic microcapsules-reinforced hydrogel-based in situ tumor vaccine for postoperative adjuvant therapy - Xin Tan; Renwang Sheng; Yanling Liang; Yinghua Tao; Weikun Li; Nuoya Chen; Diyi Feng; Xinyang Pan; Shuangshuang Ma; Fangzhou Liu; Ling Liu; Liqin Ge (Chemical Engineering Journal, 2026)

Endogenous copper manipulation based on multifunctional gold nanoparticles elicit precise and self-reinforcing photothermal-chemodynamic therapy for effective treatment of metastatic breast cancer - Haoyu Wang; Xiaolin Yu; Handan Zhang; Jie Liu; Ruozhen Ma; Li Chen; Tao Liu; Xinran Shi; Wenyun Mu; Xin Chen (Chemical Engineering Journal, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Multi-resolution ozone mapping over the Yangtze River Delta (2014–2022) using a data-driven spatial weighting and downscaling framework - Na Yang; Jian Qian; Junyu Wang; Jiayi Chen; Sheng Li; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; Tao Zhang; Fei Yin; Yue Ma (Atmospheric Pollution Research, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Study on the present-day crustal deformation characteristics and mechanism of the Yangyuan basin - Chen Gao; Jun Cao; Jian-Bao Sun; Jiang-Tao Qiu; Guang-Qing Ma; Fan Li (Applied Geophysics, 2026)

Effect of environmental regulation on agricultural green total factor productivity: evidence from China - Yuan Ma; Jiulong Zhu; Bing Wang; Xiaoyan Tao; Xiaofang Li (Environment, Development and Sustainability, 2026)

River waterbody extraction and discharge estimation using Sentinel-1 SAR and Sentinel-2 optical remote sensing data - Bin Li; Qinghua Luan; Hongfeng Wang; Tao Bai; Chuanhui Ma; Yinqin Zhang (International Journal of Remote Sensing, 2026)

Solar light irradiation activated dichloramine for efficient abatement of micropollutants - Peng Su; Wenjun Zhang; Haochen Zhang; Haonan Lu; Qiuling Lu; Kai Wang; Yuying Li; Xiaolong Xu; Changyu Liu; Jun Ma; Tao Yang (Water Research, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Low-voltage electrostatic field enhances anthracnose resistance and delays quality deterioration in postharvest persimmon via jasmonic acid-mediated defense activation - Lili Ma; Jinhua Zuo; Yunxiang Wang; Jiejie Tao; Shiyu Liu; Yiting Ren; Xinyi Feng; Tianyu Li; Hua Chen; Caie Wu; Yanyan Zheng (Postharvest Biology and Technology, 2026)

Withanolides from Datura stramonium: two unprecedented B-ring-seco derivatives and anti-inflammatory active analogues - Juan Pan; Gang-Tao Bu; Si-Yi Wang; Jia-Tong Wu; Meng-Meng Li; Wei Guan; Qing-Shan Chen; Li-Li Zhang; Xiao-Chi Ma; Hai-Xue Kuang; Yan Liu (Phytochemistry, 2026)

Real-time and accurate burst localization in water distribution networks with graph-based deep learning - Lei Chen; Tao Tao; Li He; Xiao Zhou; Pijun Duan; Zhiyu Shao; Haiyuan Ma; Hongxiang Chai (Journal of Hydrology, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Tuning the glass transition temperature of two-photon polymerized elastomers for tailorable mechanical properties and enhanced recovery - Yu Long; Tao Wang; Yan Wang; Xiaolong Huang; Zhongyan Gong; Zhiyuan Ma; Yu Lei; Biwei Deng; Yan Li (Chemical Engineering Journal, 2026)

Isolation of cold-adapted cellulose-degrading fungus Penicillium oxalicum G6 and related molecular mechanisms - Mingxiu Li; Manli Duan; Quanjiu Wang; Yan Xu; Yan Sun; Changkun Ma; Kai Wei; Wanghai Tao; Mingjiang Deng (Bioresource Technology, 2026)

Vitamin C mitigates early auditory cortical hyperexcitability and antioxidant imbalance induced by acute intermittent hypoxia - Yue Wu; Tao Li; Wanxin Cao; Rui Fan; Hailing Jiang; Jiachen Han; Furong Ma; Yan Yan (Experimental Brain Research, 2026)

Structural Variability in Bulk Soil and Rhizosphere Microbial Communities at Different Restoration Modes of Open-pit Coal Mine - Qingjun Meng; Mengke Ma; Shengnan Li; Xiaoyu Han; Tao Jin; Yang Jiao; Liyan Wang (Environmental Management, 2026)

Sustained Intra-Articular Delivery of Triple Therapeutics Using a Phase-Transition Phospholipid-Based Gel for Effective Treatment of Gouty Arthritis - Sirui Ma; Jing Yang; Ao Li; Qing Lin; Tao Gong (Pharmaceutical Research, 2026)

Rational design of low-risk and high-efficiency β-triketone herbicide alternatives via integrative computational toxicology and NGBoost modeling - Yuanquan Chi; GuoFeng Zu; Hongyu Ma; Li Tao; Yuhua Ji; Xingmin Zhao; Hongbin Wang; Ning Huang; Chenyu Zhao; Luze Yang (Molecular Diversity, 2026)

Integrated development and regional differentiation of economy, society, and ecology in the yellow river basin based on entropy TOPSIS method - Bing Wang; Xiaoyan Tao; Jiulong Zhu; Xiaofang Li; Yuan Ma; Li Chen (Environment, Development and Sustainability, 2026)

Recent advances and critical insights of cellulose nanocrystals in active food packaging - Xue Gong; Peihua Ma; Zhang Yue; Yang Li; Jinyao Wang; Jiaping Zhang; Chao Qiu; Xiangyu Liang; Bei Fan; Feng-Zhong Wang; Li-Tao Tong (Critical Reviews in Food Science and Nutrition, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Managing low C/N municipal wastewater in full-scale IFAS: Interactive effects of acetate dosing and seasonal cooling - Ning Chen; Xiaodong Wang; Shanshan Chen; Peng Xiao; Tao Ma; Xiang Li (Process Safety and Environmental Protection, 2026)

MOF-enhanced colorimetric sensor array for early detection of citrus infestation by Bactrocera dorsalis - Xin Zhang; Dapeng Li; Ke Jiang; Chao Zeng; Mi He; Xiancheng Ma; Chongshan Yang; Ling Li; Tao Wen (Postharvest Biology and Technology, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Numerical study of motion responses and trajectory patterns of a SUBOFF submerged body under internal solitary waves - Xinyu Ma; Tao Zhao; Yingjie Hu; Aimin Wang; Li Zou; Yelin Gao (Ocean Engineering, 2026)

From lepidolite acid leachate to phosphate adsorbent: selective Al/Fe recovery and conversion to Al-Fe composite hydroxide - Shuangli Xi; Jingrui Li; Youcai Ma; Jing Guo; Wentao Li; Ting Yang; Guocan Zheng; Changyuan Tao; Zuohua Liu (Journal of Environmental Chemical Engineering, 2026)

A novel multifunctional bacterial consortium synergistically promotes rhizoremediation of dibutyl phthalate and cucumber growth: Insights from multi-omics analyses - Jiaming Xu; Yan Li; Haoyan Han; Yi Wu; Yue Tao; Yuexuan Ma; Zhao Jiang; Ying Zhang (Journal of Environmental Sciences, 2026)

Novel insights into dibutyl phthalate exacerbating deltamethrin-induced autophagy inhibition and apoptosis by suppressing the crosstalk between Nrf2 and HIPK2 - Kaiwei Song; Biying Liu; Dongfang Liu; Tao Kong; Miaomiao Li; Biqi Han; Jiayi Li; Jingjing Lu; Yunfeng Liu; Jiatong Ma; Shuke Ji; Zhigang Zhang; et al. (Journal of Environmental Sciences, 2026)

Decoupling of Fe isotope and Fe3+/ΣFe in arc igneous rocks: Implications for crustal metasomatism and its contribution to mantle redox - Li-Tao Ma; Li-Qun Dai; Zi-Wei Yao; Zi-Fu Zhao; Ye-Dan Hu; Zhen-Wu Chen; Guo-Chao Sun (Geochimica et Cosmochimica Acta, 2026)

Screening and functional characterization of lactic acid bacteria with bidirectional immunomodulatory activity - Tao Wei; Fang Ma; Huiyu Li; Tonghao Du; Xiaoyan Xu; Shijin Xiong; Mingwei Zhao; Min Jia; Tao Xiong; Mingyong Xie (Food Bioscience, 2026)

The dietary flavonoid luteolin protects against cadmium-induced cerebral cortical injury in chickens via the endoplasmic reticulum stress-autophagy axis - Xianzu Luo; Qianting Shi; Li Wang; Tao Wang; Yi Wang; Yonggang Ma; Xishuai Tong; Hui Zou; Jianhong Gu; Xuezhong Liu; Jianchun Bian; Zongping Liu; et al. (Food Bioscience, 2026)

Thickness-dependent layered PbBiO2Br with local chlorination induced electronic modulation and atomic-site activation for boosted and selective aerobic photo-oxidation - Tong Li; Wenhao Ma; Han Gao; Xiufeng Lu; Tao Guo; Heyun Fu; Shourong Zheng; Danjun Mao; Xiaolei Qu; Zhaoyi Xu (Chemical Engineering Journal, 2026)

Improving spatial resolutions of unmanned aerial vehicle hyperspectral images to predict grain yield and protein content in rice - Zhonglin Wang; Rong Hu; Mingming Hu; Huilai Yin; Tao Liu; Yufei Xie; Yangming Ma; Feng Yang; Feijie Li; Zhiyuan Yang; Yongjian Sun; Jun Ma (Precision Agriculture, 2026)

Effects of 17β-estradiol interference on the temporal and spatial expression patterns of piwil1 gene and gonadal development in largemouth bass (Micropterus salmoides) - Jiale Zhang; Mingchen Ma; Shengjie Li; Taihang Tian; Jinxing Du; Caixia Lei; Tao Zhu; Jing Tian; Hongmei Song (Fish Physiology and Biochemistry, 2026)

High-temperature stress during rice flowering stage: critical roles of cumulative exposure and coastal adaptation - Manshan Yang; Runze Liu; Tao Li; Zhentao Zhang; Yuanbo Zhao; Haoyu Ma; Yanying Shi; Zhijuan Liu; Fengjing Xiao; Xiaoguang Yang (Climatic Change, 2026)

Diversity and plant growth-promoting activity of rhizospheric and endospheric microbiomes from Cyperus rotundus L. in sugarcane fields of Guangxi, China - Haili Huang; Tao Zheng; Jingbo Li; Weisheng Li; Wei Zheng; Yonglin Ma; Meisha Qiu; Wenwei Tang; Yanhui Wang (Applied Soil Ecology, 2026)

Triterpenoid saponins from Caragana korshinskii Kom.: α ‑glucosidase inhibitory activity and characterisation of four new compounds - Yumei Ma; Tao Chen; Zhibo Song; Hailun Feng; Defa Kong; Juyuan Luo; Shuo Wang; Cheng Shen; Yulin Li (Natural Product Research, 2026)

Enhancement of self-heating decarbonization and activation of coal gangue by pellet sintering process - Wenzhuo Ma; Tao Dong; Deqing Zhu; Jian Pan; Zhengqi Guo; Congcong Yang; Siwei Li; Wuju Zhang; Yuping Yang; Denan Hou (Process Safety and Environmental Protection, 2026)

Preliminary evidence of polyvinyl chloride microplastics inducing ferroptosis in the cerebral cortex of ducks - Li Wang; Hongsheng Song; Tao Wang; Yan Chen; Yonggang Ma; Xishuai Tong; Hui Zou; Jianhong Gu; Xuezhong Liu; Jianchun Bian; Zongping Liu; Yan Yuan (NeuroToxicology, 2026)

Dynamics and drivers of last-resort antibiotic resistance genes during pilot-scale aerobic fermentation of municipal sludge and subsequent bok choy pot trials - Li-Tao Zhou; Da-Hai He; Jiang Li; Ruo-Xue He; Shi-Jin Ma; Guang-Yu Gong; Xiao-Shuang Zou; Sen Li; You-Fei Zhou; Wei-Jie Hu (Journal of Hazardous Materials, 2026)

Persulfate-based advanced oxidation processes enhanced biomass carbon activation efficiency for high-performance supercapacitors - Tao Zhang; Hongkai Di; Hanrui Ma; Guangzhe Zhang; Kunjie Li; Ruihong Zhao; Wentao Niu; Jiangze Han; Jingsi Yang (Fuel, 2026)

Reveal the potential key role of characteristic metabolites of wet glycosylated Pleurotus eryngii protein-Oat β-glucan complex in the process of improving intestinal barrier function-from the perspective of intestinal digestion and microbial fermentation - Qi Tao; Xinyi Li; Yaning Duan; Yunyan Yu; Qiuhui Hu; Ning Ma; Anxiang Su; Chenlu Yang; Gaoxing Ma (Food Bioscience, 2026)

Model improvement for simulating the effects of individual and combined low-temperature stress at different reproductive stages in rice - Yanying Shi; Haoyu Ma; Tao Li; Erjing Guo; Tianyi Zhang; Xijuan Zhang; Xianli Yang; Lizhi Wang; Shukun Jiang; Litao Zhou; Wenmeng Zhang; Kaixin Guan; et al. (European Journal of Agronomy, 2026)

A hierarchical dynamic network enables closed-loop recyclable solid-solid phase change materials with high toughness and infrared stealth capability - Siyu Feng; Jiahui Zeng; Zhenshuo Huang; Muyang Li; Wenwen Wu; Dongli Fan; Peng Zhu; Haiyan Ma; Hongbin Lu; Yufeng Cao; Tao Qian (Chemical Engineering Journal, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

Role of hygroscopicity in indoor transmission of exhaled submicron particles - Yanpei Li; Nan Ma; Alfred Wiedensohler; Lingyun Guo; Zonghan Xue; Biao Luo; Shaowen Zhu; Zheng Yang; Juan Hong; Jiangchuan Tao; Yaqing Zhou; Qiaoqiao Wang (Building and Environment, 2026)

Dominant drivers of soil multifunctionality change: interactions among soil, plants, and the atmosphere - Tiantian Luo; Weiyi Zhou; Yun Shi; Fenghong Zhang; Guo Rui; Hongyuan He; Tao Wu; Hongxia Li; Yiting Ma (Plant and Soil, 2026)

A Cross-Control-Logic and Disturbance-Adaptive Line-Adhering Intelligent Navigation Framework for Autonomous Ships - Donglei Yuan; Xianghua Tao; Guanghui Li; Xiaochi Li; Yichuan Lu; Wei He; Feng Ma (Journal of Marine Science and Engineering, 2026)
Conventional heading-keeping autopilot logic exhibits well-known performance limitations under complex route geometry and environmental disturbances. Motivated by this limitation, this paper proposes a line-adhering intelligent navigation framework for disturbance-aware path-following of autonomous ships. The core idea is based on numerical simulation scenarios representing curved inland/coastal routes under wind- and current-disturbance conditions. The addressed gap lies in the limited integration of route-geometry adherence, human-like maneuvering logic, and disturbance-aware controller reconfiguration within conventional heading-centered ship path-following frameworks. Therefore, a rough-set classifier identifies disturbance modes and reconfigures PID, LQR, and MPC controllers in real time. Moreover, a vessel-dynamics constrained Bézier refinement method generates high-resolution reference paths aligned with navigational curvature limits. Mathematical models including the Nomoto and MMG formulations are incorporated to ensure controllability and dynamic feasibility. Results show that the proposed framework improves path-following precision, robustness, and comfort under the considered simulation conditions.

Reshaping the plateau of ecosystem services value of farmland: practice and exploration of high-standard farmland construction in China - Tao Wang; Yijia Liu; Li Ma (Environment, Development and Sustainability, 2026)

Development of Two Multienzyme Isothermal Rapid Amplification Techniques for the Rapid Visual Detection of Micropterus salmoides rhabdovirus - Qingyue Xu; Yiping Lin; Yixia Ma; Zhantian Liao; Tao Li; Shuai Wang; Chunguo Liu; Zhan Luo; Qingqing Song; Shun Zhou; Yunji Xiu (Journal of Fish Diseases, 2026)
Largemouth bass ( Micropterus salmoides ) is an important freshwater‐cultured species in China. M. salmoides rhabdovirus (MSRV) is a devastating pathogen that causes high mortality (exceeding 90% in acute outbreaks) in largemouth bass fry, posing a severe threat to the global largemouth bass aquaculture industry. To address the urgent demand for rapid, on‐site MSRV detection, two multienzyme isothermal rapid amplification (MIRA)‐derived methods—multienzyme isothermal rapid amplification with fluorescence detection (MIRA‐FLU) and multienzyme isothermal rapid amplification with lateral flow dipstick (MIRA‐LFD)—were established and optimized targeting the conserved nucleoprotein (N) gene of MSRV. The performance of both methods was systematically evaluated, and their practical applicability was verified using clinical samples collected from diseased fish farms. The results demonstrated that both methods exhibited high sensitivity, with a detection limit of 9 copies/μL for the standard plasmid. Both detection methods demonstrated high specificity and showed no cross‐reactivity with other common aquatic viruses, indicating their high specificity for MSRV detection. MIRA‐FLU completed amplification within 25 min at 42°C, while MIRA‐LFD achieved amplification within 12 min at 37°C. MIRA‐FLU is used for real‐time fluorescent quantitative detection, whereas MIRA‐LFD enables visual, instrument‐free reading via lateral flow test strips. In comparative analyses of clinical samples, the diagnostic results of MIRA‐FLU and MIRA‐LFD were compared with those of the standard conventional PCR test and showed nearly 100% consistency. Therefore, our MIRA‐FLU and MIRA‐LFD detection methods demonstrate excellent specificity and sensitivity, providing two simple, rapid and reliable approaches for large‐scale field surveys of MSRV in resource‐limited settings.

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Plant patches maintain soil nematode abundance and energy flow but not community structure in severely-degraded alpine grasslands in the Qinghai-Tibetan Plateau - Jie Wen; Tao Liu; Xiaoli Wang; Junjie Lei; Chunhui Zhang; Zhilei Li; Yichen Xu; Yuan Ma; Buqing Zhong; Xiaocui Liang; Wende Yan; Yushou Ma; et al. (Journal of Environmental Management, 2026)

Geochemical behavior of thallium shifts across seasons in a granite weathering river - Shuxin Pan; Shuaibei Li; Qiugui Wang; Jilong Ma; Lei Yan; Enzong Xiao; Yuxiao Chen; Yong Tao; Tangfu Xiao (Journal of Environmental Sciences, 2026)

Hydroclimatic variability since 29 ka at Gongzhu Co, SW Qinghai-Tibet Plateau: A multi-proxy reconstruction - Haoran Tai; Mingda Wang; Tao Li; Bo Yuan; Xiaoying Chen; Xinwei Liang; Tonggang Zang; Dewen Ma; Dejun Wang; Kan Yuan; Xiaoxue Gao; Zhe Sun; et al. (Global and Planetary Change, 2026)

Enhancement of ultrasound treatment on the structural and gelation properties of large yellow croaker (Pseudosciaena crocea) roe protein isolate - Jiao Jia; Li-Lin Ma; Qian-Hao Ma; Jia-Nan Yan; Bin Lai; Ce Wang; Yi-Nan Du; Hai-Tao Wu (Food Research International, 2026)

Microbial biomass P mediates post-silking rhizosphere P mobilization in maize–soybean relay strip intercropping - Wenjia Ke; Xiaomei Yang; Tianju Wu; Youmi Huang; Li Wang; Yuntong Ma; Wenyu Yang; Xiaoqian Chen; Furong Zhong; Tao Zhou (Field Crops Research, 2026)

Durability and microstructure of gas diffusion layer in proton exchange membrane fuel cells under cyclic mechanical stress - Tiancai Ma; Yuewen Zeng; Chang Du; Ziheng Gu; Ruitao Li; Julong Zhou; Fenglai Pei; Haolong Luo; Yihao Tao; Huijin Guo; lei Shi; Jianbin Su (Chemical Engineering Journal, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

A morphology-adaptive in situ assembled microporous annealed particle scaffold for localized exosome delivery in spinal cord injury therapy - Bo Li; Kaixuan Ma; Tao Yuan; Haoran Wu; Yiming Huo; Haojue Wang; Xiao Xu; Yang Liu; Lei Yang; Kai Chen (Chemical Engineering Journal, 2026)

Fructan PKP-1b from Polygonatum kingianum attenuates aging and neurodegeneration by inhibiting insulin/IGF-1 signaling - Haitao Guo; Jiahui Wang; Yueying Yuan; Jinchai Qi; Shuqi Li; Heng Chen; Zhixing Huang; Hao Liu; Shaojun Yu; Zekun Yu; Gengyang Liu; Jing Han; et al. (Carbohydrate Polymers, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

Occurrence, Distribution and Ecological Risk Assessment of Phthalate Esters in Sediments of Poyang Lake and its Tributaries - Yan Ma; Runxuan Li; Qingyuan Liu; Ke Zhang; Jiale Bi; Bo-Tao Zhang; Yan Liu; Peng Shao (Water, Air, & Soil Pollution, 2026)

Simultaneous remediation of heavy metals in mining soil using nZVI-supported attapulgite - Jun Ren; Caili Tong; Hanru Ren; Ming Gao; Gui Ma; Yunmeng Li; Rui Zhu; Xuri Mu; Chun Yang; Ling Tao (Environmental Geochemistry and Health, 2026)

Long-term nitrogen addition of different types and levels altered the relationship between species diversity and ecosystem multifunctionality in alpine grasslands - Hongye Su; Tao Chang; Li Ma; Zhonghua Zhang; Ruimin Qin; Haze Adi; Jingjing Wei; Shan Li; Xue Hu; Zhengchen Shi; Huakun Zhou (Soil Ecology Letters, 2026)

The influence of substituting alfalfa hay with amaranth hay on production performance, nutrient digestion and antioxidant capacity in fattening lambs - Tao Li; Jie Liao; Mengrong Su; Chunmei Du; Fuquan Yin; Guang Cao; Jian Ma (Animal Feed Science and Technology, 2026)

Brucella-infected macrophage-derived microparticles enhance the host anti-Brucella acquired immune response - Yuting Zhang; Jing Yuan; Aodi Wu; Zexuan Wang; Rongrong Ni; Kexin Yan; Xiaoyang Liang; Tao He; Maoyuan Gu; Chuang Meng; Honghuan Li; Changsuo Zhang; et al. (Veterinary Microbiology, 2026)

Experimental and numerical investigation on deformation response of existing tunnels induced by shield under-crossing excavation considering influence of lining stiffness loss and ground void - Zhiguo Zhang; Yinong Hao; Tao Xu; Shaokun Ma; Junjie Li; Yin Ni; Jiaxuan Li (Tunnelling and Underground Space Technology, 2026)

Subject and Physician Satisfaction With Repeated AbobotulinumtoxinA Treatments of Glabellar Lines in Chinese Subjects: Results From a Real-World Study - Jianmei Huang; Chungyung Keung; Li Ma; Jingjing Zhao; Zhiqiang Xue; Shuxian Zhang; Yuan Chen; Lin Tao; Qingyang Liu; Cecilia Persson; Inna Prygova; Weimin Song (Toxicon, 2026)

Transcriptome profiling of granulosa cells during follicular development identifies RMDN2 polymorphisms associated with reproductive traits in chickens - Ashi Li; Yuechen Liao; Dehui Li; Tao Li; Yangqiwen Luo; Meng Ma; Xingguo Wang; Liumei Sun; Liang Qu; Manman Shen (Theriogenology, 2026)

Unified quasi-solid electrolyte design for coupled stabilization of Zn anode and I2 cathode in aqueous Zn-I2 batteries - Meng’an Wang; Tao Li; Shicong Zhang; Hexian Ma; Yang Xu; Yi Shen; Chenyu Wei; Tao Zhang; Tianquan Lin (Science Bulletin, 2026)

Generating an annual 30 m rice cover product for monsoon Asia (2018–2023) using harmonized Landsat and Sentinel-2 data and the NASA-IBM geospatial foundation model - Husheng Fang; Shunlin Liang; Wenyuan Li; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Tao He; Feng Tian; Fengjiao Zhang; Hui Liang (Remote Sensing of Environment, 2026)

An integrated atmospheric-topographic correction framework for land surface reflectance estimation using a spatial-spectral Attention U-Net model - Yichuan Ma; Shunlin Liang; Han Ma; Tao He; Xiran Shi; Wenyuan Li; Dejun Cai; Xiongxin Xiao; Shikang Guan; Weiwei Liu; Jianglei Xu; Yongzhe Chen; et al. (Remote Sensing of Environment, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Scutellaria baicalensis extract prevents metabolic dysfunction-associated steatotic liver disease by modulating the gut-liver axis in high-fat diet mice - Liting Ma; Yizhu Wang; Tao Ren; Lijia Pan; Xinze Li; Shen Wang; Dihao Li; Meiyu Zhang; Fangtong Li; Fei Zheng; Hao Yue (Phytochemistry, 2026)

Optimizing irrigation regimes and split nitrogen topdressing enhances grain yield and bread baking quality in strong gluten wheat - Chuan Zhong; Jing Ma; Xiaoru Liu; Shuping Shi; Mengyu Li; Yanjie Zhang; Fan Li; Tao Yang; Mingrong He; Xinglong Dai (Field Crops Research, 2026)

Promoting the ionic conductivity and self-healing ability of micro-Si anode via a versatile crosslinker of Al(H2PO4)3 - Yang-Ning You; Shu-Hao Guo; Tao Li; Yu-Jun Bai; Xi-Cheng Ma (Chemical Engineering Journal, 2026)

Revealing the electronic-scale origins of polysulfide catalytic conversion on amorphous MoS2 toward ultrastable lithium–sulfur batteries - Jiayue Li; Meng Jing Jin; Wei Kang; Chengzhu Yi; Yanchun Wang; Jing Liu; Hongruo Ma; Limao Cairang; Renqian Tao; Zhenxing Zhang; Xiaojun Pan; Guowen Sun; et al. (Chemical Engineering Journal, 2026)

Engineering interfacial charge redistribution in Sb2Te3/MoS2 topological heterojunction for enhanced bifunctional electrocatalysis - Shoujun Ma; Shouyi Wang; Dingxuan Zhang; Xuan Fang; Ying Yang; Dan Fang; Haiyan Tao; Baitong Zhou; Jiayao Jiang; Junjie Pan; Dengkui Wang; Yong Wang; et al. (Chemical Engineering Journal, 2026)

Phosphorus transformation in co-pyrolysis of biogas residue driven by intrinsic Fe/Mg in Fenton sludge: multi-scale mechanisms and enhancement of phosphorus bioavailability - Lei Ma; Hongxing Tu; Jingtong Li; Chunyang Chen; Liandong Zhu; Xiujuan Wang; Qianyi Cai; Junshi Tao; Jinrong Qiu; Zifeng Luo (Bioresource Technology, 2026)

Comprehensive Evaluation of Maize Material Production and Nitrogen Utilization in Saline-Alkali Land Under Different Nitrogen Application Levels Based on EWM-TOPSIS-AISM Models - Weifan Liu; Hao Liu; Fenglan Ma; Menghu Wan; Tao Li; Xiaoying Ma; Yong Cui; Linfeng Huang; Jili Liu; Na Wu (Journal of Soil Science and Plant Nutrition, 2026)

Hydrochemical and isotopic evidence of aquitard brine evolution from Late Pleistocene paleo-seawater in the coastal plain of southern Laizhou Bay, China - Xiaomin Lin; Jing Li; Tao Zhang; Qingshan Ma; Alhassan Abdullah (Hydrogeology Journal, 2026)

Experimental study on mechanical properties of clay reinforced by fiber and phosphogypsum slag-based cementitious materials - Qiang Ma; Yue Tao; Hang Shu; Lei Xi; Meng Li (Bulletin of Engineering Geology and the Environment, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

Effect of Fluid pH on Subcritical Crack Growth and Mineral Morphology of Marble Under Double Torsion Tests - Mimi Wang; Diyuan Li; Xibing Li; Jie Tao; Jinyin Ma (Rock Mechanics and Rock Engineering, 2026)

Integration of aerobic riverbank filtration and ultrafiltration for advanced water treatment and membrane ageing reduction - Jian Zhao; Siqi Wu; Zhanyan Chen; Tingming Ye; Bi Chen; Shuoxun Dong; Baiwen Ma; Tao Lyu; Gang Liu; Mathias Ulbricht; Li Wang; Huijuan Liu (Water Research, 2026)

UVB-activated permanganate enables rapid emerging organic contaminants decontamination through synergistic HO• and reactive manganese species - Ping Li; Peng Su; Qixiao Lv; Qiuling Lu; Ying Xu; Xiangyang Hou; Jucai Xu; Jun Ma; Tao Yang (Water Research, 2026)

A comparative analysis of numerical approaches for hydrogen storage in salt cavern during injection-stand-withdrawal process with brine impact - Wanrui Hu; Wenjing Li; Tao Sun; Chengyu Ma; Xiuxiu Miao (Tunnelling and Underground Space Technology, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Analyzing the effects of the transportation environment and green spaces on residents' satisfaction - Hanyan Li; Jing Ma; Sui Tao (Journal of Transport Geography, 2026)

A concept-drift-driven hybrid modeling framework for high-resolution ambient surface NO2 retrieval in Beijing-Tianjin-Hebei Region, China - Junyu Wang; Jian Qian; Jiayi Chen; Caiying Luo; Sheng Li; Na Yang; Ruoyu Li; You Zou; Tao Zhang; Fei Yin; Chenglin Tao; Nan Wang; et al. (Journal of Hazardous Materials, 2026)

Exposure risk assessment of polycyclic aromatic hydrocarbons (PAHs) in soil around coking sites at regional scale based on stacking ensemble model - Weiwei Shi; Xuepu Ma; Lingzhi Luo; Xiaoyong Liao; Huan Tao; You Li; Hongying Cao (Journal of Hazardous Materials, 2026)

Machine learning-optimized efficient CO2-to-CO conversion in a novel catalyst-free spark discharge plasma - Guangdong Yang; Tao Jiang; Jing Wen; Tangxia Yu; Changqing Li; Lan Zhang; Mingze Ma (Journal of Cleaner Production, 2026)

Sulfur-doped carbon for enhanced flue gas desulfurization: Synergistic experimental and DFT insights - Jun Li; Xiang Wang; Xiao Zhu; Yuke Li; Min Yan; Yang Ma; Ping Cui; Jingcai Chang; Liqiang Zhang; Tao Wang; Chunyuan Ma; Zhanlong Song (Fuel, 2026)

Improving rice quality by enhancing key amylose and amylopectin and their complexation with fatty acids - Tao Liu; Xinrui Li; Jiayue Wang; Zhonglin Wang; Huilai Yin; Zhixin Li; Wenqi Yuan; Xiangyu Xu; Xiaomeng Shen; Yue Huang; Zhiyuan Yang; Yongjian Sun; et al. (Food Chemistry, 2026)

Functionalized Zr-MOFs regulated polyamide membrane toward high-efficiency nanofiltration - Shuangqiao Han; Pengjia Zhu; Xiaofei Ma; Rui Li; Huixian Wang; Xueqi Tao; Xiao Wang; Yuping Tong; Yatao Zhang; Junyong Zhu (Desalination, 2026)

Self-adaption ultra-small coordination polymer-incorporated nanofibers for multipronged management of diabetic wounds - Peirong Zhou; Min Jiang; Silei Li; Xuemin Ma; Yajuan Hu; Junliang Chen; Yun He; Gang Tao; Rui Cai (Chemical Engineering Journal, 2026)

Sulfur-induced electronic coupling in g-C3N4/Ti3C2Tx-MXene 2D/2D heterojunction enables highly efficient solar-driven disinfection - Rong Ma; Xiaochun Tao; Shuo Li; Chenglong Chen; Qinqin Liu; Shaosheng Rao; Juan Yang (Chemical Engineering Journal, 2026)

Comprehensive study on the competitive mechanisms of oxidation and nitriding reactions in ferrosilicon alloys under high-temperature air condition: reaction mechanism, product properties, and kinetics - Tao Yang; Lijuan Chen; Jinrong Ma; Pengfei Wang; Yanfeng Cheng; Hualin Peng; Bo Wei; Maierhaba Abudoureheman; Shuanglong Li (Chemical Engineering Journal, 2026)

Integrated microbial and metabolic coordination orchestrates antler growth induced by guar gum and xylo-oligosaccharides - Songze Li; Ruijia Deng; Jianan Sang; Yuhang Zhu; Cuiliu Ma; Weixiao Nan; Tao Wang; Huazhe Si; Zhipeng Li (Carbohydrate Polymers, 2026)

Millennial-scale terrestrial weathering history and anthropogenic imprint in an alpine lake from Central Asia: evidence from the sedimentary geochemistry of Lake Sayram - Wen Liu; Yizhen Li; Long Ma; Jingyu Wang; Tao Zeng; Jilili Abuduwaili (CATENA, 2026)

Overlooked closed reactor thermal steam discharge: steering ARGs fate and microbiome evolution in kitchen waste-livestock manure composting - Jiani Wang; Tianlong Song; Qianlin Gao; YiRan Zhou; Yan Yang; Xia Gao; Ruonan Ma; Guoxue Li; Tao Jiang; Jiali Chang; Jing Yuan (Bioresource Technology, 2026)

Characterizing dynamic indoor pollutant dispersion pathways using an interpretable attention-driven spatiotemporal modeling framework - Ruiliang Ma; Yuan Zhao; Li Wang; Lingshu Jia; Zhongji Guo; Guolong Li; Tao Huang; Xiaoxuan Mao; Hong Gao; Jianmin Ma (Building and Environment, 2026)

Characterizing low-supersaturation CCN activity with AAC-CCNC system at a mountain site in continental region in China - Mengyao An; Jiangchuan Tao; Yaqing Zhou; Minghua Liang; Li Li; Juan Hong; Linhong Xie; Weikang Ran; Shaobin Zhang; Qiaoqiao Wang; Qiyuan Wang; Nan Ma (Atmospheric Research, 2026)

Adaptive frequency-domain synthesis and performance evaluation for wideband multi-antenna signals - Xuejian Li; Hong Ma; Yiwen Jiao; Tao Wu; Xueshu Shi; Hongbin Ma; Yuxin Wang (Advances in Space Research, 2026)

Biogeochemical controls on the co-occurrence of mid-depth pH and DO minima in the inner shelf of the East China Sea - Dewang Li; Zhongqiang Ji; Bin Wang; Chen Zeng; Haiyan Jin; Zhibing Jiang; Xiao Ma; Qinyu Liu; Yixuan Tao; Yanbin Tang; Hongliang Li; Feng Zhou; et al. (Marine Pollution Bulletin, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

Are iron and manganese key factors in nitrate attenuation within the shallow groundwater of the nitrogen attenuation zone? - Qiwen Xia; Jiangtao He; Baonan He; Binghua Li; Cong Yan; Wei Li; Hua Zou; Chenchen Tao; Zhen Chen; Shuo Ma (Water Research, 2026)

Orthogonal-optimized n-doped biochar via microwave pyrolysis for efficient peroxymonosulfate activation and tetracycline hydrochloride degradation - Shihao Xu; Xiaobo Huang; Zhongyu Tao; Li Chen; Yujia Zhang; Xinhong Fu; Haoyu Ma; Yongze Jiang; Jingying Wen; Wenrui Zhou; Cornelis F. de Hoop; Jinqiu Qi; et al. (Process Safety and Environmental Protection, 2026)

Ozone treatment maintains the sweetness and volatile odor of sweet corn by enhancing antioxidant capacity and resistance to disease - Tianyu Li; Zhengrong Wang; Yunxiang Wang; Christopher B. Watkins; Hua Chen; Chunmei Bai; Jiejie Tao; Lili Ma; Ronghuan Wang; Yaxing Shi; Xinyi Feng; Shiyu Liu; et al. (Postharvest Biology and Technology, 2026)

Performance evaluation of an enhanced air-lift internal circulation anaerobic–aerobic integrated reactor for treating real domestic wastewater - Yi Jiang; Muhammad Younas; Rui Zhang; Yizhi Zhang; Siyi Bian; Mingjie Hu; Die Liang; Linshan Yang; Pan Li; Suhui Xia; Wenyang Tao; Yuji Ma; et al. (Journal of Water Process Engineering, 2026)

Dustfall source-apportionment and source-oriented health risk assessment using unsupervised machine learning, PMF, and HYSPLIT: Insights from a hotspot area in Xinjiang, China - Buweihaidiqie Maitituersun; Long Ma; Yizhen Li; Lingxin Kong; Tao Zeng; Wen Liu; Jilili Abuduwaili (Journal of Hazardous Materials, 2026)

Quantifying the dual role of river network density in cadmium accumulation from mining area (source) to agricultural soil (sink) and implications for mitigation strategies - Hongxi Ma; Huan Tao; You Li; Bayier Wulijia; Qixing Yao; Xiaoyong Liao (Journal of Hazardous Materials, 2026)

Preparation of KMnO4 modified N-doped bamboo biochar by microwave pyrolysis for enhancing heavy metals adsorption from aqueous solution - Xiaobo Huang; Shihao Xu; Li Chen; Zhongyu Tao; Haoyu Ma; Yujia Zhang; Xinhong Fu; Jinqiu Qi; Xingyan Huang (Journal of Contaminant Hydrology, 2026)

Study of deformation and fragmentation of emulsion under electric field and shear based on fluid dynamics - Chuanke Liang; Zexin Liu; Sichen Wei; Nanjun Ma; Qijie Sun; Tao Li (Fuel, 2026)

Performance analysis and optimization of an ammonia-fueled solid oxide fuel cell-micro gas turbine-rankine cycle system as a power station in an emerging industrial area - Yan Zhu; Liangyu Tao; Wenting Li; Hongchun Zhao; Zheshu Ma (Fuel, 2026)

High-precision prediction of venting capacities for type III hydrogen tanks with TPRDs in standard bonfire tests - Xin Ma; Bei Li; Bing Han; Donglei Sun; Siwei Tao; Xingtao Dai; Xin Jin; Chen Song (Fuel, 2026)

Comparative rheological properties evaluation of virgin and SBS modified-asphalt binder/mastic under solution erosion and its water aging behavior - Feng Ma; Chen Li; Zhen Fu; Jiasheng Dai; Xinye Jiang; Wenhao Dong; Yalu Wen; Ke Shi; Tao Liu; Zhiru Yang; Yao Xue (Fuel, 2026)

Integration of no-tillage practice and legume-based crop rotation enhancing climate resilience - Kaixin Guan; Jin Zhao; Shibo Guo; Chenlong Yang; Wenmeng Zhang; Tao Liu; Mingzhe Li; Xi Wang; Xinyi Zheng; Yi Zhou; Weixin Wu; Yuanbo Zhao; et al. (European Journal of Agronomy, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Microwave-triggered plasma catalysis over Cu/CuOx wires: Synergistic CO2 reduction via enhanced discharge and dynamic oxygen vacancies - Shuning Xiao; Yang Xu; Haotong Ma; Xiuwen Zhao; Hao Zheng; Shuo Wang; Zhanshuo Tao; Hexing Li (Chemical Engineering Journal, 2026)

Pillared amorphous carbon nanotube/MXene nanohybrid for ultrathin broadband electromagnetic wave absorption - Tao Jiang; Tingkai Zhao; Abdul Jalil; Xianghong Li; Muyang Ma (Chemical Engineering Journal, 2026)

Amino-functionalized covalent organic framework-carboxylated carbon nanotubes via covalent bonding for sensitive Tau electrochemical immunosensing - Ping He; Wen-Tao Li; A-Min Zhu; Si-Yuan An; Jun-Ping Ma; She-Ying Dong; Yuan-Zhen Zhou; Jun-Jie Zhu (Chemical Engineering Journal, 2026)

Plants, soil microbes and physical structure jointly regulate natural grassland ecosystem stability across slope scales on the Qinghai-Tibetan Plateau - Yunqiao Ma; Shuzhen Nan; Yu Chai; Wenyin Xu; Yicheng Ba; Qiang Li; Tao Ma; Defei Liang; Chunli Li; Xilai Li; Yang Yu; Gernot Bodner (CATENA, 2026)

Fugitive emissions of fine particulate matter from yak dung stove in the Qinghai-Tibet Plateau Region: Dynamic characteristics and chemical composition - Zongyan Li; Yumiao Li; Yitong Luo; Ke Zhang; Chuan Xiong; Tao Yu; Rongjiang Ma; Yuhao Yi; Mengsi Deng (Building and Environment, 2026)

Basp1 Intensifies Neutrophil Migration and NETs Formation in Traumatic Brain Injury - Jianbin Sun; Tao Li; Tong Zhang; Teng Yang; Pengjiao Ma; Ruitian Zhou; Menglan Tan; Yvsha Huang; Wenhui He; Shuang-Shuang Dai; Yang-Wuyue Liu (Molecular Neurobiology, 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

Organic fertilization enhances soil quality and stabilizes functional fungal networks in semi-arid Astragalus agroecosystems - Abdul Qadir Khan; Chaoli Guo; Yuzhen Liu; Hailong Ma; Rafi Ullah; Zhihao Li; Tao Feng; Feng-Min Li (Applied Soil Ecology, 2026)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Fine-grained classification of Orah mandarin tree plots in UAV remote sensing images based on GACL-DeepLabV3+ - Tao Yue; Hongteng Fang; Siyuan Ma; Qingyang Wang; Jianwu Jiang; Bo Song; Jingwen Li; Yun Chen; Hong Huang (Computers and Electronics in Agriculture, 2025)

How neighborhood environments influence neighborhood satisfaction and travel satisfaction for different purposes? - Hanyan Li; Jing Ma; Sui Tao (Transportation Research Part D: Transport and Environment, 2025)

Integrated physiological and metabolomic analysis reveals metabolite diversity and cultivar-specific characteristics during post-ripening in four Torreya grandis cultivars - Zhenmin Ma; Han Tao; Lin Li; Ruqi Meng; Jinwei Suo; Weiwu Yu; Yuanyuan Hu; Fei Gao; Mohamed A. Farag; Zuying Zhang; Jiasheng Wu; Lili Song (Postharvest Biology and Technology, 2025)

Water migration and browning mechanisms in postharvest litchi pericarp: Insights from LF NMR - Yongqi Chen; Jingyi Li; Difa Zhu; Dongmei Han; Chulin Zhou; Yao Li; Yiwen Liu; Yuwei Ma; Tao Luo; Bingyi Wen; Zhenxian Wu (Postharvest Biology and Technology, 2025)

A multivariate copula framework quantifies the augmenting joint risks of compound high temperature and dry/wet events under climate change in China - Min Liu; Tao Li; Peter Goethals; Fengjiao Song; Jianying Ma; Wei Sun (Journal of Hydrology, 2025)

Role of carbonate in light-driven periodate activation for efficient tetracycline abatement - Shuo Li; Peixuan Sun; Yalun Yang; Heshan Zheng; Jun Ma; Tao Yang (Journal of Cleaner Production, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Probabilistic ecological risk characterizing and source-specific risk apportionment of antibiotics in rivers in the sub-center of Beijing, China - Cong Men; Yuting Ma; Haoquan Jiang; Haoxiang Tao; Zifu Li; Jiane Zuo (Journal of Environmental Sciences, 2025)

Investigation of the structure-activity relationship of resveratrol and its glycosylated and acylated derivatives in relation to their α-glucosidase inhibitory activities - Changdong Lin; Juyuan Luo; Shuo Wang; Cheng Shen; Shucan Zhang; Zhibo Song; Yumei Ma; Yongling Liu; Yulin Li; Tao Chen (Food Chemistry, 2025)

Beyond waste to bioactive potential: advances in olive by-product valorization and resource recovery - Qi Sun; Meiqi Huang; Jian Zeng; Miaomiao Ma; Jianmei Li; Tao Le (Food Chemistry, 2025)

Sensory-directed flavor decoding: key aroma compounds determination in new Chinese apple cultivars using GC × GC-QTOFMS approach - Jianing Li; Tao Lu; Yue Wang; Mengge Tang; Tingting Ma; Mukesh Kumar Awasthi; Xiangyu Sun; Yulin Fang (Food Chemistry, 2025)

MALDI-MSI-based spatial metabolite mapping of Rheum tanguticum roots across growth years reveals functional food potential - Tao Wang; Shuo Zhao; Jianan Li; Famei Zhang; Bo Wang; Huiyuan Ma; Zengrong Ye; Guoying Zhou (Food Bioscience, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Sources and mineralization determine the generation and transformation pathway of sedimentary organic matter over the past century - Shuaidong Li; Tao Huang; Changchun Huang; Jinliang Liu; Qun Liu; Xiaoli Gu; Robert G.M. Spencer; Anne M. Kellerman; Amy M. McKenna; Xiaohua Ma; Quanliang Jiang; Hao Yang (Environmental Research, 2025)

Operation strategy and configuration optimization method of building envelope energy storage-photovoltaic electric heating system for rural houses on the plateau - Yuhao Yi; Chuan Xiong; Yumiao Li; Yunxiang Li; Xiaoyun Zhang; Tao Yu; Rongjiang Ma; Mengsi Deng (Energy and Buildings, 2025)

Deep eutectic solvent-enzyme synergistic pre-treatment strategy for the preparation of cottonseed meal-based porous carbon for advanced supercapacitors - Qu Zhang; Tao Wang; Yan Ma; Pengxu Ren; Bo Li; Yinying Wang; Lina Peng; Dongling Wu (Chemical Engineering Journal, 2025)

Asymmetric actuators via lignin-cellulose nanofibrous composite films with programmable wet-light dual-responsiveness - Qiang Mu; Qiangli Zhao; Min Mao; Yao Liu; Jie Tao; Jiahao Kang; Wei Yong; Xinhai He; Jianhua Ma; Jianwei Li (Carbohydrate Polymers, 2025)

Alpine gravelization compromises ecosystem multifunctionality through vegetation loss and soil nutrient depletion - Shan Li; Hongye Su; Li Ma; Zhonghua Zhang; Qiang Zhang; Faliang Wu; Haze Ade; Xue Hu; Tao Chang; Zhen Wang; Yingcheng Wang; JingJing Wei; et al. (CATENA, 2025)

Atmospheric physicochemical multi-parameter horizonal and vertical mitigation response of two recent Sheveluch volcano eruptions in kamchatka - Qinqin Liu; Lu Gui; Xiangjun Ma; Jinlei Li; Jian Xu; Minghui Tao; Hui Jing; Wenxiu Liu; Qijun Jiao; Jiajun Li; Yuxiang Tian; Zhongting Wang; et al. (Atmospheric Environment, 2025)

Mechanism of Axial Chain Rockbursts in Deep Tunnels: Structural Plane-Induced Stress Concentration Triggered by Drilling and Blasting - Hong-Pu Li; Ben-Guo He; Xia-Ting Feng; Wen-Jing Niu; Tao Ma (Rock Mechanics and Rock Engineering, 2025)

Large deformation mechanisms of the Xiaochatou landslide reactivated by the impoundment of the Wudongde reservoir based on multisource data and the material point method (MPM) - Jiayu Liu; Junwei Ma; Guangcheng Zhang; Hongfei Wang; Tao Chen; Ziyou Zhang; Xin He; Shu Jiang; Yizhe Li; Guanghui Zeng (Landslides, 2025)

Diet as a source of the non-direct genetic effects in metabolic traits: evidence from a family-based GWAS study - Han Xiao; Zechen Zhou; Yujia Ma; Xiaoyi Li; Kexin Ding; Yiqun Wu; Tao Wu; Yonghua Hu; Dafang Chen (Human Genetics, 2025)

Cellular and molecular targets in β-Thalassemia: advances in iron Regulation, Erythropoiesis, and Gene-Based therapies - Xueting Shan; Qianlian Li; Meijuan Wang; Yifan Niu; Zhongxin Sun; Xiang Ma; Tao Wang; Xiangmin Tong; Jufang Zhang; Dong Niu (Functional & Integrative Genomics, 2025)

Roles of Immunity and Endogenous Retroelements in the Pathogenesis of Rheumatoid Arthritis and Treatment Strategies - Mingyang Li; Yuanyuan Sun; Xueting Shan; Yuhong Tong; Yite Fu; Xiang Ma; Zhongxin Sun; Yun Xiang; Yidan Zhu; Tao Wang; Xin Wang; Jufang Zhang; et al. (Functional & Integrative Genomics, 2025)

Autoimmune mechanisms and inflammation in obesity-associated type 2 diabetes, atherosclerosis, and non-alcoholic fatty liver disease - Yuanyuan Sun; Xueting Shan; Mingyang Li; Yifan Niu; Zhongxin Sun; Xiang Ma; Tao Wang; Jufang Zhang; Dong Niu (Functional & Integrative Genomics, 2025)

Improving PPP ambiguity resolution with a modified particle swarm optimization method - Zhiqiang Li; Tao Geng; Zhuang Ma; Xin Xie; Lingyue Cheng; Hang Yu; Jie Yang (Advances in Space Research, 2025)

Efficiency of apple trees-watermelon intercropping assessed by yields and photosynthesis response - Pei-pei Zhang; Xiao-mei Ding; Song-tao Liu; S. M. El-Sawy; Xiao-hu Ma; Chao-fan Wei; Zhi-xiang Zhang; Wei Zhang; Qian Li (Agroforestry Systems, 2025)

Corrigendum to “Biogeochemical cycles of iron: Processes, mechanisms, and environmental implications” [Sci. Total Environ., 951(2024) 175722] - Huan Liu; Tao Liu; Shengnan Chen; Xiaoyan Liu; Nan Li; Ben Ma; Xiang Liu; Sixuan Pan; Haihan Zhang (Science of The Total Environment, 2025)

Anomaly detection in unmanned surface vehicles via multimodal learning - Meiyue Tao; Zhongyuan Jiang; Xiuxuan Shen; Yanyi Liu; Xiaotong Fang; Zhiwei Chen; Gang Zhao; Xinghua Li; Jianfeng Ma; Philip S. Yu (Ocean Engineering, 2025)

Coffee intercropping reduces soil N2O and N2 emissions: Empirical test and meta-analysis - Ronghua Li; Nanke Ma; Yue Shi; Hao Sun; Ziman Yang; Yun Zhou; Liyin Li; Syed Turab Raza; Tao Ye; Li Rong; Leqi Fang; Zhe Chen; et al. (Journal of Environmental Management, 2025)

Enhancing soil health and microbial resilience with organic fertilization in semi-arid Astragalus ecosystems - Abdul Qadir Khan; Chaoli Guo; Rafi Ullah; Farhan Ahmad; Zhihao Li; Hailong Ma; Tao Feng; Feng-Min Li (Journal of Environmental Management, 2025)

How does thinning affect the photosynthetic parameters and their responses to environmental factors in a subtropical plantation? - Mingjie Xu; Shengtong Li; Fengting Yang; Tao Zhang; Qingkang Li; Zeqing Ma; Xianjin Zhu; Xiaoli Fu; Xiaoqin Dai; Jiaxin Song; Ning Chen; Jiaxing Zu; et al. (Forest Ecology and Management, 2025)

Enhanced catalytic degradation activity through quenching introduces Pd doping in TiO2 derived from NH2-MIL-125(Ti) - Jinqiang Fu; Fenglan Liang; Wenjing Zhong; Tao Kuang; Ziyuan Yin; Yongshi Li; Zhenggui Huang; Hongli Liu; Deyun Ma (Environmental Research, 2025)

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

Comparative experimental study on the cooling effect of passive nanofluid roofs in glass greenhouses - Jiangqiaoyu Ma; Tao Li; Shaolong Shi; Yuan Yuan; Qianjun Mao (Energy and Buildings, 2025)

High energy electron irradiation promotes the space weathering process on the nearside of the Moon - Zhenyu Xu; Yazhou Yang; Longlong Zhang; Shuai Li; Hongwei Li; Panpan Zhang; Mengyuan Zhang; Haolin Yin; Mengze Tao; Zichen Wei; Hao Zhang; Lianghai Xie; et al. (Earth and Planetary Science Letters, 2025)

Hierarchically structured Fe-Cu-Ni-O@Al2O3-ZrO2 monolithic oxygen carrier for efficient chemical looping hydrogen production - Zixiang Gao; Tao Li; Suxia Ma; Haiyu Liu; Rui Xiao (Chemical Engineering Journal, 2025)

Expired Vitamin C derived CoO and Co nanoclusters embedded biochar enhanced peroxymonosulfate activation for chloroquine phosphate degradation - Shangchao Fan; Ruotong Xu; Qihong Tao; Yiting Ma; Nan Chen; Ying Li; Jing Guo; Cheng Chen (Chemical Engineering Journal, 2025)

Preparation of AuSe-BNPs/CFME and its high-sensitivity simultaneous detection of caffeic acid and dihydrotanshinone I - Han Cheng; Yanbing Pan; Tao Fang; Uchkun Ishimov; Awais Ihsan; Abrar Hussain; Ruiting Tian; Wenwen Ma; Jun Li; Xianju Huang (Chemical Engineering Journal, 2025)

Confinement-effect adsorbents based on titanium-based lithium ion sieve for efficient lithium adsorption under natural pH conditions - Yuling Ma; Yu Han; Yan Yang; Tao Zhang; Jinxin Yao; Yuchen Li; Yongchen Zong; Wei Wang (Chemical Engineering Journal, 2025)

GWAS and gene co-expression network analysis reveal the genetic control of seed germination under salt stress in maize - Minyan Zhang; Yinchao Zhang; Zhike Deng; Tao Liu; Yuru Liang; Qinglin Li; Chaoying Zou; Zhong Chen; Langlang Ma; Yaou Shen (Theoretical and Applied Genetics, 2025)

METTL16 promotes progression of clear cell renal cell carcinoma via up-regulating N6-methyladenosine modification of KLK4 mRNA - Bo Fan; Yunfeng Niu; Tao Li; Hao Chen; Kunpeng Zeng; Shujun Li; Yongliang Ma (Molecular and Cellular Biochemistry, 2025)

Mechanisms of Freak Wave Generation from Random Wave Evolution in 3D Island-Reef Topography - Aimin Wang; Tao Zhou; Dietao Ding; Xinyu Ma; Li Zou (Journal of Marine Science and Engineering, 2025)
The mechanisms of freak wave generation in 3D island-reef topography are investigated. Four types of freak waves are investigated, based on the wavelet transform for examining the characteristics of freak waves and their mechanism. The freak waves come from a three-dimensional experimental terrain model in a random wave. The wavelet energy spectrum, scale-averaged and time-averaged wavelet spectrum are considered. A new parameter (scale-centroid wavelet spectrum) is defined, based on the wavelet transform algorithm, to quantitatively analyze and further estimate the energy transfer process. The results suggest that the occurrence of freak waves is associated with the gradual alignment of the phases of wave components. The nonlinear interaction in terms of wavelet cross-bispectrum implies that wave–wave interaction, especially with high-frequency components, is obviously enhanced during a freak wave occurrence. The energy transforms to a high frequency during a freak wave occurrence. The current result forms a definite indication that the occurrence of freak waves is caused by the combined effects of linear superposition and nonlinear interactions. Linear superposition begins to take effect long before the freak wave occurs, whereas nonlinear interactions primarily occur during the shorter period just before the freak wave forms. It provides an important reference for the prediction of abnormal waves.

Machine learning-based optimization of enhanced nitrogen removal in a full-scale urban wastewater treatment plant with ecological combination ponds - Jinhu Yun; Yang Yu; Chenliang Tao; Mudi Zhai; Hongliang Zhang; Ying Chen; Hongjing Li; Bao Zhang; Jun Ma (Water Research, 2025)

Integrative scATAC-seq and mtDNA mutation analysis reveals disease-driven regulatory aberrations in AML - Chen Tian; Yijun Dong; Xin Sun; Longchen Xu; Xiaoli Ma; Yuwei Tao; Fang Wang; Haohang Zhang; Jie Li; Kun Li; Yasong Chen; Hongxing Liu; et al. (Science Bulletin, 2025)

Experimental investigation on wave attenuation capacity of kelp farms - Yushun Lian; Jiantao Ma; Dong-ang Li; Jinhai Zheng; Aifeng Tao; Wenxing Chen; Jisheng Zhang; Solomon C. Yim (Ocean Engineering, 2025)

Sustainable nutrients removal from low-strength wastewater: A comprehensive review of biofiltration for resource recovery and carbon neutrality - Chengde Sun; Guangyi Ma; Bin Qi; Kun Wu; Tao Zhang; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Journal of Environmental Chemical Engineering, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Self-regeneration mechanism in nitrogen-doped viscose-based ACF for flue gas desulfurization - Tianli Ma; Li Lv; Shengwei Tang; Tao Zhang; Wenxiang Tang; Zongpeng Zou; Yan Wang (Journal of Environmental Chemical Engineering, 2025)

Insights into phase transformations of PM in high SO2 and HF flue gas from iron ore pelletizing: Implications for cleaner emission control strategy - Qiuyu Li; Ke Ma; Zijian Su; Yuanbo Zhang; Tao Jiang (Journal of Environmental Chemical Engineering, 2025)

Comprehensive review on pretreatment and recovery technology of spent hydrogenation catalysts: Current developments and bottlenecks - Deqing Zhu; Tao Dong; Jian Pan; Wenzhuo Ma; Zhengqi Guo; Siwei Li (Journal of Environmental Chemical Engineering, 2025)

Recent advances on iron bound phosphorus in wetland sediments: characteristics, influencing factors, interactions with organic matter and emerging contaminants - Yi Tao; Shuai Ma; Manman Cao; Junhong Li; Feng Wang; Ziqi Gao; Qing Xu; Jing Guo; Ke Sun; Fei Wang (Environmental Pollution, 2025)

Adaptive mechanisms of moss (Campylopus schmidii) to Cr(Ⅵ) stress in pyrite-mining polluted ecosystems: Integrating biochemical, structural, and molecular perspectives - Huayan Huang; Xin Zheng; Shan Tao; Shiyu Ma; Shuang Feng; Yanglong Li; Ke Liang; Guorui Li; Jia Lei; Huakang Liu; Heng Xu (Environmental Pollution, 2025)

Cold model study of a megawatt-scale chemical looping combustion unit - Yongqi Tong; Jinchen Ma; Xi Chen; Ye Tao; Ao Li; Xiaofan Zhang; Zhongye Li; Zehua Chen; Haibo Zhao (Chemical Engineering Journal, 2025)

Estimating daily NOx and CO2 emissions in typical megacities of east China using TROPOMI NO2 observations - Yizhen Jia; Minghui Tao; Hongming Zhang; Pengfei Ma; Bin Zhao; Rong Li; Dejia Yin; Lijuan Zhang; Haijun Huang; Lunche Wang; Yi Wang; Liangfu Chen (Atmospheric Environment, 2025)

Modification effects of regional temperature and humidity on the relationship between daily mortality and short-term coexposure to fine particulate matter and ozone - Jing Zeng; Jian Qian; Jiayi Chen; Sheng Li; Junyu Wang; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Chenglin Tao; Xinyin Xu; et al. (Atmospheric Environment, 2025)

Health impacts and drivers of long-term ozone and nitrogen dioxide exposure in urban China - Zhaoli Yang; Fangliang Li; Rongmin Ye; Huiping Ge; Hongyu Li; Shulian Zhang; Jiaxin Wang; Yuan Zhao; Hong Gao; Tao Huang; Jianmin Ma (Atmospheric Pollution Research, 2025)

Poly-γ-glutamic acid could enhance the salt resistance of maize by collectively increasing the osmotic, ion, and oxidative stresses resistance and enriching the salt-tolerant PGPBs in rhizosphere soil - Haizhen Ma; Ning Xiao; Yifan Liu; Jiang Liu; Peng Li; Xinru Deng; Jia Wei; Panpan Li; Tao Xia (Plant and Soil, 2025)

Small molecules that targeting p53 Y220C protein: mechanisms, structures, and clinical advances in anti-tumor therapy - Jinglei Xu; Jiahao Yuan; Wenxin Wang; Xiaoning Zhu; Jialong Li; Yule Ma; Shaojie Liu; Jie Feng; Yadong Chen; Tao Lu; Hongmei Li (Molecular Diversity, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Deep learning and machine learning methods based on the NIRS dataset for rapid determination of the nutrients content and quality of oat hay - Li Wang; Tao Wang; Luming Dai; Fei Li; Tao Guo; Fadi Li; Zhiyuan Ma; Kaidong Li; Hui Xu; Maimaiti Reshalaitihan (Computers and Electronics in Agriculture, 2025)

Efficient permanganate activation under UV 222 nm irradiation for enhanced pollutant abatement - Haochen Zhang; Peng Su; Maoju Jiang; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Junhui Zhou; Shuo Li; Bin Zhang; Bei Zhang; Jun Ma; et al. (Water Research, 2025)

Electrification of logistics vehicles: Subsidies or penalties? A tripartite evolutionary game analysis - Quanzhou Tao; Wen Yang; Huiling Zhu; Jianhua Ma; Yanchun Pan; Xin Li (Transportation Research Part D: Transport and Environment, 2025)

Synergistic mechanism for preparation of high-performance ceramsite from coal gangue and iron ore tailings - Wenzhuo Ma; Wuju Zhang; Jian Pan; Deqing Zhu; Tao Dong; Zhengqi Guo; Congcong Yang; Siwei Li (Process Safety and Environmental Protection, 2025)

Metabolic resistance to bensulfuron-methyl endowed by the CdCYP71FL1 gene in Cyperus difformis from China - Yonglin Ma; Mengge Huang; Jianying Qin; Wei Zheng; Tao Zheng; Weisheng Li; Meisha Qiu; Jingbo Li; Yanhui Wang (Pesticide Biochemistry and Physiology, 2025)

Integrated transcriptomic and metabolomic analyses reveal information on the sex pheromone biosynthesis pathways of female Anoplophora glabripennis (Coleoptera: Cerambycidae) - Lulu Kong; Meng Li; Rui Ma; Chenfei Ma; Sainan Zhang; Lili Ren; Jing Tao (Pesticide Biochemistry and Physiology, 2025)

Influences of nutrients on summer algal bloom in the Changjiang plume revealed by high-resolution profiles - Chen Zeng; Dewang Li; Bin Wang; Haiyan Jin; Ruijie Ye; Qianwen Sun; Zhibing Jiang; Yixuan Tao; Xiao Ma; Qinyu Liu; Hongliang Li; Jianfang Chen (Marine Environmental Research, 2025)

Shale fracture prediction using integrated seismic methods - Zhiyuan Sun; Shouyu Xu; Cunfei Ma; Tao Li; Jiachang Zhang; Fancheng Zeng (Marine and Petroleum Geology, 2025)

The hot air circulation ventilation composting system removes antibiotic resistance genes through competitive inhibition by core bacteria - Jiani Wang; Yiran Zhou; Xuyan Li; Tianlong Song; Ruonan Ma; Yan Yang; Jie Yin; Tao Jiang; Guoxue Li; Jiali Chang; Jing Yuan (Journal of Hazardous Materials, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

A universal physically-based topographic correction framework for high-resolution optical satellite data - Yichuan Ma; Shunlin Liang; Wanshan Peng; Tao He; Han Ma; Yongzhe Chen; Wenyuan Li; Jianglei Xu; Shikang Guan (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Influence of the strain rate on the deformation and failure of rocks with multiscale cracks - Yan-jie Feng; Cheng-zhi Qi; Fa Zhao; Tao Li; An-sen Gao; Xiao-yu Ma (Geomechanics for Energy and the Environment, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Corrigendum to “Multi-omics techniques to compare the potential of raw and processed licorice as a food supplement for ameliorating chronic fatigue syndrome” [Food Bioscience, 56, December (2023), 103334] - Wenxin Xia; Heming Zhang; Mengxin Tao; Hao Zhou; Jiahua Ma; Tingting Li; Xiaofen Huang; Xueyan Fu (Food Bioscience, 2025)

An intelligent method for leakage segmentation and area quantification to evaluate the safety performance of tunnels - Tao Tian; Dechun Lu; Fanchao Kong; Yiding Ma; Jiulin Li; Xiuli Du (Engineering Structures, 2025)

Piezoelectric-induced transient phase transition in phosphorus-doped MoS2 for efficient catalytic degradation of perfluorooctanoic acid - Jiapeng Zhong; Rongyue Wang; Yuqiong Li; Dexuan Li; Xi Ma; Tao Shao; Jiazhou Meng; Jinxi Feng; Wei Guo; Jimmy C. Yu; Kengbo Ding; Chuanhao Li (Chemical Engineering Journal, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Monitoring probiotic viability in vivo using DNA nanodevice-decorated bacteria - Siqi Zou; Li Yang; Ruoting Tang; Wumiti Aihemaiti; Ziang Cheng; Jiaxiong Li; Wei Tao; Yue Huang; Jiehua Ma; Chao Li (Chemical Engineering Journal, 2025)

Simulation-guided plasma surface engineering for enhanced triboelectric Nanogenerator performance - Hong Yu; Haonan Ma; Zuying Huang; Mengya Lin; Junming Chen; Ruibin Wu; Ye Tao; Chengrun Li; Ruijia Yang; Xiaozhen Du (Chemical Engineering Journal, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

Insight into the rutin biosynthesis in the unique flavonol synthesis pathway of Tartary buckwheat based on the enzymatic functions of FLSs - Chenglei Li; Jiayi Sun; Guanlan Shi; Xuerong Zhao; Jun Gu; Jiaqi Shi; Qihan Ma; Daoping Zeng; Tao Wang; Zizhong Tang; Tongliang Bu; Hui Chen; et al. (Theoretical and Applied Genetics, 2025)

Assessing the robustness and generalizability of machine learning models for predicting selenium content in rice: a case study from the Pearl River Delta and Eastern Guangdong, China - Guiqi Ye; Tingting Li; Wenda Geng; Kun Qian; Xudong Ma; Qingye Hou; Tao Yu; Zhongfang Yang; Xin Zhu (Environmental Geochemistry and Health, 2025)

Consistency Assessment of the Winds in Reanalysis Datasets and the GIIRS Product Using Radiosondes - Yue Liu; Di Di; Jun Li; Zhenglong Li; Zheng Ma; Jing Zheng; Yan-An Liu; Tao Zhang (Advances in Atmospheric Sciences, 2025)

Quantifying mutual transport contributions of ozone and its precursors among adjacent county-level cities during typical pollution episodes - Demian Lai; Yifei Chen; Yangjun Wang; Yan Zhang; Lin Xu; Zijia Ma; Burcak Kaynak; Shikang Tao; Yu Shang; Li Li (Urban Climate, 2025)

Trigeminal sensations in representative spices: Sensory characteristics, chemical compounds, salt reduction, and mechanisms of saltiness enhancement - Zeyao Qiao; Lei Zhao; Bolin Shi; Xinyu Yu; Tao Yang; Hehe Li; Lulu Zhang; Chao Ma (Trends in Food Science & Technology, 2025)

Transcription and functional analysis of phosphine fumigation regulating heat responses in Bactrocera dorsalis - Yisha Ma; Li Li; Hang Zou; YongLin Ren; Penghao Wang; Tao Liu (Pesticide Biochemistry and Physiology, 2025)

Numerical investigation of internal waves generated by submerged bodies with different aspect ratios in stratified flow - Tao Zhao; Li Zou; Zongbing Yu; Guoqing Jin; Xinyu Ma (Ocean Engineering, 2025)

A clean and carbon-reducing pre-granulation process for enhanced muddy iron concentrate and dust sintering: Parameters optimization and deep mechanism analysis - Yonghe Ma; Yan Zhang; Qiang Zhong; Qian Li; Yongbin Yang; Tao Jiang (Journal of Cleaner Production, 2025)

Impacts of trade-driven outsourced nitrogen emissions on environment and environmental inequities in China - Chaoran Xie; Xiaodong Zhang; Jiayi Xin; Xiaohu Jian; Tao Huang; Zhiyuan Tang; Zhanxiang Wang; Zixuan Li; Zhaoli Yang; Hong Gao; Yuan Zhao; Jianmin Ma (Journal of Cleaner Production, 2025)

Nanobubble enhanced flocculation and filtration of fine coal and associated mechanisms - Guangxi Ma; Jingtao Cui; Jiahuan Li; Xiangning Bu; Huaizhi Shao; Zhaolian Wang; Fengliang Liu; Ahmed Sobhy; Dongping Tao (Fuel, 2025)

Thermal–Mechanical Damage Evolution During Deep Underground Excavation in Prestressed Geothermal Deposits - Y. Zhou; X. Q. Zhou; W. Hong; C. C. Ma; J. Tao; H. T. Li; X. G. Yang; G. D. Lu (Rock Mechanics and Rock Engineering, 2025)

Identification of STAT3 phosphorylation inhibitors using generative deep learning, virtual screening, molecular dynamics simulations, and biological evaluation for non-small cell lung cancer therapy - Weiji Cai; Beier Jiang; Yichen Yin; Lei Ma; Tao Li; Jing Chen (Molecular Diversity, 2025)

Leaching behavior and release mechanism of arsenic and antimony from different storage duration in a phosphogypsum stack - Jun Huang; Chao Ma; Tao Jin; FengJuan Liu; KeXiang Li; JunCai Wang (Environmental Geochemistry and Health, 2025)

Rice water requirement exacerbates groundwater depletion in Northeast China under a changing climate - Yuanbo Zhao; Tao Li; Jin Zhao; Zhentao Zhang; Runze Liu; Yanying Shi; Haoyu Ma; Chuang Zhao; Zhijuan Liu; Xiaoguang Yang (Agricultural and Forest Meteorology, 2025)

Cell-free synthesis of high-order carbohydrates from low-carbon molecules - Yuyao Wang; Peng Chen; Wenwen Li; Yanfei Wang; Qianzhen Dong; Wan Song; Yinlu Liu; Tao Cai; Yuanxia Sun; Jiangang Yang; Yanhe Ma (Science Bulletin, 2025)

SeedLLM·Rice: A large language model integrated with rice biological knowledge graph - Fan Yang; Huanjun Kong; Jie Ying; Zihong Chen; Tao Luo; Wanli Jiang; Zhonghang Yuan; Zhefan Wang; Zhaona Ma; Shikuan Wang; Wanfeng Ma; Xiaoyi Wang; et al. (Molecular Plant, 2025)

Boosting virus enrichment with macroporous magnetic sorbent based on ketoenamine covalent organic framework - Bo'ou Li; Fei Wang; Xiaonan Dong; Yuchang Li; Tao Jiang; Xiaojie Ma; Xiaoping Kang; Bo Wang (Journal of Hazardous Materials, 2025)

Diffusion-driven zircon Zr isotopic fractionation during ultramafic–mafic magmatic differentiation - Li-Tao Ma; Li-Qun Dai; Shao-Bing Zhang; Ren-Xu Chen; Qiong-Xia Xia; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2025)

Corrigendum to “Antifibrotic and antioxidant injectable hydrogel boosts endometrial repair and fertility via sGC/cGMP/SMAD7 signaling activation” [Chem. Eng. J. 512 (2025) 162672] - Donghai Zhang; Liangsheng Li; Jingyi Zhou; Xiaofei Wang; Xiangyu Gao; Junfeng Chen; Tao Duan; Qiuhong Ma; Jigang Li; Yongsheng Yu; Qian Zhou (Chemical Engineering Journal, 2025)

Thermal-electrical synergistic treatment of high-sulfur coal gangue in direct current and chaotic electric fields - Youcai Ma; Xiaoting Li; Shuangli Xi; Jingrui Li; Zhaoming Xie; Guocan Zheng; Jinjing Tang; Qian Zhang; Erfeng Hu; Changyuan Tao; Zuohua Liu (Chemical Engineering Journal, 2025)

Impacts of preparation technologies on biological activities of edible mushroom polysaccharides – novel insights for personalized nutrition achievement - Gaoxing Ma; Xinyi Li; Qi Tao; Sai Ma; Hengjun Du; Qiuhui Hu; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Impacts of glacier shrinkage on peak melt runoff at the sub-basin scale of Northwest China - Min Xu; Pengshou Wang; Xi Zhang; Tao Ma; Junliang Jin; Shichang Kang; Haidong Han; Hao Wu; Zhikang Hou; Xingdong Li; Xiaodong Wu (Journal of Hydrology, 2025)

Optimizing visible light absorption, exciton dissociation, and charge transfer through the interaction of donor-acceptor materials to enhance xanthate photodegradation - Anyang Huang; Jingyu He; Ciyuan Huang; Jinpeng Feng; Wei Mo; Xiujuan Su; Jinlin Yang; Dingzheng Wang; Wenhan Sun; Xiurong Li; Aoping He; Bingsuo Zou; et al. (Journal of Environmental Management, 2025)

Bromine radicals and hydroxyl radicals efficiently degrade emerging organic contaminants in the UVA photolysis of bromine process - Tao Yang; Xiujuan Kong; Ge Zeng; Maoju Jiang; Linqian An; Peng Su; Qixiao Lv; Jun Ma; Juan Li (Journal of Environmental Chemical Engineering, 2025)

A novel chitosan-polyacrylonitrile composite for enhanced selective removal of phenolic contaminants and heavy metals Hg2 + in water treatment - Xiaoting Li; Jinxin Liu; YanFei Zhang; Minli Tao; Ning Ma; Jian Cao; Wenqin Zhang (Journal of Environmental Chemical Engineering, 2025)

Green and efficient conversion of polypropylene wastes into Ni@CNTs hybrids and their application for fire resistant polycarbonate composites - Junlin Zhu; Zhaotian Ba; Yuanmeng Lou; Cui Li; Lili Ma; Jie Liu; Xin Wen; Tao Tang (Journal of Environmental Chemical Engineering, 2025)

Altitudinal influences on soil microbial diversity: The pivotal role of plant functional composition in shaping bacterial and fungal communities - Zhihong Guo; Xiaobo Huang; Cong Li; Siju Ma; Ni Yang; Haibo Li; Tao Zhang; Tongli Wang; Shuaifeng Li; Jianrong Su (Forest Ecology and Management, 2025)

Fermentation biological protection and aroma characteristics of selected non-Saccharomyces yeasts in wine fermentation - Xuan Guan; Yueqi Li; Wen Ma; Junxiang Zhang; Yongsheng Tao (Food Bioscience, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

Weissella paramesenteroides LAB14 mitigates the inflammation elicited by lipopolysaccharide and Salmonella through the suppression of the NF-κB and IRF pathways - Dan Xiong; Mengru Liu; Tao Sun; Zeyang Ma; Yue Sun; Lei Yuan; Li Song; Zhenquan Yang (Food Bioscience, 2025)

Tailored PVDF ultrafiltration membranes with quaternary ammonium salt for enhancing antibacterial efficacy - Ao Ma; Yan Bai; Jie Han; Qi Qi; Chengbing Ma; Yujuan Zhang; Tao Xie; Guohui Zhang; Huiquan Li; Yunkun Wang (Desalination, 2025)

Deep eutectic solvents for ginsenoside extraction and inhibition of ginsenoside hydrolysis in Panax notoginseng leaves: methodology and mechanistic insights - Jia-Yue Liu; Shi-Yao Hua; Li-Juan Ma; Xin Tao; Wen-Yu Fu; Jian-Bo Wan (Chemical Engineering Journal, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Tracking NO2 and CO pollution hotspots at provincial scale in China with TROPOMI observations and image segmentation method - Mingyu Zeng; Minghui Tao; Rong Li; Pengfei Ma; Lijuan Zhang; Jun Wang; Lunche Wang; Yi Wang; Haijun Huang; Liangfu Chen (Atmospheric Environment, 2025)

Insight into dysregulated VEGF-related genes in diabetic retinopathy through bioinformatic analyses - Xiaoguang Wang; Xianglian He; Zhen Li; Tao Mu; Lin Pang; Weiguo Ma; Xuejun Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Frictional characteristics of calcareous sand subjected to oscillatory normal stress - Wengang Dang; Zhenchao Bai; Linchong Huang; Kang Tao; Xiang Li; Jianjun Ma; Yu Liang (Bulletin of Engineering Geology and the Environment, 2025)

The Effect of Plant Quercetin on Immune Function of Microtus Fortis - Yuting An; Dongmei Yang; Bo Ma; Dongming Liu; Kaidong Deng; Shuanglun Tao; Huijuan Cai; Yangjing Ou; Junnian Li (Journal of Chemical Ecology, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

Design of multi-epitope chimeric phage nanocarrier vaccines for porcine deltacoronavirus - GuoQing Zhao; YuMin Zhang; Yan Li; ShiDan Zhang; ShengJing Jiao; XiaoYan Zeng; JingJiao Ma; YuQiang Cheng; HengAn Wang; YaXian Yan; JianHe Sun; Pan Tao; et al. (Veterinary Microbiology, 2025)

Experimental study on the effect of thermal radiation on the performance and temperature of PEM electrolyzer stacks - Tao Du; Changjian Wang; Yunbo Xu; Hongsheng Ma; Yang Li (Process Safety and Environmental Protection, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Influence of two sorghum varieties on metabolic factors, microbial community, and flavor component precursors of strong-flavor Baijiu Zaopei - Hui Zhu; Qiang Li; Ahmed H. El-Sappah; Yong Sun; Ying Liu; Shijiang Pan; Ke Zhu; Xiaoke Sun; Tao Xiong; Huibo Luo; Tao Wu; Linjuan Li; et al. (Food Chemistry, 2025)

Sterilization of blueberry juice under solution plasma process: Factors, quality, and its action mechanisms - Hui Zheng; Bin Li; Qisen Xiang; Bin Du; Baiqing Zhang; Dongbing Tao; Tingyu Zhu; Dongge Wu; Fengming Ma (Food Control, 2025)

Antifibrotic and antioxidant injectable hydrogel boosts endometrial repair and fertility via sGC/cGMP/SMAD7 signaling activation - Donghai Zhang; Liangsheng Li; Jingyi Zhou; Xiaofei Wang; Xiangyu Gao; Junfeng Chen; Tao Duan; Qiuhong Ma; Jigang Li; Yongsheng Yu; Qian Zhou (Chemical Engineering Journal, 2025)

Comparative analysis of Fe(IV)-based advanced oxidation processes in generating disinfection byproducts and altering dissolved organic matter molecular structure - Zeyu Chen; Zhen Wang; Jinxing Ma; Xianhui Li; Yang Zhou; Yuan Gao; Tao Yang; Zhong Zhang; Zihao Wu (Chemical Engineering Journal, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Mapping of resistance genes to powdery mildew based on DNA re-sequencing and bulk segregant analysis in Capsicum - Tao Zhang; Paul W. Bosland; Yan Ma; Yuhang Wang; Wei Li; Weifu Kong; Min Wei; Panpan Duan; Gaoyuan Zhang; Bingqiang Wei (Protoplasma, 2025)

Rice-crayfish farming increases soil organic carbon sequestration by promoting aggregate protection and microbial necromass accumulation - Wanyang Zhang; Jiaqiong Wu; Mingshuang Xu; Tianqiao Ma; Jianwei Lu; Jun Zhu; Tao Ren; Rihuan Cong; Zhifeng Lu; Yangyang Zhang; Xiaokun Li (Agriculture, Ecosystems & Environment, 2025)

Polysaccharides from Ganoderma lucidum attenuate cognitive impairment in 5xFAD mice by inhibiting oxidative stress and modulating mitochondrial dynamics via the Nrf2/antioxidative axis activation - Xiaoqin Liu; Yanbing Li; Jiwei Wang; Tao Meng; Lijuan Song; Lizhi Yang; Jiezhong Yu; Cungen Ma (Metabolic Brain Disease, 2025)

Porcine antibodies reveal novel non-neutralizing universal epitopes on FMDV and their overlaps with neutralization sites - Ying Sun; Shenglin Huang; Fengjuan Li; Shulun Huang; Pinghua Li; Qiongqiong Zhao; Tao Wang; Huifang Bao; Yuanfang Fu; Pu Sun; Xingwen Bai; Hong Yuan; et al. (Veterinary Microbiology, 2025)

Reinforcement learning assisted differential evolution with adaptive resource allocation strategy for multimodal optimization problems - Tao Ma; Hong Zhao; Xiangqian Li; Fang Yang; Chun-sheng Liu; Jing Liu (Swarm and Evolutionary Computation, 2025)

The dual role of electrical stimulation in pain: from management to reconstruction - Kehui Xu; Yuxuan Ma; Tao Ye; Yuzhu Wang; Yannan Xie; Chaohui Li; Franklin R. Tay; Lina Niu; Zhou Li; Kai Jiao (Science Bulletin, 2025)

Historical inputs and biogeochemical transformations of dissolved organic matter since 1850 CE in a small plateau-lake, Southwest China - Shuaidong Li; Xiaolei Wang; Jinliang Liu; Yanhui Zhang; Robert G.M. Spencer; Anne M. Kellerman; Amy M. McKenna; Xiaohua Ma; Quanliang Jiang; Tao Huang; Hao Yang; Changchun Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Anaerobic treatment of refractory industrial organic wastewater: A review of bioenergy recovery and low-carbon nitrogen removal toward carbon neutrality - Zixuan Deng; Chengde Sun; Guangyi Ma; Xinzheng Zhang; Hongbo Guo; Tao Zhang; Xuefei Zhou; Yalei Zhang; Yong Hu; Dapeng Li; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2025)

Ultrasensitive ammonia sensor with excellent humidity resistance based on PANI/SnS2 heterojunction - Ahua Xu; Shupeng Sun; Xinlei Li; Nan Wang; Xiaoyu Wang; Huajin Tao; Yitian Ma; Zhao Zhang; Baoyu Huang; Xiaogan Li (Journal of Hazardous Materials, 2025)

The combination of metagenomics and metabolomics reveals the effect of nitrogen fertilizer application driving the remobilization of immobilization remediation cadmium and rhizosphere microbial succession in rice - Huan-Zhan Zhou; Bu-Qing Wang; Yong-Hong Ma; Yu-Ying Sun; Huan-Lin Zhou; Zhen Song; Yuan Zhao; Wei Chen; Jie Min; Jing-Wen Li; Tao He (Journal of Hazardous Materials, 2025)

Metastable phase reconstruction for enhanced vanadium extraction via cerium oxide-catalyzed low-sodium roasting - Jingrui Li; Kang Tang; Yan Chen; Youcai Ma; Qian Zhang; Zuohua Liu; Changyuan Tao; Yi Peng; Jun Du; Zhaoming Xie; Wenyi He; Biao Shen (Journal of Cleaner Production, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Catalytic application of coal gasification slag-based materials: A review - Lei Han; Haijie Hu; Chengtun Qu; Jinling Li; Lanting Ma; Tao Yu (Chemical Engineering Journal, 2025)

Chemically activating biomass into hierarchically porous carbon as an efficient sulfur host for high-performance room temperature Na-S batteries - Jiawang Liu; Heng Zhang; Baojian Xie; Junquan Cheng; Tao Song; Youcun Bai; Ruguang Ma; Chang Ming Li (Chemical Engineering Journal, 2025)

Oxidative stress in asthma pathogenesis: mechanistic insights and implications for airway smooth muscle dysfunction - Kangxia Li; Xiang Ji; Shan Tian; Jian Li; Yizhu Tian; Xiaoqing Ma; Huanping Li; Hong Zhang; Cai-tao Chen; Wei Gu (Cell and Tissue Research, 2025)

Beneficial role of exogenous enzymes inclusion on improving growth performance, feed utilization, intestinal health and disease resistance against Streptococcus agalactiae of GIFT tilapia (Oreochromis niloticus) fingerlings - Jiajie Tao; Zhongbao Guo; Ye Gong; Liting Chen; Shenyang Ma; Shaojie Liu; Jinliang Zhao; Xuxiong Huang; Naisong Chen; Songlin Li (Aquaculture, 2025)

Extractable organic matter from PM2.5 inhibits cardiomyocyte differentiation via AHR-mediated m6A RNA methylation - Xiaoxiao Li; Shoushuang Zhao; Mengya Zhai; Yuqin Ma; Bin Jiang; Yan Jiang; Tao Chen (Journal of Hazardous Materials, 2025)

Description of three new species of Trigonidiidae Saussure, 1874 from China (Orthoptera: Grylloidea) - Tao Li-Long; Yang Rui-Ying; He Zhi-Xin; Ma Li-Bin (Journal of Asia-Pacific Entomology, 2025)

Integrated experimental studies of pore structure and fluid uptake in the Bossier Shale in eastern Texas, USA - Qiming Wang; Qinhong Hu; Chen Zhao; Cunjian Zhang; Jan Ilavsky; Lingjie Yu; Changli Ma; He Cheng; Xiuhong Li; Yuxiang Zhang; Ivan Kuzmenko; Tao Zhang (Fuel, 2025)

A comparison study on compounding oat β-glucan onto Pleurotus eryngii protein by using different methods: In vitro digestion and fermentation characteristics - Qi Tao; Xinyi Li; Sai Ma; Qiuhui Hu; Gaoxing Ma (Food Hydrocolloids, 2025)

Integrated soil-crop system management improves rice N uptake and yield by reducing iron plaque formation - Shihao Ma; Jianwei Lu; Tao Ren; Shishi Liu; Rihuan Cong; Zhifeng Lu; Jun Zhu; Xiaokun Li (Field Crops Research, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Multimedia distribution and exchange characteristics of organophosphorus flame retardants in a typical semi-arid city in China - Junwen Tang; Yuan Zhao; Li Wang; Zhiyuan Tang; Xiaoxuan Mao; Yuxuan Guo; Baicheng Hu; Guolong Li; Hong Gao; Tao Huang; Jianmin Ma (Environmental Pollution, 2025)

Associations between long-term exposure to fine particulate matter and its constituents with lung cancer incidence: Evidence from a prospective cohort study in Beijing, China - Jinlong Hu; Lei Yang; Ning Kang; Ning Wang; Luyan Shen; Xi Zhang; Shuo Liu; Huichao Li; Tao Xue; Shaohua Ma; Tong Zhu (Environmental Pollution, 2025)

Optimizing building energy consumption through synchronization and asynchronization of occupancy and air-conditioning behavior - Tao Li; Xiangyu Liu; Wenjie Zhou; Jiangqiaoyu Ma; Yang Li; Jiajia Gao; Min Chen; Qianjun Mao (Energy and Buildings, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Unveiling Latent interaction mechanisms influencing the spatial pattern of soil salinity in arid Oases: Insights from integrated modeling - Tao Zeng; Yizhen Li; Long Ma; Lingxin Kong; Jingjing Zhang; Jilili Abuduwaili (CATENA, 2025)

Phosphine fumigation followed by forced hot-air treatment for postharvest control of Bactrocera dorsalis in dragon fruit - Yisha Ma; Li Li; Baishu Li; Qun Liu; YongLin Ren; Penghao Wang; Tao Liu (Journal of Pest Science, 2025)

Utilization of municipal solid waste incineration fly ash with different pretreatments with gold tailings and coal fly ash for environmentally friendly geopolymers - Ke Li; Jie Deng; Ying Zhu; Weiyi Zhang; Tao Zhang; Chao Tian; Jinwei Ma; Yingying Shao; Yanfeng Yang; Yanqiu Shao (Waste Management, 2025)

Uncertainty analysis and parameter optimization of a water yield ecosystem service model: A case study of the Qilian Mountains, China - Bei Wang; Gao-Feng Zhu; Jun-Tao Zhong; Chun-Feng Ma; Ling Zhang; Mei-Bao Tan; Xin Li (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Transcriptome and metabolome association analysis revealed key factors involved in melatonin-mediated copper-stress detoxication in tomato - Geng Meng; Yong Wang; Zhaopeng Ouyang; Lei Deng; Yinglei Bai; Wenqing Li; Xiaojing Ma; Shunshan Shen; Fengzhi Piao; Tao Zhang; Kaile Sun (Journal of Cleaner Production, 2025)

Innovative research on one-step regeneration and reduction of saturated desulfurization coke: Reactivating desulfurization performance and sulfur recovery - Jun Li; Jingcai Chang; Chunyuan Ma; Tai Feng; Liqiang Zhang; Tao Wang; Zhanlong Song (Fuel, 2025)

Rate-dependent FDEM numerical simulation of dynamic tensile fracture and failure behavior in frozen soil - Taiyu Zhang; Zhiwu Zhu; Yue Ma; Zhengqiang Cheng; Tao Li (Computers and Geotechnics, 2025)

Bimetallic Bi–Sn nanoparticles in-situ anchored in carbon nanofiber as flexible self-supporting anode toward advanced magnesium ion batteries - Shaoqing Pan; Miao Cheng; Chen Ma; Huaijia Jing; Tongyu Shen; Jing Hu; Qianqian Liu; Tao Wei; Ruirui Wang; Wanfei Li; Bo Liu (Chemical Engineering Journal, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

Origin of the coeval Nb-enriched and arc mafic igneous rocks: Implications for Paleozoic tectonic evolution of the Southwestern Tianshan - Li-Tao Ma; Li-Qun Dai; Ye-Dan Hu; Zi-Fu Zhao (Chemical Geology, 2025)

Mechanism of cadmium (Cd) enrichment in the soil of karst areas with high geochemical background in Southwest China - Bo Li; Kun Lin; Xu Liu; Xudong Ma; Xuezhen Li; Zhiliang Wu; Cheng Li; Tao Yu; Tiansheng Wu; Zhongfang Yang (Chemical Geology, 2025)

Mining of latent feruloyl esterase resources in rumen and insight into dual-functional feruloyl esterase-xylanase from Pecoramyces ruminantium F1 - Qicheng Shi; Jing Ma; Ahmed M. Abdel-Hamid; Yuqi Li; Pei Zhong; Dongyang Wang; Zhanying Sun; Tao Tu; Weiyun Zhu; Yanfen Cheng; Isaac Cann (Bioresource Technology, 2025)

A novel approach combining indoor mobile measurements and interpretable machine learning to unveil highly-resolved indoor air pollution - Zhiyuan Tang; Yuan Zhao; Li Wang; Junwen Tang; Guolong Li; Jianmin Ma; Hong Gao; Tao Huang; Xiaoxuan Mao (Building and Environment, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Predictive model for peak ground velocity using long short-term memory networks - Dongwang Tao; Haifeng Zhang; Shanyou Li; Jianqi Lu; Zhinan Xie; Qiang Ma (Journal of Seismology, 2025)

Indole-3-Aldehyde alleviates lung inflammation in COPD through activating Aryl Hydrocarbon Receptor to inhibit HDACs/NF-κB/NLRP3 signaling pathways - Pengtao Wang; Wei Tao; Qiujie Li; Wanting Ma; Wei Jia; Yuting Kang (Journal of Molecular Medicine, 2025)

Different rumen biohydrogenation extents in lambs: Assessing fatty acid composition, growth performance, carcass characteristics, and digestibility - Zhiyuan Ma; Fei Li; Yarong Meng; Li Wang; Tao Guo; Zhian Zhang; Xiuxiu Weng; Xinji Wang; Xiumin Zhang; Duohu Tian (Animal Feed Science and Technology, 2025)

Global warming creates the adaptation tipping points of livestock exposure to cold and heat stress on the Qinghai-Tibetan plateau - Ning Zhan; Weihang Liu; Tao Ye; Yiqing Liu; Zitong Li; Heng Ma (Agricultural Systems, 2025)

Depressive intensity, duration, and their associations with cognitive decline: a population-based study in Korea - Kai Lu; Wei Wang; Junyu Wang; Qianqian Du; Chen Li; Yuxin Wei; Menghan Yao; Tao Zhang; Fei Yin; Yue Ma (GeroScience, 2025)

The independent and combined associations of nocturnal sleep duration, sleep midpoint, and sleep onset latency with global cognitive function in older Chinese adults - Xueyao Wu; Jiaqiang Liao; Xin Chen; Jinyu Xiao; Xinyang Dui; Tianpei Ma; Lin Hu; Xunying Zhao; Qian Bu; Mengyu Fan; Tao Zhang; Lu Long; et al. (GeroScience, 2025)

Occurrence, toxicity, and control of halogenated aliphatic and phenolic disinfection byproducts in the chlorinated and chloraminated desalinated water - Youwei Jiang; Shuang Zang; Yue Qiao; Yirang Tan; Hongfei Tao; Qiao Li; Yingjie Ma; Xianshi Wang; Jun Ma (Water Research, 2025)

Creative assets, people, and places: Rural art action practices of US nonprofit organizations - Tao Ma; YueNing Wang; Li Zhang; Wuyang Hong; Xiaochun Yang (Journal of Rural Studies, 2025)

Bioaerosol emission characteristics and potential risks during composting: Focus on pathogens and antimicrobial resistance - Ruonan Ma; Lijuan Peng; Ruolan Tang; Tao Jiang; Jiali Chang; Guoxue Li; Jiani Wang; Yan Yang; Jing Yuan (Journal of Hazardous Materials, 2025)

Identification of the key factors influencing biodeterioration of open-air cultural heritage in the temperate climate zone of China - Chong Wang; Li Wang; Chongbin Bai; Mingpeng Wang; Tao Ma; Honglin Ma; Guangming Zhang; Weiwei Wang; Zisheng Guo; Yanmei Sun; Shiwei Wang (International Biodeterioration & Biodegradation, 2025)

Association of residential greenness exposures on disability: Findings from the cohort study on global AGEing and Adult Health (SAGE) in China - Zhiqing Chen; Yan Shi; Yanfei Guo; Siwen Yu; Qijiong Zhu; Shangfeng Yang; Yuan Zheng; Yayi Li; Yixiang Huang; Wan Peng; Guanhao He; Jianxiong Hu; et al. (Environmental Research, 2025)

Probabilistic evaluation of landslide influence zones considering stratigraphic dips and nonstationarity of soil properties - Jian-Ping Li; Shui-Hua Jiang; Guo-Tao Ma; Mohammad Rezania; Mohaddeseh Mousavi Nezhad; Jian-Hong Wan (Computers and Geotechnics, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Electro-thermal responses polymer systems with continuous shape memory alloys: Merging rapid shape memory and color transitions - Guanzheng Wu; Peiyu Bian; Runxin Xu; Tao Wang; Ziyin Li; Haiyan Mao; Yanlong Tai; Chunxia Wang; Zhipeng Ma; Xiuliang Hou; Nathan Carpentier; Subhajit Dutta; et al. (Chemical Engineering Journal, 2025)

Anaerobic treatment of nitrogenous industrial organic wastewater by carbon–neutral processes integrated with anaerobic digestion and partial nitritation/anammox: Critical review of current advances and future directions - Zixuan Deng; Chengde Sun; Guangyi Ma; Xinzheng Zhang; Hongbo Guo; Tao Zhang; Yalei Zhang; Yong Hu; Dapeng Li; Yu-You Li; Zhe Kong (Bioresource Technology, 2025)

Construction of a physical map for Aegilops geniculata chromosome 7Mg and localization of its novel purple coleoptile gene - Huanhuan Li; Fu Guo; Yanlong Zhao; Chaoli Wang; Ziwei Fan; Yajun Feng; Xiang Ji; Luna Tao; Chao Ma; Jiajun Qian; Yue Zhao; Qianwen Liu; et al. (Theoretical and Applied Genetics, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Horizontal Detection Range Estimation of Deep-Sea Acoustic Shadow Area Based on Vertical Phased Emission Array - Naibin Chen; Dayong Peng; Li Ma; Tao Hu; Haijun Liu; Haifeng Li (Journal of Marine Science and Engineering, 2024)
To scan the horizontal range of the deep-sea shadow zone with high accuracy and efficiency, enabling active target detection, a horizontal detection range estimation method based on phased sound focusing technology is presented. The model of the phased emission sound field is derived, along with the theoretical estimation formula for the horizontal detection range, by combining the half-power beamwidth of the beam curve at the phased-emitter end with the ray propagation law of deep-sea acoustics. The corresponding relationships among each discrete phased angle, the horizontal distance, and the detection range of the focused beam boundary are detailed. The estimation formula for the horizontal detection range is then improved to account for the sea surface reflection effect, and angle optimization is applied to the transmitted beam curve to counteract the boundary error accumulation effect of the focused sound beam as the sound ray propagates. To address the issue of reduced scanning efficiency at large phased angles, the grating lobe-focused sound beam generated by phased emission array parameters is used to achieve angle scanning within the close deep-sea sound shadow zone, increasing the phased angle scanning efficiency. Finally, the deep-sea phased emission active target detection experiments were carried out, and the echo signal generated by the phased focused sound beam and received by the vertical receiving array was recorded. Numerical simulation and echo signal processing show that the high-efficiency angle scanning of the entire deep-sea sound shadow zone is achieved by the proposed estimation method.

A hybrid spatiotemporal model combining graph attention network and gated recurrent unit for regional composite air pollution prediction and collaborative control - Li Wang; Baicheng Hu; Yuan Zhao; Kunlin Song; Jianmin Ma; Hong Gao; Tao Huang; Xiaoxuan Mao (Sustainable Cities and Society, 2024)

Improving zinc reduction and removal from pellets of zinc-bearing dusts via vacuum microwave-assisted carbothermal reduction process - Wuju Zhang; Tao Dong; Deqing Zhu; Yin Jiang; Jian Pan; Zhengqi Guo; Siwei Li; Wenzhuo Ma (Process Safety and Environmental Protection, 2024)

New insights into anaerobic digestion of lignocellulosic wastes towards carbon neutrality: A review of current advancement and future prospects - Xuyihui Chen; Xinzheng Zhang; Chengde Sun; Yiming Chen; Zheming Xi; Guangyi Ma; Tao Zhang; Yalei Zhang; Xuefei Zhou; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2024)

Study on the treatment of rural sewage with microbial fuel cell-constructed wetlands enhanced by agricultural biomass - Yuting Ma; Yutong Li; Mengni Tao; Shiwei Cao; Zhaoqian Jing (Journal of Water Process Engineering, 2024)

Deciphering sustainability and carbon neutrality for effective treatment of rural wastewater: A review of development and perspectives of biofiltration process - Jingping Niu; Chengde Sun; Tao Chen; Hongbo Guo; Zheming Xi; Guangyi Ma; Tao Zhang; Xuefei Zhou; Yalei Zhang; Dapeng Li; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2024)

Diethylhexyl phthalate induces immune dysregulation and is an environmental immune disruptor - Dongli Linghu; Zhenru Zhu; Dongyan Zhang; Yongyi Luo; Jing Ma; Tao Li; Zhichao Sun; Zheng Xie; Jingyuan Sun; Chuanhui Cao (Journal of Hazardous Materials, 2024)

High-resolution full-coverage ozone (O3) estimates using a data-driven spatial random forest model in Beijing-Tianjin-Hebei region, China - Junyu Wang; Jian Qian; Jiayi Chen; Sheng Li; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Ying Deng; Jing Zeng; Chenglin Tao; et al. (Journal of Hazardous Materials, 2024)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Interpretable regional meteorological feature extraction enhances deep learning for extended 120-h PM2.5 forecasting - Xinyi Liu; Xueting Pu; Chengwei Lu; Han Zhang; Tao Li; Michael L. Grieneisen; Jucheng Li; Ning Ma; Chang Yan; Yu Zhan; Fumo Yang (Journal of Cleaner Production, 2024)

Biofiltration for low-carbon rural wastewater treatment: A review of advancements and opportunities towards carbon neutrality - Guangyi Ma; Zheming Xi; Yiheng Chen; Wenjie Xu; Chengde Sun; Wenjun Zhuang; Tao Zhang; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Environmental Chemical Engineering, 2024)

Joint block adjustment and variational optimization for global and local radiometric normalization toward multiple remote sensing image mosaicking - Dekun Lin; Huanfeng Shen; Xinghua Li; Chao Zeng; Tao Jiang; Yongming Ma; Mingjie Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Investigating how oxygen levels and particle size impact the thermodynamics of low temperature coal oxidation: A case study using weakly caking coal - Li-Feng Ren; Fan Tao; Teng-Fei Weng; Qing-Wei Li; Xin Yu; Xiao-Wei Zhai; Teng Ma (Fuel, 2024)

Insights into carbon-neutral treatment of rural wastewater by constructed wetlands: A review of current development and future direction - Feifei Jiao; Xinzheng Zhang; Tao Zhang; Yong Hu; Rui Lu; Guangyi Ma; Tao Chen; Hongbo Guo; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Curcumin protects porcine granulosa cells and mouse ovary against reproductive toxicity of aflatoxin B1 via PI3K/AKT signaling pathway - Sihong Li; Rui Li; Jun Jiang; Lu Liu; Xiang Ma; Tao Wang; Lili Zhao; Weifen Li; Dong Niu (Environmental Pollution, 2024)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

Effects of iron-carbon on nitrogen metabolism of floc and aerobic granular sludge - Kuan Pan; Zhou Qian; Tao Guo; Yunxin Chen; Fei Li; Mengting Ding; Xiao Ma; Jun Li (Bioresource Technology, 2024)

Creatine Kinase-MM/Proto-oncogene Tyrosine-Protein Kinase Receptor as a Sensitive Indicator for Duchenne Muscular Dystrophy Carriers - Zhilei Zhang; Dongyang Hong; Dingyuan Ma; Peiying Yang; Jingjing Zhang; Xin Wang; Yan Wang; Lulu Meng; Yanyun Wang; Yahong Li; Yun Sun; Tao Jiang; et al. (Molecular Neurobiology, 2024)

An optimized method for analysis of existing tunnels undercrossed by new tunnels in rich-water strata - Bo Liu; Qian Han; Yanhui Han; Tao Li; Shaojun Ma; Bing Zhang (Transportation Geotechnics, 2024)

Biogeochemical cycles of iron: Processes, mechanisms, and environmental implications - Huan Liu; Tao Liu; Shengnan Chen; Xiaoyan Liu; Nan Li; Tinglin Huang; Ben Ma; Xiang Liu; Sixuan Pan; Haihan Zhang (Science of The Total Environment, 2024)

Characteristics of surface microlayer film under different freshwater environments: Physical, chemical, and biological properties - Yuankun Yang; Tian Ma; Shu Chen; Han Song; Lunzhen Li; Yu He; Tao Song; Qiuhong Zhou; Weiguo Tu (Process Safety and Environmental Protection, 2024)

Vortex-induced vibration characteristic and trigger mechanism of semi-closed streamlined box girder trans-sea bridges - Qingsong Duan; Cunming Ma; Tao Zhang; Zhiguo Li (Ocean Engineering, 2024)

Long-term rice-crayfish farming alters soil dissolved organic carbon quality and biodegradability by regulating microbial metabolism and iron oxidation - Wanyang Zhang; Tianqiao Ma; Jianwei Lu; Jun Zhu; Tao Ren; Rihuan Cong; Zhifeng Lu; Yangyang Zhang; Xiaokun Li (Journal of Environmental Management, 2024)

The regulation mechanism of ethephon-mediated delaying of postharvest physiological deterioration in cassava storage roots based on quantitative acetylproteomes analysis - Yan Yan; Meiying Li; Zehong Ding; Jinghao Yang; Zhengnan Xie; Xiaoxue Ye; Weiwei Tie; Xiangru Tao; Ganlu Chen; Kaisen Huo; Jianxiang Ma; Jianqiu Ye; et al. (Food Chemistry, 2024)

Metabolomics study of dietary Pleurotus eryngii β-type glycosidic polysaccharide on colitis induced by dextran sodium sulfate in mice – Exploration for the potential metabolic indicators in urine and serum - Gaoxing Ma; Qi Tao; Xinyi Li; Yanhui Han; Hengjun Du; Qiuhui Hu; Hang Xiao (Food Chemistry, 2024)

Caprock sealing integrity and key indicators of CO2 geological storage considering the effect of hydraulic-mechanical coupling: X field in the Bohai Bay Basin, China - Bowen Chen; Qi Li; Yongsheng Tan; Yao Zhang; Tao Yu; Jiyuan Ma; Yiyan Zhong; Xiaying Li (Engineering Geology, 2024)

Experimental investigation on product and temperature distribution in a continuous flow packed-bed reactor for dodecahydro-N-ethylcarbazole dehydrogenation - Jingwen Xue; Pengzhao Li; Pengfei Yu; Jinhao Yi; Tao Ma; Hu Liu; Defu Che (Chemical Engineering Journal, 2024)

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Ignored microbial-induced taste and odor in drinking water reservoirs: Novel insight into actinobacterial community structure, assembly, and odor-producing potential - Haihan Zhang; Tongchao Ni; Xiang Liu; Ben Ma; Tinglin Huang; Daijuan Zhao; Haiyun Li; Kaige Chen; Tao Liu (Water Research, 2024)

Joint effects of air pollution and genetic susceptibility on incident primary open-angle glaucoma - Hao-Neng Huang; Pan-Pan Zhu; Zhou Yang; Yi-Ming Tao; Xiaofeng Ma; Hai-Bing Yu; Li Li; Chun-Quan Ou (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improved mapping of heavy metals in agricultural soils using machine learning augmented with spatial regionalization indices - Xudong Ma; Dong-Xing Guan; Chaosheng Zhang; Tao Yu; Cheng Li; Zhiliang Wu; Bo Li; Wenda Geng; Tiansheng Wu; Zhongfang Yang (Journal of Hazardous Materials, 2024)

Manufacturing of Fe/C micro-electrolysis materials with the pyrite cinder towards the degradation of high-concentration organic wastewater - Tao Dong; Zhengqi Guo; Deqing Zhu; Jian Pan; Wenzhuo Ma; Siwei Li; Yue Shi (Journal of Environmental Chemical Engineering, 2024)

Three-dimensional mass transfer modeling and phenolic chemistry exploration for ultrasound-assisted and microwave drying of goji berry - Rui Zhu; Xiaoxuan Ma; Dandan Li; Yongbin Han; Sivakumar Manickam; Yang Jiao; Erico Marlon Moraes Flores; Yang Tao (Food Research International, 2024)

Milk fat globule membrane (MFGM) phospholipid - Whey protein interaction characterization and its effect on physicochemical, interfacial properties and evaluation of in vitro digestion of emulsions - Inspired by the MFGM - Yanjie Zhao; Lu Liu; Qian Ma; Yuxin Wang; Xiaodong Li; Xiuxiu Zhang; Tao Zhou; Shuo Chen; Kouadio Jean Eric Parfait Kouame (Food Hydrocolloids, 2024)

Microwave-edge-thermal effect induced growth of coral-like self-supporting CoFe2O4/NF electrocatalysts for efficient water splitting at high-current–density - Fengqi Han; Tao Li; Shupei Lv; Lu Chen; Bo Ma; Shasha Yi; Chunyong He; Yubin Ke; Deliang Chen (Chemical Engineering Journal, 2024)

Accurate point-of-care lotus biomimetic microfluidic urine testing platform for patients with chronic kidney disease - Chen Yang; Guoqing He; Yantong Liu; Yihan Ma; Tao Jiang; Xiaoqi Gao; Shukun Zhao; Lonfei Chen; Xuan Zhang; Kezhen Yi; Shuchen Zhang; Lijun Li; et al. (Chemical Engineering Journal, 2024)

Thermodynamic Characteristics and Kinetic Mechanism of Bituminous Coal in Low-Oxygen Environments - LiFeng Ren; Fan Tao; TengFei Weng; QingWei Li; Xin Yu; XiaoWei Zhai; Teng Ma (Natural Resources Research, 2024)

Brain state and dynamic transition patterns of motor imagery revealed by the bayes hidden markov model - Yunhong Liu; Shiqi Yu; Jia Li; Jiwang Ma; Fei Wang; Shan Sun; Dezhong Yao; Peng Xu; Tao Zhang (Cognitive Neurodynamics, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

Association between Mixed Heavy Metal Exposure and Arterial Stiffness, with Alkaline Phosphatase Identified as a Mediator - Pingan Li; Jianhua Ma; Yue Jiang; Xinghua Yang; Yanxia Luo; Lixin Tao; Xiuhua Guo; Bo Gao (Biological Trace Element Research, 2024)

Improved classification of soil As contamination at continental scale: Resolving class imbalances using machine learning approach - Tao Hu; Kechao Li; Chundi Ma; Nana Zhou; Qiusong Chen; Chongchong Qi (Chemosphere, 2024)

Deep-sea mining of massive sulfides: Balancing impacts on biodiversity and ecosystem, technological challenges and law of the sea - Astrid Holzheid; Hongbo Zhao; Tony Cabus; Lei Fan; Thomas Kuhn; Linlin Sun; Chunhui Tao; Matthias Haeckel; Duong Hoang; Norman Kelly; Terue Kihara; Bing Li; et al. (Marine Policy, 2024)

Unraveling the role of Mn(V)/Mn(III) in the enhanced permanganate oxidation under Vis-LED radiation - Jiamin Mai; Ge Zeng; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Xiangyang Hou; Minchao Liu; Jun Ma; Tao Yang (Science of The Total Environment, 2024)

Harnessing Lecanicillium attenuatum: A novel strategy for combatting Nilaparvata lugens in rice fields - Xin Zhang; Kui Li; Pei Wang; Mingyong Ma; Tao Tang; Wei Fu; Hongtao Wu; Yan Sun; Sizhen Liu; Dehua Liu; Xinqiu Tan (Pesticide Biochemistry and Physiology, 2024)

Stable isotope revealed hydroclimate transition and topography growth in the Northern Tibetan Plateau at ∼ 10 Ma - Tao Zhang; Wenxia Han; Qian Tian; Li Mai; Ziqiang Mao; Xinting Yan; Yanlong Ma; Xiaomin Fang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Characterization of start-up, long-term performance and resistance to ammonia inhibition during anaerobic treatment of high-strength pharmaceutical wastewater by up-flow anaerobic blanket reactor integrated with partial nitritation-anammox - Xinzheng Zhang; Guangyi Ma; Chengde Sun; Hongbo Guo; Zheming Xi; Tao Zhang; Yong Hu; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2024)

Mixotrophic aerobic denitrification facilitated by denitrifying bacterial-fungal communities assisted with iron in micro-polluted water: Performance, metabolic activity, functional genes abundance, and community co-occurrence - Ben Ma; Mengting Chu; Haihan Zhang; Kaige Chen; Fengrui Li; Xiang Liu; Dmitry B. Kosolapov; Wei Zhi; Zhongbing Chen; Jun Yang; Ye Deng; Raju Sekar; et al. (Journal of Hazardous Materials, 2024)

Insight into the influence mechanism of chloride ions towards in-situ electric-induced uranium incorporation into magnetite - Mi Li; Xin Ma; Xiao-yan Wu; Yi-long Hua; Xiao-wen Zhang; Qi Fang; Tao Cai (Journal of Cleaner Production, 2024)

Key indicators of caprock sealing assessment with consideration of faults in potential CO2 geological storage sites in Subei Basin, China - Bowen Chen; Qi Li; Yongsheng Tan; Yao Zhang; Tao Yu; Yiyan Zhong; Jiyuan Ma; Xiaochun Li (Gas Science and Engineering, 2024)

Group VIII metals effects on lignite pyrolysis and char gasification with Ca-based catalyst - Tao Qin; Na Li; Hang Ma; Guodong Wang; Xiaoguo Zhang; Youneng Feng; Wei Lu; Shenfu Yuan (Fuel, 2024)

Promotional mechanism of La-Mn-Fe modification on activated coke for NH3-SCR of NOx at low temperatures - Rui Li; Tao Yue; Yang Zheng; Guoliang Li; Jiajia Gao; Yali Tong; Jiaqing Wang; Mengying Ma; Wei Su (Fuel, 2024)

Mechanistic insights into the enhanced low-temperature activity of Cu-SSZ-13 by MnOx-CeO2 modification for standard SCR reaction and fast SCR reactions - Rui Li; Tao Yue; Yang Zheng; Guoliang Li; Jiajia Gao; Wenbo Zhang; Jiaqing Wang; Mengying Ma; Wei Su (Fuel, 2024)

Synthesis of spiroindoline derivatives and biphenyl compounds in green solvent via a “capture–release” mechanism using modified polyacrylonitrile fiber as a catalyst - Xiaoting Li; Yanfei Zhang; Jinxin Liu; Jian Cao; Ning Ma; Minli Tao; Wenqin Zhang (Chemical Engineering Journal, 2024)

Advanced bionic inverted coral solar evaporator: Enhancing sustainable water utilization with efficient and salt-resistant evaporation - Yangyaqi Mi; Yinlong Li; Yuetong Tao; Yangyang Chen; Jinbo Bai; Gang Wang; Lunjun Wang; Shenghua Ma; Beibei Wang (Chemical Engineering Journal, 2024)

Secular mantle wedge evolution due to variable slab fluid metasomatism: Evidence from Permian-Triassic mafic igneous rocks in the Paleo-Tethys tectonic regime - Ye-Dan Hu; Li-Qun Dai; Li-Tao Ma; Zi-Fu Zhao (Chemical Geology, 2024)

Maintaining real-time precise point positioning during outages of the corrections broadcast by BDS-3 global short-message communication - Zhuang Ma; Tao Geng; Zhiqiang Li; Xin Xie; Lingyue Cheng; Wenjian Liu (Advances in Space Research, 2024)

Sleep onset time as a mediator in the association between screen exposure and aging: a cross-sectional study - Senlin Lin; Meng Gao; Juzhao Zhang; Yuting Wu; Tao Yu; Yajun Peng; Yingnan Jia; Haidong Zou; Lina Lu; Deshang Li; Yingyan Ma (GeroScience, 2024)
Excessive screen exposure has become a significant health concern. This study investigates the impact of screen time on aging in middle-aged and elderly populations. Healthy working adults over 45 years old in Shanghai, China, underwent general and ocular examinations. Questionnaires collected demographics, medical history, and screen exposure details. Aging was assessed using the retinal age gap, defined as the difference between the retinal age predicted by deep learning algorithms based on fundus images and chronological age. Pathway analysis tested the mediation effect of sleep duration and onset time on the relationship between screen usage and retinal age gap. The retinal age gap increased with longer screen exposure, from 0.49 ± 3.51 years in the lowest tertile to 5.13 ± 4.96 years in the highest tertile (Jonckheere-Terpstra test, p < 0.001). Each additional hour of screen exposure accelerated the retinal age gap by 0.087 years (95% CI, 0.027, 0.148, p = 0.005) in the fully adjusted linear model. Sleep onset time mediated the impact of screen usage on the retinal age gap (indirect effect, β = 0.11; 95% CI 0.04–0.24). The impact of screen usage in a light-off environment on the retinal age gap was fully mediated by sleep onset time (indirect effect, β = 0.22; 95% CI 0.07–0.38), with the proportion being 100%. Our study identified a correlation between excessive screen time and a wider retinal age gap in middle-aged and elderly individuals, likely due to delayed sleep onset. To mitigate the adverse effects on the retina and aging, it is important to limit screen usage and avoid screens before bedtime.

Effects of Enterobacter cloacae insecticidal protein on the Duox-ROS system and midgut bacterial community and function of Galleria mellonella larvae - Tao Zhu; Yi Yang; Chao Hu; Liang Ma; Jiaqing Sheng; Ruiying Chang; Yanfei Liao; Lianzhe Wang; Yutao Zhu; Mei Zhao; Bingbing Li; Taotao Li; et al. (Toxicon, 2024)

Point cloud registration via sampling-based evolutionary multitasking - Hangqi Ding; Yue Wu; Maoguo Gong; Hao Li; Peiran Gong; Qiguang Miao; Wenping Ma; Yiping Duan; Xiaoming Tao (Swarm and Evolutionary Computation, 2024)

Evolution of the rare-metal mineralization system associated with collision-related pegmatites in the western Altyn Tagh Orogen, Tugeman, NW China - Yince Ma; Tao Hong; Qiang Ke; Hang Li; Wenkai Jin; Zhiquan Yang; Peng Zhang; Zhaoxia Liao; Kai Kang; Chen Li; Decheng Ma; Xing-Wang Xu (Journal of Asian Earth Sciences, 2024)

Suitable habitat evaluation and ecological security pattern optimization for the ecological restoration of Giant Panda habitat based on nonstationary factors and MCR model - Hui He; Xiangke Yu; Hui Yu; Zhigang Ma; Yong Luo; Tao Liu; Ziwei Rong; Jinhong Xu; Dianpeng Chen; Pengshang Li; Fuxin Yuan; Yongtao Zhao (Ecological Modelling, 2024)

Probabilistic assessment of 3D slope failures in spatially variable soils by cooperative stochastic material point method - Shui-Hua Jiang; Jian-Ping Li; Guo-Tao Ma; Mohammad Rezania (Computers and Geotechnics, 2024)

Catalytic oxidation of SO2 in O2-aerated aqueous Solution: superior catalytic capability of KOH/urea-treated biochars and catalytic mechanism - Liu Pi; Yan Shao; Tao Xu; Junru Ma; Yan Li; Xuhui Mao (Chemical Engineering Journal, 2024)

Thermal comfort prediction in multi-occupant spaces based on facial temperature and human attributes identification - Mianyang Yu; Ziyue Tang; Yanling Tao; Liyuan Ma; Zhilong Liu; Longkang Dai; Hua Zhou; Meng Liu; Ziqiao Li (Building and Environment, 2024)

Placenta-targeted Treatment Strategies for Preeclampsia and Fetal Growth Restriction: An Opportunity and Major Challenge - Jianjian Cui; Zejun Yang; Ruilin Ma; Wencong He; Hui Tao; Ya’nan Li; Yin Zhao (Stem Cell Reviews and Reports, 2024)
The placenta plays a crucial role in maintaining normal pregnancy. The failure of spiral artery remodeling (SAR) is a key factor leading to placental ischemia and poor perfusion which is strongly associated with obstetric diseases, including preeclampsia (PE) and fetal growth restriction (FGR). Existing interventions for PE and FGR are limited and termination of pregnancy is inevitable when the maternal or fetus condition deteriorates. Considering the safety of the mother and fetus, treatments that may penetrate the placental barrier and harm the fetus are not accepted. Developing targeted treatment strategies for these conditions is urgent and necessary. With the proven efficacy of targeted therapy in treating conditions such as endometrial cancer and trophoblastic tumors, research on placental dysfunction continues to deepen. This article reviews the studies on placenta-targeted treatment and drug delivery strategies, summarizes the characteristics proposes corresponding improvement measures in targeted treatment, provides solutions for existing problems, and makes suggestions for future studies. Graphical abstract

HDAC inhibitors as a potential therapy for chemotherapy-induced neuropathic pain - Chalton Manengu; Chun-Hao Zhu; Guo-Dong Zhang; Miao-Miao Tian; Xiao-Bing Lan; Li-Jun Tao; Lin Ma; Yue Liu; Jian-Qiang Yu; Ning Liu (Inflammopharmacology, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Assessment of the migration characteristics and source-oriented health risks of heavy metals in the soil and groundwater of a legacy contaminated by the chlor-alkali industry in central China - Wanqi Ma; Mingya Wang; Mingshi Wang; Lu Tao; Yuanhang Li; Shili Yang; Fan Zhang; Shaobo Sui; Luhao Jia (Environmental Geochemistry and Health, 2024)

A Novel TGF-β-Related Signature for Predicting Prognosis, Tumor Microenvironment, and Therapeutic Response in Colorectal Cancer - Baorui Tao; Chenhe Yi; Yue Ma; Yitong Li; Bo Zhang; Yan Geng; Zhenmei Chen; Xiaochen Ma; Jinhong Chen (Biochemical Genetics, 2024)

Genetic affinity of cave burial and Hmong-Mien populations in Guangxi inferred from ancient genomes - Jianxin Guo; Haifeng He; Guangmao Xie; Le Tao; Xi Mai; Kongyang Zhu; Qiusheng Qin; Xiaomin Yang; Ying Xie; Rui Wang; Hao Ma; Jing Zhao; et al. (Archaeological and Anthropological Sciences, 2024)

Connection patterns and resilience simulation of innovation network in the context of technology transfer: A case study of strategic emerging industries in the Guangdong-Hong Kong-Macao Greater Bay Area - Tao Ma; Wuyang Hong; Zhan Cao; Li Zhang; Xiaochun Yang (Sustainable Cities and Society, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Analysis of the causes and safety countermeasures of coal mine accidents: A case study of coal mine accidents in China from 2018 to 2022 - Shuicheng Tian; Yajuan Wang; Hongxia LI; Tao Ma; Junrui Mao; Lei Ma (Process Safety and Environmental Protection, 2024)

Experimental and theoretical investigations into overpressure during confined space explosions of methane-hydrogen mixture - Shuhong Li; Zihao Xiu; Ranran Li; Jianbo Ma; Kaiyuan Zhao; Zhenyi Liu; Pengliang Li; Mingzhi Li; Tao Fan (Process Safety and Environmental Protection, 2024)

Climatic and anthropogenic forcing of vegetation change at different altitudes on the northeastern Tibetan Plateau over the past millennium - Dou Chen; Youmo Li; Shilong Guo; Tao Wang; Lin Chen; Lanlan Hu; Jinghua Huang; Lili Pan; Xuyi Ma; Duo Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of warming at embryonic and larval stages on tadpole fitness in high-altitude Rana kukunoris - Zhiyi Niu; Peng Pu; Tao Zhang; Lun Jia; Xinying Li; Huihui Wang; Miaojun Ma; Xiaolong Tang; Qiang Chen (Journal of Thermal Biology, 2024)

Coupling sedimentary records of anthropogenic metal(loid)s in urban waterscape parks with the “Coal to Gas” transition - Shen Yu; Tao Ma; Linlin Zhang; Qi Li; Min Zhou (Journal of Hazardous Materials, 2024)

Hydrophobic nanosheet silicalite-1 zeolite for iodine and methyl iodide capture - Qian Zhao; Xin Li; Guangyuan Chen; Zeru Wang; Chuan Tan; Cheng Liu; Hao Zou; Jing Ma; Lin Zhu; Tao Duan (Journal of Hazardous Materials, 2024)

Robust Er2O3/UiO-66-NH2 core–shell nanohybrid for efficient CO2 photoreduction via fast interfacial charge-transfer - Chong Chen; Pengfei Zhao; Qiuhao Li; Yukun Zhang; Tao Sun; Changjiang Hu; Jun Ma (Fuel, 2024)

Metabolites and metabolic pathway analysis of sulfadimidine in carp (Cyprinus carpio) based on UHPLC-Q-orbitrap HRMS - Shuwen Wang; Lihong Xing; Xiaojie Sun; Zhaoxin Li; Tao Ding; Jiyao Wang; Jixing Peng; Haijian Ma; Ting Lin; Qingli Yang (Environmental Research, 2024)

Freeze-sonication delamination method of high crystalline-quality MXene with high yield - Haohang Song; Yusheng Ma; Qian Yao; Chao Liu; Xuesong Li; Xutang Tao (Chemical Engineering Journal, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Combining canopy spectral reflectance and RGB images to estimate leaf chlorophyll content and grain yield in rice - Zhonglin Wang; Xianming Tan; Yangming Ma; Tao Liu; Limei He; Feng Yang; Chuanhai Shu; Leilei Li; Hao Fu; Biao Li; Yongjian Sun; Zhiyuan Yang; et al. (Computers and Electronics in Agriculture, 2024)

Photo-assisted natural chalcopyrite activated peracetic acid for efficient micropollutant degradation - Linqian An; Xiujuan Kong; Maoju Jiang; Wenqi Li; Qixiao Lv; Xiangyang Hou; Chenlong Liu; Peng Su; Jun Ma; Tao Yang (Water Research, 2024)

Anemhupehins D F, sterols and chromone derivative from Anemone hupehensis and their anti-inflammatory activity - Jin-Lei Ning; Ning Qin; Hong-Fei Li; Xi-Yue Ma; Fei Zhang; Tao Feng; Juan He (Phytochemistry Letters, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Exploring the relationships among commute, work and life satisfaction: A multiscale analysis in Beijing - Hanyan Li; Jing Ma; Sui Tao (Journal of Transport Geography, 2024)

Role of microalgae-bacterial consortium in wastewater treatment: A review - Lixin Li; Wei Chai; Caiyu Sun; Linlin Huang; Tao Sheng; Zhiwei Song; Fang Ma (Journal of Environmental Management, 2024)

Multiplex-PCR method application to identify duck blood and its adulterated varieties - Lijun Gao; Bingyang Du; Qiuhe Ma; Yuhe Ma; Wenying Yu; Tao Li; Yue Liu; Guangxin Yuan (Food Chemistry, 2024)

Landslides triggered by the 2022 Ms. 6.8 Luding strike-slip earthquake: An update - Xiaoyi Shao; Siyuan Ma; Chong Xu; Chenchen Xie; Tao Li; Yuandong Huang; Yu Huang; Zikang Xiao (Engineering Geology, 2024)

A newly early warning model for anaerobic digestion systems: Based on an improved sparrow search algorithm combined with least square support vector machine - Yushu Chen; Zetao Huang; Chongjian Ma; Zuhao Li; Zhige Zhang; Tao Tan; Yong Chen (Chemical Engineering Journal, 2024)

Genetic diversity analysis of macadamia germplasm in China based on whole-genome resequencing - Zhiqiang Li; Chao Wu; Jing Ma; Jianjian Geng; Liang Tao; Xiyong He; Lidan Gong (Tree Genetics & Genomes, 2024)

Promoter replication of grape MYB transcription factor is associated with a new red flesh phenotype - Hui Li; Yaxin Yang; Wen Zhang; Huan Zheng; Xianbin Xu; Haoran Li; Chenxu Sun; Haipeng Hu; Wanli Zhao; Ruiyang Ma; Jianmin Tao (Plant Cell Reports, 2024)

Multiphase evolution of a Li-pegmatite field from the Tashisayi area, Altyn Tagh, NW China: insights from a petrological, geochemical, and geochronological study - Yin-Ce Ma; Xing-Wang Xu; Tao Hong; Wen-Kai Jin; Hang Li; Zhi-Quan Yang; Shan-Ke Liu; Kai Kang; Xue-Hai Wang; Lei Niu (Mineralium Deposita, 2024)

Comprehensively Assessing PM2.5 Exposure Across Mainland China with Estimated Concentrations Considering Spatial Aggregation - Xuelin Li; Jingfei Huang; Yi Zhang; Siwei Zhai; Xinyue Tian; Sheng Li; Wei Wang; Tao Zhang; Fei Yin; Yue Ma (International Journal of Environmental Research, 2024)

Epidemiology, pathogenesis, immune evasion mechanism and vaccine development of porcine Deltacoronavirus - Xueting Shan; Rui Li; Xiang Ma; Guoqiang Qiu; Yi Xiang; Xiaojun Zhang; De Wu; Lu Wang; Jianhong Zhang; Tao Wang; Weifen Li; Yun Xiang; et al. (Functional & Integrative Genomics, 2024)

The effect of elevation, latitude, and plant richness on robustness of pollination networks at a global scale - Xiang-Ping Wang; Jeff Ollerton; Kit S. Prendergast; Jin-Chao Cai; Ma-Yin Tong; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Arthropod-Plant Interactions, 2024)

Multiplexed colorimetry collaborated with smartphone-based image analysis for simultaneous and fast visualization of dyes in both environmental and food samples - Shuangshou Wang; Yuwen Ding; Lu Zhang; Wenhao Yang; Tianyou Geng; Tong Li; Tingxuan Yan; Yang Chen; Tao Ma; Yu Wu; Jin Ye; Daojin Li (Journal of Hazardous Materials, 2024)

Role of bipyridyl in enhancing ferrate oxidation toward micropollutants - Juan Li; Jiachun Cao; Maoju Jiang; Linqian An; Ge Zeng; Jiamin Mai; Peng Su; Binghua Jing; Mingbao Feng; Zhimin Ao; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Determination of high-risk factors and related spatially influencing variables of heavy metals in groundwater - Huanhuan Shi; Yao Du; Yueping Li; Yamin Deng; Yanqiu Tao; Teng Ma (Journal of Environmental Management, 2024)

Role of turbulence in ozone chemistry: Segregation effect implicated from multiscale modeling over Hong Kong - Yuting Wang; Yong-Feng Ma; Cathy W.Y. Li; Tao Wang; Guy Brasseur (Atmospheric Environment, 2024)

Estimating the mutually adjusted health effects of short- and long-term exposure to PM2.5 on respiratory mortality in a population-based study - Yi Zhang; Jing Zeng; Xinyue Tian; Siwei Zhai; Jingfei Huang; Xuelin Li; Sheng Li; Junyu Wang; Menghan Yao; Qianqian Du; Wei Wang; Tao Zhang; et al. (Atmospheric Pollution Research, 2024)

A combination of QTL mapping and genome-wide association study revealed the key gene for husk number in maize - Zhenjuan Liang; Na Xi; Tao Liu; Minglin Li; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Guangtang Pan; Langlang Ma; Yaou Shen (Theoretical and Applied Genetics, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Geochemical behavior of rare earth elements in agricultural soils along the Syr Darya River within the Aral Sea Basin - Yizhen Li; Galymzhan Saparov; Tao Zeng; Jilili Abuduwaili; Long Ma (Environmental Monitoring and Assessment, 2024)

The effect of canagliflozin on gut microbiota and metabolites in type 2 diabetic mice - Li Zeng; Jideng Ma; Tiantian Wei; Hao Wang; Guitao Yang; Chongxiang Han; Tao Zhu; Haoming Tian; Min Zhang (Genes & Genomics, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Association between exposure to outdoor artificial light at night during pregnancy and glucose homeostasis: A prospective cohort study - Lei Zhang; Haixia Wang; Ping Zu; Xinyu Li; Shuangshuang Ma; Yuanyuan Zhu; Tianqin Xie; Fangbiao Tao; Dao-min Zhu; Peng Zhu (Environmental Research, 2024)

A robust Zr(IV)-based metal-organic framework featuring high-density free carboxylic groups for efficient uranium recovery - Bin Wang; Chunyu Bao; Jiahui Xu; Yunnan Tao; Long Chen; Duo Zhang; Kui Tan; Shuao Wang; Jian-Rong Li; Shengqian Ma (Chemical Engineering Journal, 2024)

Structure-induced interfacial activation convoying the CO-relayed conversion of CO2 to dimethyl carbonate - Shu-Guo Han; Shenghua Zhou; Xiaofang Li; Jianqiang Zhao; Wen-Bo Wei; Lirong Zheng; Dong-Dong Ma; Xin-Tao Wu; Qi-Long Zhu (Chemical Engineering Journal, 2024)

Highly efficient hydrogenolysis of lignin into monophenol over an atomically dispersed platinum catalyst - Meifang Cao; Yuqiao Ma; Tao Ruan; Lifeng Li; Bo Chen; Xueqing Qiu; Di Fan; Xinping Ouyang (Chemical Engineering Journal, 2024)

Neogene integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Tao Deng; Xiaomin Fang; Qiang Li; Shiqi Wang; Feixiang Wu; Sukuan Hou; Jiao Ma; Qigao Jiangzuo; Danhui Sun; Yan Zheng; Qinqin Shi; Boyang Sun; et al. (Science China Earth Sciences, 2024)

TET1 is a Diagnostic and Prognostic Biomarker Associated with Immune Infiltration in Papillary Thyroid Cancer - Yong-xun Zhao; Li-bin Ma; Ze Yang; Tao-hua Zhang; Yong Wang; Cheng Xiang (Biochemical Genetics, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Influence of lithospheric thickness distribution on oil and gas basins, China seas and adjacent areas - Jing Ma; Wanyin Wang; Hermann Zeyen; Yimi Zhang; Zhongsheng Li; Tao He; Dingding Wang (Acta Oceanologica Sinica, 2024)

Response of erosion rate to hydrodynamic parameters in sheet and rill erosion process on saturated soil slopes - Dandan Li; Xiaoyan Chen; Wenhao Tan; Tingting Tao; Liwen Ma; Lingyong Kong; Pingzong Zhu (Soil and Tillage Research, 2024)

Temporal patterns and driving factors of sediment carbon, nitrogen, and phosphorus stoichiometry in a eutrophication plateau lake - Fang Tang; Jianhong Li; Xiaohua Ma; Yunmei Li; Hao Yang; Changchun Huang; Tao Huang (Science of The Total Environment, 2024)

Inferring the demographic history of Hexi Corridor over the past two millennia from ancient genomes - Jianxue Xiong; Rui Wang; Guoke Chen; Yishi Yang; Panxin Du; Hailiang Meng; Minmin Ma; Edward Allen; Le Tao; Hui Wang; Li Jin; Chuan-Chao Wang; et al. (Science Bulletin, 2024)

Halogenated aliphatic and phenolic disinfection byproducts in chlorinated and chloraminated dairy wastewater: Occurrence and ecological risk evaluation - You-Wei Jiang; Gui-Jing Wang; Shuang Zang; Yue Qiao; Hong-Fei Tao; Qiao Li; Han Zhang; Xian-Shi Wang; Jun Ma (Journal of Hazardous Materials, 2024)

Promoted catalytic performance of Ag-Mn bimetal catalysts synthesized through reduction route - Wenkai Hu; Tao Guo; Kaiyao Ma; Xu Li; Wangting Luo; Mingzhi Wu; Hao Guo; Yaxin Zhang; Wenfeng Shangguan (Journal of Environmental Sciences, 2024)

Generation of •OH and intermediate manganese species for the efficient removal of micropollutants via photocatalysis of permanganate by indium oxide - Juan Li; Maoju Jiang; Peng Su; Qixiao Lv; Linqian An; Ge Zeng; Xiangyang Hou; Wenqi Li; Chunzhao Chen; Jun Ma; Tao Yang (Chemical Engineering Journal, 2024)

New perspectives on organic carbon storage in lake sediments based on classified mineralization - Jiang Quanliang; Ma Xiaohua; Li Zhichun; Li Shuaidong; Huang Changchun; Huang Tao; Xue Bin; Yang Hao (CATENA, 2024)

Response of soil aggregation and associated organic carbon to organic amendment and its controls: A global meta-analysis - Shihao Ma; Yudong Cao; Jianwei Lu; Tao Ren; Rihuan Cong; Zhifeng Lu; Jun Zhu; Xiaokun Li (CATENA, 2024)

Analysis of actual evapotranspiration changes in China based on multi-source data and assessment of the contribution of driving factors using an extended Budyko framework - Tao Su; Shuting Wang; Siyuan Sun; Taichen Feng; Bicheng Huang; Qianrong Ma; Shuping Li; Guolin Feng (Theoretical and Applied Climatology, 2024)

Heterogeneous metal sources for mintage in the early Han empire, second century BCE: archaeometallurgical study of the Banliang coins from the Guanghuacun cemetery, Chengdu, Southwest China - Ding Ma; Ning Wang; Pei Li; Tao Yang; Jun Yang; Ruizhe Wang; Wugan Luo (Archaeological and Anthropological Sciences, 2024)

Morpho-physio-biochemical, molecular, and phytoremedial responses of plants to red, blue, and green light: a review - Muzammal Rehman; Jiao Pan; Samavia Mubeen; Wenyue Ma; Dengjie Luo; Shan Cao; Wajid Saeed; Gang Jin; Ru Li; Tao Chen; Peng Chen (Environmental Science and Pollution Research, 2024)

Fluoride promotes the secretion of inflammatory factors in microglia through NLRP3/Caspase-1/GSDMD pathway - Qiuyi Zhang; Tao Li; Ruili Shi; Ruifang Qi; Xiaoqiong Hao; Baohui Ma (Environmental Science and Pollution Research, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Is the application of organic fertilizers becoming an undeniable source of microplastics and resistance genes in agricultural systems? - Tianhao Li; Shiyu Tao; Mengjie Ma; Shiwei Liu; Maocai Shen; Huijuan Zhang (Science of The Total Environment, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Towards carbon-neutral biotechnologies for rural wastewater: A review of current treatment processes and future perspectives - Xinzheng Zhang; Guangyi Ma; Tao Chen; Churen Yan; Yiheng Chen; Qinye Wang; Xinyu Peng; Wenjie Xu; Tianwei Hao; Tao Zhang; Rui Lu; Dapeng Li; et al. (Journal of Water Process Engineering, 2024)

Understanding the effects of A-site Ag-doping on LaCoO3 perovskite for NO oxidation: Structural and magnetic properties - Ran Ao; Tao Pu; Liping Ma; Quxiu Dai; Jie Yang; Wengang Li; Longgui Xie; Zhiying Guo (Journal of Environmental Management, 2024)

Performance of aerobic denitrifying fungal community for promoting nitrogen reduction and its application in drinking water reservoirs - Tao Liu; Ziying Zhao; Haiyun Li; Mukesh Kumar Awasthi; Dmitry B. Kosolapov; Tongchao Ni; Ben Ma; Xiaoyan Liu; Xiang Liu; Wei Zhi; Haihan Zhang (Journal of Environmental Management, 2024)

Biomass ash chemistry in oxygen carrier aided combustion: Interaction between potassium and red mud - Yu Yang; Yali Shao; Shiwei Ma; Ping Li; Tao Song (Fuel, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Photo-thermochromic W18O49/hydrogel hybrid smart windows for graded and dual-band sunlight control - Jiahui Tao; Shouqin Tian; Bin Li; Tingfeng Ma; Longxiao Zhou; Xiujian Zhao (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Overexpression of ZmSUS1 increased drought resistance of maize (Zea mays L.) by regulating sucrose metabolism and soluble sugar content - Ning Xiao; Haizhen Ma; Wanxia Wang; Zengkun Sun; Panpan Li; Tao Xia (Planta, 2024)

Optimization analysis of thermal–hydraulic features of the 2.5 MW LBE spallation target of CiADS - Weiping Deng; Tao Wan; Weifeng Yang; Yongqin Ju; Fei Ma; Chengwen Qiang; Long Li; Fei Wang; Xueying Zhang (Annals of Nuclear Energy, 2024)

Novel dual-responsive hydrogel composed of polyacrylamide/Fe-MOF/zinc finger peptide for construction of electrochemical sensing platform - Youyu Li; Jiejie Feng; Tao Yao; Hongliang Han; Zhanfang Ma; Haijun Yang (Analytica Chimica Acta, 2024)

Environmental selenium and human longevity: An ecogeochemical perspective - Bo Li; Xu Liu; Tao Yu; Kun Lin; Xudong Ma; Cheng Li; Zhongfang Yang; Qifeng Tang; Guodong Zheng; Jianxun Qin; Ying Wang (Chemosphere, 2024)

A Real-World Study of Patient and Physician Satisfaction With AbobotulinumtoxinA Treatment of Glabellar Lines in Chinese Patients - Cecilia Persson; Jianmei Huang; Zhongrong Jiang; Li Ma; Jingjing Zhao; Zhiqiang Xue; Shuxian Zhang; Yuan Chen; Weiming Song; Lin Tao; Qingyang Liu; Inna Prygova (Toxicon, 2024)

Enhancing urban real-time PM2.5 monitoring in street canyons by machine learning and computer vision technology - Zhiguang Fan; Yuan Zhao; Baicheng Hu; Li Wang; Yuxuan Guo; Zhiyuan Tang; Junwen Tang; Jianmin Ma; Hong Gao; Tao Huang; Xiaoxuan Mao (Sustainable Cities and Society, 2024)

Podophyllotoxin-mediated neurotoxicity via the microbiota-gut-brain axis in SD rats based on the toxicological evidence chain (TEC) concept - Jiajia Duan; Jiaxing Sun; Tao Jiang; Xiao Ma; Xuejiao Li; Yuming Wang; Fangfang Zhang; Chuanxin Liu (Science of The Total Environment, 2024)

Characteristics of quartz grains in the middle and lower reaches of the Hutubi River, NW China, and its paleo-environmental significance - Dianjia Tan; Yunqiang Ma; Zhizhong Li; Jianhui Jin; Rui Liu; Xiaojun Zou; Tonglian Tao (Sedimentary Geology, 2024)

Using a novel strategy to identify the clustered regions of associations between short-term exposure to temperature and mortality and evaluate the inequality of heat- and cold-attributable burdens: A case study in the Sichuan Basin, China - Wei Wang; Jing Zeng; Xuelin Li; Fang Liao; Tao Zhang; Fei Yin; Ying Deng; Yue Ma (Journal of Environmental Management, 2024)

Numerical analysis of the abiotic formation and distribution of the “iron curtain” in subterranean estuaries - Tao Wang; Chenming Zhang; Ye Ma; Harald Hofmann; Congrui Li; Zicheng Zhao (Environmental Modelling & Software, 2024)

Rapid oxidation and deep As(III) purification from water using gelatin-supported iron-based metal-organic framework aerogel coupled with H2O2: Preparation, performance and mechanism - Guiyuan Cai; Yu Tian; Lipin Li; Jun Zhang; Wei Zuo; Qinyu Wang; Tao Liu; Lina Ma; Yifeng Zhang (Chemical Engineering Journal, 2024)

Mass transfer study on noncovalent adsorption and desorption of soluble phenolics by plant cell wall materials for green purification - Xiaoxuan Ma; Rui Zhu; Jue Li; Sivakumar Manickam; Pau Loke Show; Dandan Li; Yongbin Han; Erico Marlon Moraes Flores; Yang Tao (Chemical Engineering Journal, 2024)

RLP system: A single-tube two-step approach with dual amplification cascades for rapid identification of EGFR T790M - Tao Huang; Yanxi Han; Yuqing Chen; Zhenli Diao; Yu Ma; Lei Feng; Duo Wang; Rui Zhang; Jinming Li (Analytica Chimica Acta, 2024)

Assessing the short-term effects of PM2.5 and O3 on cardiovascular mortality using high-resolution exposure: a time-stratified case cross-over study in Southwestern China - Xinyue Tian; Jing Zeng; Xuelin Li; Sheng Li; Tao Zhang; Ying Deng; Fei Yin; Yue Ma (Environmental Science and Pollution Research, 2023)

Spatially varying relationships of soil Se concentration and rice Se concentration in Guangxi, China: A geographically weighted regression approach - Bo Li; Xu Liu; Chaosheng Zhang; Tao Yu; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Lei Wang; Kun Lin; Xudong Ma; Xuezhen Li; Husheng Zhang; et al. (Chemosphere, 2023)

Constructed electron-dense Mn sites in nitrogen-doped Mn3O4 for efficient catalytic ozonation of pyrazines: Degradation and odor elimination - Yinning He; Jiayi Li; Jingyu Tang; Haijun Cheng; Tao Zeng; Zhiqiao He; Da Wang; Lizhang Wang; Shuang Song; Jun Ma (Water Research, 2023)

A coarse- and fine-grained niching-based differential evolution for multimodal optimization problems and its application in multirobot task allocation - Tao Ma; Hong Zhao; Xiangqian Li; Fang Yang; Chun Sheng Liu; Jing Liu (Swarm and Evolutionary Computation, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

Strategies for fertilizer management to achieve higher yields and environmental and fertilizer benefits of rice production in China - Zongkui Chen; Xinrui Li; Tao Liu; Hao Fu; Xiaojuan Yuan; Qingyue Cheng; Qin Liao; Yue Zhang; Weitao Li; Yongjian Sun; Zhiyuan Yang; Jun Ma; et al. (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Study of the interaction mechanism between theaflavin and Zein - Tingting Yang; Guanhua Tao; Li Li; Qingwen Ma (Journal of Food Engineering, 2023)

Multi-omics techniques to compare the potential of raw and processed licorice as food supplements for ameliorating chronic fatigue syndrome - Wenxin Xia; Heming Zhang; Mengxin Tao; Hao Zhou; Jiahua Ma; Tingting Li; Xiaofen Huang; Xueyan Fu (Food Bioscience, 2023)

A review of recent techniques in performance augmentation and evaluation metrics of Trombe walls - Wenbo Gu; Gaochao Li; Arepati Xiermaimaiti; Tao Ma (Energy and Buildings, 2023)

Effects of polyols with different hydroxyl numbers on the structure and properties of starch straws - Chenyu Ma; Haiteng Tao; Congping Tan; Shijun Gao; Zehua Wu; Li Guo; Bo Cui; Fang Yuan; Feixue Zou; Pengfei Liu; Lu Lu (Carbohydrate Polymers, 2023)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Recent advances in tea seeds (Camellia Sinensis (L.) O. Kuntze): Active ingredients, health effects, and potential applications - Su Zhou; Zhiying Li; Haizhao Song; Hao Hu; Shicheng Ma; Yike Tao; Zhilong Hao; Xinyu Feng; Yani Pan; Shuying Gong; Fangyuan Fan; Ping Chen; et al. (Trends in Food Science & Technology, 2023)

Effect of depositional evolution on phosphorus enrichment in aquifer sediments of alluvial-lacustrine plain - Meihui Liu; Yao Du; Yamin Deng; Yueping Li; Yanqiu Tao; Yiqun Gan; Teng Ma (Science of The Total Environment, 2023)

Prediction of cadmium contents in rice grains from Quaternary sediment-distributed farmland using field investigations and machine learning - Xudong Ma; Tao Yu; Dong-Xing Guan; Cheng Li; Bo Li; Xu Liu; Kun Lin; Xuezhen Li; Lei Wang; Zhongfang Yang (Science of The Total Environment, 2023)

Combined health effects of PM2.5 components on respiratory mortality in short-term exposure using BKMR: A case study in Sichuan, China - Siwei Zhai; Jing Zeng; Yi Zhang; Jingfei Huang; Xuelin Li; Wei Wang; Tao Zhang; Ying Deng; Fei Yin; Yue Ma (Science of The Total Environment, 2023)

Numerical study of submerged body tail linearization in a strongly stratified fluid on the characteristics of generated internal waves - Li Zou; Tao Zhao; Xinyu Ma; Xueyu Wang; Yelin Gao (Ocean Engineering, 2023)

Revealing continuous hydrocarbon generation and shale oil accumulation of saline lacustrine source rocks by sequential extraction - Wenwen Li; Jian Cao; Wenxuan Hu; Yong Tang; Baoli Xiang; Wanyun Ma; Wenjun He; Keyu Tao; Yingqi Wang (Fuel, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

Stabilizing Cr(Ⅲ) deriving from tannery sludge with kaolin and organic matter - Junjun Ma; Tao E; Shuyi Yang; Liang Chen; Ying Cheng; Jia Yu; Yun Li (Environmental Research, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Distinct and shared endothermic strategies in the heat producing tissues of tuna and other teleosts - Baosheng Wu; Xueli Gao; Mingling Hu; Jing Hu; Tianming Lan; Tingfeng Xue; Wenjie Xu; Chenglong Zhu; Yuan Yuan; Jiangmin Zheng; Tao Qin; Peidong Xin; et al. (Science China Life Sciences, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

A Preliminary Study of Suspended Matters Variation Associated with Hypoxia and Shoaling Internal Tides on the Continental Shelf of the Northern Andaman Sea - Feilong Lin; Chujin Liang; Tao Ding; Dingyong Zeng; Feng Zhou; Xiao Ma; Chenghao Yang; Hongliang Li; Beifeng Zhou; Chenggang Liu; Weifang Jin (Journal of Marine Science and Engineering, 2023)
The northern Andaman Sea (AS) continental shelf is unique due to the diverse marine ecosystem and existences of both hypoxia and internal tides, but limited in situ observations restrict our understanding of the hydrographic dynamic process. Based on the turbidity, mean volumes of backscattering strength (MVBS), we qualitatively studied the mean distribution characteristics and temporal variation in suspended matters on the northern AS continental shelf and their relation to hypoxia and internal tides. The results of both MVBS and turbidity revealed that the suspended matters exhibited a three-layer vertical structure. The upper and lower layers exhibited high values, while the middle layer had low values. The upper boundary of the high-value region in the upper layer descended below the surface to a depth of 30 m after sunrise and returned to the surface after sunset, indicating a diel vertical migration of zooplankton and micronekton. Daytime migration depth was likely constrained by hypoxia’s upper boundary. In the lower layer, three MVBS enhancements and attenuations correlated with vertical upward and downward velocities, respectively, primarily driven by uplift or suppression. We proposed vertical velocity patterns resulted from internal bores, possibly triggered by shoaling semidiurnal internal tides.

Design and experiment of maize kernel loss monitoring system based on signal interval duration - Jiaqi Dong; Dongxing Zhang; Li Yang; Tao Cui; Xiantao He; Ronghua Ma; Huihui Zhao; Chuan Li; Shulun Xing (Computers and Electronics in Agriculture, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

A comprehensive evaluation of spontaneous pelvic organ prolapse in rhesus macaques as an ideal model for the study of human pelvic organ prolapse - Yaqian Li; Jian Liu; Ye Zhang; Meng Mao; Hong Wang; Yidi Ma; Zhigang Chen; Youyue Zhang; Chengmin Liao; Xiaoqing Chang; Qianqian Gao; Jianbin Guo; et al. (Science Bulletin, 2023)

De novo artificial synthesis of hexoses from carbon dioxide - Jiangang Yang; Wan Song; Tao Cai; Yuyao Wang; Xuewen Zhang; Wangyin Wang; Peng Chen; Yan Zeng; Can Li; Yuanxia Sun; Yanhe Ma (Science Bulletin, 2023)

Trace elements and Li isotopes distinguish between liquid and solid phases contributing to mafic arc magmas - Li-Tao Ma; Li-Qun Dai; Yong-Fei Zheng; Zi-Fu Zhao; Bing Gong; Yilin Xiao; Fengtai Tong (Lithos, 2023)

Transcriptome analysis of miRNAs and mRNAs of medium-sized ovarian follicles of Duroc and Meishan sows - Xin Chen; Su Xie; Mengxun Li; Yi Liu; Lipeng Ma; Tao Huang (Livestock Science, 2023)

Cadmium accumulation in paddy soils affected by geological weathering and mining: Spatial distribution patterns, bioaccumulation prediction, and safe land usage - Cheng Li; Zhongfang Yang; Tao Yu; Zhongcheng Jiang; Qibo Huang; Yeyu Yang; Xu Liu; Xudong Ma; Bo Li; Kun Lin; Tengfang Li (Journal of Hazardous Materials, 2023)

The toxic mechanism of tetracycline on root tips in hulless barley (Hordeum vulgare L. var. nudum) - Wenxiu Xue; Wenhan Liu; Ruwen Ma; Shuhao Zhang; Xingxu Yu; Tao Li; Xiaoyu Luan; Xiaowei Cui; Jia Liu; Chengwei Zhang; Shaolei Shan; Shouqing Ni; et al. (Journal of Hazardous Materials, 2023)

Directed evolution of TetR for constructing sensitive and broad-spectrum tetracycline antibiotics whole-cell biosensor - Shunlan Li; Dongdong Chen; Ziqing Liu; Shipin Tao; Tianyi Zhang; Yiwen Chen; Lingzhi Bao; Jie Ma; Yuee Huang; Shengmin Xu; Lijun Wu; Shaopeng Chen (Journal of Hazardous Materials, 2023)

VPS41-mediated incomplete autophagy aggravates cadmium-induced apoptosis in mouse hepatocytes - Tao Wang; Lianqi Yan; Li Wang; Jian Sun; Huayi Qu; Yonggang Ma; Ruilong Song; Xishuai Tong; Jiaqiao Zhu; Yan Yuan; Jianhong Gu; Jianchun Bian; et al. (Journal of Hazardous Materials, 2023)

Fate of Cd during mineral transformation by sulfate-reducing bacteria in clay-size fractions from soils with high geochemical background - Xing Yan; Dong-Xing Guan; Jie Li; Yinxian Song; Hua Tao; Xianming Zhang; Ming Ma; Junfeng Ji; Wancang Zhao (Journal of Hazardous Materials, 2023)

Mineral-solubilizing microbial inoculant positively affects the multifunctionality of anthropogenic soils in abandoned mining areas - Chong Li; Hui Nie; Shuifeng Zhang; Zhaohui Jia; Shilin Ma; Tao Li; Lu Zhai; Bo Zhang; Xin Liu; Jinchi Zhang; Christoph Müller (Journal of Environmental Management, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Influence of nitrogen sources on wastewater treatment performance by filamentous algae in constructed wetland system - Congcong Zhao; Wenying Li; Dawei Shang; Qilong Ma; Luxing Liu; Jingtao Xu; Jiashuo Meng; Tao Zhang; Qian Wang; Xiaofei Wang; Jian Zhang; Qiang Kong (Environmental Research, 2023)

Temperature-adaptive porous polymer radiative cooling coatings for all-season thermal management and annual energy-saving - YingJie Wu; Bin Liu; RenYan Zhang; Tao Yu; MingBo Pu; Xiong Li; XiaoLiang Ma; YongCai Guo; XianGang Luo (Energy and Buildings, 2023)

New insights into the influence of SO2 as an activator on the physicochemical properties of carbon materials and the influence of S-doping on SO2 adsorption: Experimental and density functional theory study - Jun Li; Jingcai Chang; Shanjie Cheng; Ziang Wang; Yuan Zhao; Binxuan Zhou; Chunyuan Ma; Liqiang Zhang; Tao Wang; Zhanlong Song (Chemical Engineering Journal, 2023)

Revealing the mechanism of adsorption and separation of acetone/methanol by porous carbon via experimental and theoretical calculations - Wenjun Xu; Haoling Huo; Xiancheng Ma; Rongkui Su; Zhipeng Yuan; Xin Liang; Hanqing Wang; Tao Wen; Zheng Zeng; Liqing Li; Shaobin Wang (Chemical Engineering Journal, 2023)

Spherical nano-graphite anode derived from electrochemical stripping for high performance Li-ion capacitors - Zhihua Xiao; Zhuo Chen; Yankun Sun; Tao Li; Lu Zhao; Zechen Li; Zhiqing Yu; Zhenfei Gao; Xinlong Ma; Chunming Xu (Chemical Engineering Journal, 2023)

Elemental sulfur autotrophic partial denitrification (S0-PDN) with high pH and free ammonia control strategy for low-carbon wastewater: From performance to microbial mechanism - Yong Li; Bohan Chen; Xiaolei Zhang; Zhizhan Luo; Mengen Lei; Tao Song; Zhiyun Long; Ji Li; Jun Ma (Chemical Engineering Journal, 2023)

Manipulating the excited states from charge-transfer to hybridized local and charge-transfer towards high-performance blue electroluminescence - He Jiang; Hanlin Li; Jiahao Qiu; Jibiao Jin; Chunying Xi; Peng Tao; Baohua Zhang; Dongge Ma; Wai-Yeung Wong (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Wuzi Yanzong Pill relieves MPTP-induced motor dysfunction and neuron loss by inhibiting NLRP3 inflammasome-mediated neuroinflammation - Tao Pan; Qi Xiao; Hui-Jie Fan; Lei Xu; Shao-Chen Qin; Li-Xia Yang; Xiao-ming Jin; Bao-Guo Xiao; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

Carbon emission characteristics of urban trip based on multi-layer network modeling - Wuyang Hong; Tao Ma; Renzhong Guo; Xiaochun Yang; Xiaoming Li; Maopeng Sun; Yebin Chen; Yiyao Zhong (Applied Geography, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

Efficient removal of Cl-DBPs by direct-indirect continuous hydrodechlorination reduction reaction on Ti3C2X2 surface: A theoretical calculation - Yuxin Zhou; Tao Zhuang; Haijie Cao; Mingxue Li; Yanru Huo; Jinchan Jiang; Yuhui Ma; Ju Xie; Maoxia He (Chemosphere, 2023)

Enhanced hydroxyl radical generation for micropollutant degradation in the In2O3/Vis-LED process through the addition of periodate - Tao Yang; Linqian An; Ge Zeng; Jiamin Mai; Yuying Li; Jinchuan Lian; Haochen Zhang; Juan Li; Xiaoxiang Cheng; Jianbo Jia; Minchao Liu; Jun Ma (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Linking environmental changes and organic matter enrichment in the middle part of the Yanchang Formation (Ordos Basin, China) to the rollback of an oceanic slab in the eastern Paleo-Tethys - Jiaqiang Zhang; Zhen Qiu; Shutong Li; Shanlin Gao; Ruiliang Guo; Xiaofeng Ma; Junli Qiu; Shixiang Li; Huifei Tao; Junlin Chen; Jiacheng Li; Wenjiao Xiao (Sedimentary Geology, 2023)

Dammarane-type saponins from Gynostemma pentaphyllum and their anti-aging activities via up-regulating mitochondria related proteins - Hai-Zhen Liang; Peng-Xin Lu; Li-Li Chu; Gang Li; Chuan-Biao Li; Xiao-Juan Chen; Jie Zhang; Juan Song; Tao Zhang; Ying Luo; Ying Hu; Bai-Ping Ma (Phytochemistry, 2023)

Carbon footprints in pork production and consumption in China from 2005 to 2020 - Haoyue Fan; Kaijie Chen; Haibo Ma; Jian He; Hongyu Li; Zhaoli Yang; Qingyi Wu; Chengsi Zhang; Shulian Zhang; Tao Huang; Hong Gao; Jianmin Ma (Journal of Cleaner Production, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

Insight into wavelength-dependent UVA-LED/chlorine process for micropollutant degradation: Performance, mechanism, and effects of water matrix - Ge Zeng; Jiamin Mai; Linqian An; Cui Huang; Juan Li; Haiping Wang; Qiuhua Li; Jingxin Yang; Xiaolong Xu; Changyu Liu; Jianbo Jia; Tao Yang; et al. (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Study on oxidation kinetics of three kinds of candidate superalloys for VHTR under air ingress accident - Haoxiang Li; Huang Zhang; Wei Zheng; Bin Du; Huaqiang Yin; Xuedong He; Tao Ma; Xingtuan Yang; Huaqiang Yin (Annals of Nuclear Energy, 2023)

Effect of impurity ratios on the high-temperature corrosion of Inconel 617 and Incoloy 800H in impure helium - Wei Zheng; Huang Zhang; Bin Du; Haoxiang Li; Huaqiang Yin; Xuedong He; Tao Ma (Annals of Nuclear Energy, 2023)

The overlooked role of Cr(VI) in micropollutant degradation under solar light irradiation - Tao Yang; Cui Huang; Linqian An; Ge Zeng; Juan Li; Changyu Liu; Xiaolong Xu; Jianbo Jia; Jun Ma (Water Research, 2023)

Efficient removal of p-arsanilic acid and arsenite by Fe(II)/peracetic acid (Fe(II)/PAA) and PAA processes - Tao Yang; Linqian An; Ge Zeng; Maoju Jiang; Juan Li; Changyu Liu; Jianbo Jia; Jun Ma (Water Research, 2023)

Impact of pyroxasulfone on sugarcane rhizosphere microbiome and functioning during field degradation - Yanhui Wang; Jianan Men; Tao Zheng; Yonglin Ma; Weisheng Li; Tomislav Cernava; Lianyang Bai; Decai Jin (Journal of Hazardous Materials, 2023)

Seismic behavior of ultra-high performance concrete columns with GFRP bars under different loading directions - Jiaxing Ma; Guang-Tao Li; Xiao-Fang Deng; Kai Qian (Engineering Structures, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Spatiotemporal variation of ecological environment quality and extreme climate drivers on the Qinghai-Tibetan Plateau - Tao Sun; Yan-mei Yang; Ze-gen Wang; Zhi-wei Yong; Jun-nan Xiong; Guo-li Ma; Jie Li; Ao Liu (Journal of Mountain Science, 2023)

A review on intelligent impedance cytometry systems: Development, applications and advances - Tao Tang; Trisna Julian; Doudou Ma; Yang Yang; Ming Li; Yoichiroh Hosokawa; Yaxiaer Yalikun (Analytica Chimica Acta, 2023)

Inventory, source and health risk assessment of nitrated and parent PAHs in agricultural soils over a rural river in Southeast China - Tao Ma; Jijie Kong; Weidi Li; Xinying Cheng; Yueqing Zhang; Deyang Kong; Shaogui Yang; Shiyin Li; Limin Zhang; Huan He (Chemosphere, 2023)

The positive effects of mineral-solubilizing microbial inoculants on asymbiotic nitrogen fixation of abandoned mine soils are driven by keystone phylotype - Chong Li; Zhaohui Jia; Shuifeng Zhang; Tao Li; Shilin Ma; Xuefei Cheng; Meiling Chen; Hui Nie; Lu Zhai; Bo Zhang; Xin Liu; Jinchi Zhang; et al. (Science of The Total Environment, 2023)

Bioaccumulation characteristics of typical pollutants in seafood from coastal waters of Jiangsu, China - Yangjun Chen; Xueting Chen; Rendong Jiang; Shihu Li; Xiaona Ma; Yixin Sun; Tao Zhang; Zhihua Feng (Continental Shelf Research, 2023)

Engineering oxygen vacancies of 2D WO3 for visible-light-driven benzene hydroxylation with dioxygen - Tao Chen; Fangpei Ma; Zhe Chen; Menglin Xie; Ting Li; Yu Zhou; Jun Wang (Chemical Engineering Journal, 2023)

Cation-deficient T-Nb2O5/graphene Hybrids synthesized via chemical oxidative etching of MXene for advanced lithium-ion capacitors - Lei Wang; Xiong Zhang; Chen Li; Yanan Xu; Yabin An; Wenjie Liu; Tao Hu; Sha Yi; Kai Wang; Xianzhong Sun; Yue Gong; Zhong-Shuai Wu; et al. (Chemical Engineering Journal, 2023)

Identification of the spatial patterns and controlling factors of Se in soil and rice in Guangxi through hot spot analysis - Xu Liu; Chaosheng Zhang; Tao Yu; Wenbing Ji; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Bo Li; Lei Wang; Yuxiang Shao; Kun Lin; Xudong Ma; et al. (Environmental Geochemistry and Health, 2023)

Optimization of anchorage support parameters for soft rock tunnel based on displacement control theory - Gan Li; Wei-bin Ma; Chang-yi Yu; Zhi-gang Tao; Feng-nian Wang (Journal of Mountain Science, 2023)

Solvent-Free Loading of Vitamin A Palmitate into β-Cyclodextrin Metal-Organic Frameworks for Stability Enhancement - Ying Zhang; Jiacai Chen; Zaiyong Zhang; Huajie Zhu; Wuzhen Ma; Xiangyu Zhao; Manli Wang; Caifen Wang; Weidong Chen; Abid Naeem; Jiwen Zhang; Tao Guo; et al. (AAPS PharmSciTech, 2023)

Identification of soil parent materials in naturally high background areas based on machine learning - Cheng Li; Chaosheng Zhang; Tao Yu; Xudong Ma; Yeyu Yang; Xu Liu; Qingye Hou; Bo Li; Kun Lin; Zhongfang Yang; Lei Wang (Science of The Total Environment, 2023)

Organic ligands regulate the environmental impacts of metal-organic frameworks on nitrogen-fixing bacterium Azotobacter vinelandii - Chengzhuang Liang; Qinmei Zhong; Lejie Pan; Fangshi Liu; Xin Li; Jinwei Yang; Yusen Ma; Junrou Zhou; Sheng-Tao Yang (Journal of Hazardous Materials, 2023)

Revealing the nature of dinuclear active sites on CenTiOx catalysts for the selective catalytic reduction NOx with NH3 - Jingchen Zhao; Tao Zhang; Guoxin Ma; Jianning Zhang; Sixuan Li; Weiyu Song; Jian Liu (Journal of Environmental Chemical Engineering, 2023)

RSARE: A physically-based vegetation index for estimating wheat green LAI to mitigate the impact of leaf chlorophyll content and residue-soil background - Wei Li; Dong Li; Shouyang Liu; Frédéric Baret; Zhiyuan Ma; Can He; Timothy A. Warner; Caili Guo; Tao Cheng; Yan Zhu; Weixing Cao; Xia Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Cenozoic morphotectonic evolution of the northeasternmost Tibetan Plateau: Evidence from detrital thermochronology - Xiuxi Wang; Massimiliano Zattin; Lingbing Wang; Bozhong Pang; Yu Yang; Kuang He; Martin Danišík; Xiaomiao Li; Zhenhua Ma; Jia Tao; Ai Song; Huiming Liu; et al. (Global and Planetary Change, 2023)

Formation mechanism of hydrogen production from catalytic pyrolysis of waste tires: A ReaxFF molecular dynamics and experimental study - Zhaoying Li; Qirong Yang; Li Tao; Xinru Ma; Jie Zhou; Tao Ye; Jinhu Wu; Ronghua Wu; Haoxi Ben (Fuel, 2023)

An oral nano-antioxidant for targeted treatment of inflammatory bowel disease by regulating macrophage polarization and inhibiting ferroptosis of intestinal cells - Jing Yang; Yunhao Bai; Shuilin Shen; Xinyue Tao; Chengyu Ma; Bowen Fu; Qihao Dai; Jian Wu; Zhengjie Meng; Qingmin Sun; Xueming Li; Hao Ren (Chemical Engineering Journal, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

The Supplement of Magnesium Element to Inhibit Colorectal Tumor Cells - Heng Li; Xiaonan Feng; Hai Li; Shuo Ma; Wei Song; Bao Yang; Tao Jiang; Chun Yang (Biological Trace Element Research, 2023)
Magnesium ions are essential elements to the human body, with a daily intake of about 350 mg for an adult. Recently, a meta-analysis reported that magnesium ion intake is related to a reduced risk of colorectal tumors. In addition, implantation of biodegradable magnesium pins after colorectal tumor resection could potentially inhibit the residual tumor cells. These impressive results implied that magnesium ions possess inhibitory properties against colorectal carcinoma. However, this hypothesis has yet to be confirmed by experimental results. In this work, different concentrations of magnesium ions were modulated to investigate their inhibitory effects on cell viability through cell cycle arrest, subsequently inducing apoptosis by activating the caspase-3 pathway. The animal experiments revealed that magnesium injection restricted tumor growth after 3 weeks of treatment compared to the control group. According to the immunohistochemistry and transmission electron microscopy results, the remarkable effect may be attributed to promoting the apoptotic rate of tumor cells. The evidence highlights the potential for the clinical use of magnesium implants to inhibit the growth of residual cells after colorectal tumor surgery.

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

Movement and deformation characteristics of overlying rock mass in deep coal seam - Yong Li; Jing Zheng; Feng-nian Wang; Chao-wen Hu; Fan Yang; Xin-gen Ma; Zhi-gang Tao (Journal of Mountain Science, 2023)

Controlled-release nitrogen fertilizer application mitigated N losses and modified microbial community while improving wheat yield and N use efficiency - Quan Ma; Yinsen Qian; Qiaoqiao Yu; Yifan Cao; Rongrong Tao; Min Zhu; Jinfeng Ding; Chunyan Li; Wenshan Guo; Xinkai Zhu (Agriculture, Ecosystems & Environment, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Study on the inactivation and reactivation mechanism of pathogenic bacteria in aquaculture by UVC-LED - Weixiao Zhang; Ruipin Huang; Tao Zhang; Baolong Wang; Na Li; Yan Sun; He Ma; Qian Zhang; Junxin Zhang; Ying Liu (Frontiers in Marine Science, 2023)
Ultraviolet disinfection is an important method for controlling the large-scale outbreaks of diseases in aquaculture. As a novel and promising light source, ultraviolet light-emitting diode (UV-LED) has the advantages of safety, high efficiency and no environmental pollution risks. However, it remains unclear whether UV-LEDs can replace traditional UV light sources for aquaculture water treatment processes. Present study aimed to investigate the efficacy of UVC-LEDs (265 nm) on pathogenic bacteria, specifically Aeromonas salmonicida and Escherichia coli . The effects of UVC-LED dose, light conditions, and temperature on bacterial reactivation were also investigated. The results showed that exposure to UVC-LED effectively inactivated both types of bacteria. To achieve 4.5-log inactivation of A. salmonicida and E. coli , 24 mJ/cm 2 and 28 mJ/cm 2 UVC-LED irradiation were required, and the inactivation rate increased with increasing UVC-LED fluence. Both A. salmonicida and E. coli were revived after UVC-LED disinfection, and photoreactivation was significantly higher than dark reactivation. Bacterial reactivation rate due to high-dose UVC-LED treatment was significantly lower than that of low-dose. After 72 h of reactivation, photoreactivation and dark reactivation rates were 1 ± 0.4% and 2.2 ± 0.2%for A. salmonicida , and 0.02% and 0% for E. coli , respectively. Besides, the photoreactivation rates for the two bacteria exhibited different correlations with temperature. The highest photoreactivation rate for A. salmonicida was 68.7 ± 4% at 20°C, while the highest photoreactivation rate for E. coli was 53.98 ± 2.9% at 15°C for 48 h. This study reveals the rapid and efficient inactivation of bacteria by UVC-LED, and elucidates the mechanism and influencing factors for inactivation and reactivation by UVC-LED. The study also highlights that adequate UVC-LED irradiation and avoidance of visible light after UVC-LED disinfection can effectively inhibit bacterial reactivation. Our findings form a reference for the design and operation of UV disinfection in aquaculture.

Experimental study of the dynamic responses of surrounding jointed rock masses and adjacent underground openings and induced ground vibrations subjected to underground explosion - Yashi Li; Jianbo Zhu; Dongya Han; Rui Zhao; Yankun Ma; Tao Zhou (Tunnelling and Underground Space Technology, 2023)

Invasive Spartina alterniflora habitat forms high energy fluxes but low food web stability compared to adjacent native vegetated habitats - Xiaoxiao Li; Wei Yang; Xu Ma; Zhenchang Zhu; Tao Sun; Baoshan Cui; Zhifeng Yang (Journal of Environmental Management, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Abatement of CO and light alkanes on the heterostructured catalysts: Insights into the interfacial effect - Bin Wang; Hongyuan Ma; Chuan Gao; Yue Xuan; Yanjie Liang; Kangbo Tong; Qiaowan Chang; Yang Yun; Dong Wang; Tao Luan; Kuihua Han; Junhua Li (Chemical Engineering Journal, 2023)

Ensemble learning system to identify nutritional risk and malnutrition in cancer patients without weight loss information - Liangyu Yin; Jie Liu; Ming Liu; Jin Zheng; Aiguo Xu; Quanjun Lyu; Yongdong Feng; Zengqing Guo; Hu Ma; Jipeng Li; Zhikang Chen; Hui Wang; et al. (Science China Life Sciences, 2023)

Overexpression of the ZmSUS1 gene alters the content and composition of endosperm starch in maize (Zea mays L.) - Panpan Li; Haizhen Ma; Ning Xiao; Yuqing Zhang; Tianyu Xu; Tao Xia (Planta, 2023)

Enhanced arsenite removal from water using zirconium-ferrocene MOFs coupled with peroxymonosulfate:oxidation and multi-sites adsorption mechanism - Zongchen Li; Shengjia Ma; Linfeng Sang; Guojuan Qu; Tao Zhang; Bin Xu; Wei Jin; Yaping Zhao (Chemosphere, 2023)

Photolysis of chlorite by solar light: An overlooked mitigation pathway for chlorite and micropollutants - Tao Yang; Mengyang Zhu; Linqian An; Ge Zeng; Chengqian Fan; Juan Li; Jin Jiang; Jun Ma (Water Research, 2023)

Classification and sources of extremely severe sandstorms mixed with haze pollution in Beijing - Tianyi Liu; Fengkui Duan; Yongliang Ma; Tao Ma; Qinqin Zhang; Yunzhi Xu; Fan Li; Tao Huang; Takashi Kimoto; Qiang Zhang; Kebin He (Environmental Pollution, 2023)

Effects of temperature, relative humidity, and illumination on the entomological parameters of Aedes albopictus: an experimental study - Xiaoshuang Cai; Jianguo Zhao; Hui Deng; Jianpeng Xiao; Tao Liu; Weilin Zeng; Xing Li; Jianxiong Hu; Cunrui Huang; Guanghu Zhu; Wenjun Ma (International Journal of Biometeorology, 2023)

Novel insights into aerobic denitrifying bacterial communities augmented denitrification capacity and mechanisms in lake waters - Haihan Zhang; Limin Niu; Ben Ma; Tinglin Huang; Tao Liu; Xiang Liu; Xiaoyan Liu; Yinjie Shi; Hanyan Liu; Haiyun Li; Wanqiu Yang (Science of The Total Environment, 2023)

Predicting the minimum scale of urban ecological space based on socio-ecological systems analysis - Wuyang Hong; Chuangchang Liao; Renzhong Guo; Qi An; Xiaoming Li; Tao Ma (Science of The Total Environment, 2023)

Adaptive reinforcement learning fault-tolerant control for AUVs With thruster faults based on the integral extended state observer - Zhifu Li; Ming Wang; Ge Ma; Tao Zou (Ocean Engineering, 2023)

Effect of solution pulsed plasma process on the degradation and physicochemical properties of pectin - Wenze Hu; Pu Li; Dongxu Guo; Baiqing Zhang; Dongbing Tao; Jinfeng Li; Weitian Zhong; Hui Zang; Yufeng Xu; Fengming Ma (Food Hydrocolloids, 2023)

Neuroprotective effect of hyperoside in MPP+/MPTP -induced dopaminergic neurodegeneration - Xing-Jie Xu; Tao Pan; Hui-Jie Fan; Xu Wang; Jie-Zhong Yu; Hai-Fei Zhang; Bao-Guo Xiao; Zhen-Yu Li; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

Porcine endogenous retrovirus: classification, molecular structure, regulation, function, and potential risk in xenotransplantation - Yu Liu; Yifan Niu; Xiang Ma; Yun Xiang; De Wu; Weifen Li; Tao Wang; Dong Niu (Functional & Integrative Genomics, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Influence of the Moho surface distribution on the oil and gas basins in China seas and adjacent areas - Yimi Zhang; Wanyin Wang; Linzhi Li; Xingang Luo; Dingding Wang; Tao He; Feifei Zhang; Jing Ma (Acta Oceanologica Sinica, 2023)

A chromosome‐level Populus qiongdaoensis genome assembly provides insights into tropical adaptation and a cryptic turnover of sex determination - Yiling Li; Deyan Wang; Weiwei Wang; Wenlu Yang; Jinwen Gao; Wenyan Zhang; Lanxing Shan; Minghui Kang; Yang Chen; Tao Ma (Molecular Ecology, 2023)
Populus species have long been used as model organisms to study the adaptability of trees and the evolution of sex chromosomes. As a species belonging to the section Populus and limited to tropical areas, the P. qiongdaoensis genome contains important information for tropical poplar studies and protection. Here, we report a chromosome‐level genome assembly and annotation of a female P. qiongdaoensis . Gene family clustering, positive selection detection and historical reconstruction of population dynamics revealed the tropical adaptation of P. qiongdaoensis , and showed convergent evolution with another tropical poplar, P. ilicifolia , at the molecular level, especially on some functional genes (e.g., PIF3 and PIL1 ). In addition, we also identified a ZW sex determination system on chromosome 19 of P. qiongdaoensis , and inferred that it seems to have a similar sex determination mechanism to other poplars, controlled by a type‐A cytokinin response regulator ( RR ) gene. However, comparison and phylogenetic analysis of the sex determination regions confirmed a cryptic sex turnover event in the section Populus , which may be caused by the translocation and duplication of the RR gene driven by Helitron ‐like transposable elements. Our study provides new insights into the environmental adaptation and sex chromosome evolution of poplars, and emphasizes the importance of using long read sequencing in ecological and evolutionary inferences of plants.

A spatial distribution – Principal component analysis (SD-PCA) model to assess pollution of heavy metals in soil - Jiawei Liu; Hou Kang; Wendong Tao; Hanyu Li; Dan He; Lixia Ma; Haojie Tang; Siqi Wu; Kexin Yang; Xuxiang Li (Science of The Total Environment, 2023)

Two haplotype-resolved, gap-free genome assemblies for Actinidia latifolia and Actinidia chinensis shed light on the regulatory mechanisms of vitamin C and sucrose metabolism in kiwifruit - Xue Han; Yilin Zhang; Qiong Zhang; Ni Ma; Xiaoying Liu; Wenjing Tao; Zhiying Lou; Caihong Zhong; Xing Wang Deng; Dawei Li; Hang He (Molecular Plant, 2023)

Distinct contribution of aqueous solutions and hydrous melts to the mantle sources: Geochemical evidence from Late Paleozoic igneous rocks in Southwestern Tianshan, Western China - Li-Tao Ma; Li-Qun Dai; Zi-Fu Zhao; Fang Huang; Bing Gong (Lithos, 2023)

CQDs improved the photoelectrocatalytic performance of plasma assembled WO3/TiO2-NRs for bisphenol A degradation - Yi Zhang; Hao Ma; Xinwei Chen; Wenbin Wang; Fangying Li; Tao Qiang; Yiping Shen; Yanqing Cong (Journal of Hazardous Materials, 2023)

Occurrence, partition behavior, source and ecological risk assessment of nitro-PAHs in the sediment and water of Taige Canal, China - Jijie Kong; Tao Ma; Xiaoyu Cao; Weidi Li; Fengxiao Zhu; Huan He; Cheng Sun; Shaogui Yang; Shiyin Li; Qiming Xian (Journal of Environmental Sciences, 2023)

Predicting ozone formation in petrochemical industrialized Lanzhou city by interpretable ensemble machine learning - Li Wang; Yuan Zhao; Jinsen Shi; Jianmin Ma; Xiaoyue Liu; Dongliang Han; Hong Gao; Tao Huang (Environmental Pollution, 2023)

Changes in regional religious activities in the last millennium recorded by black carbon in Lake Dalzong, northeastern Tibetan Plateau - Xuyi Ma; Duo Wu; Yuan Liang; Zijie Yuan; Tao Wang; Youmo Li; Ngondzin Ngawang Gyatso (Science China Earth Sciences, 2023)

Sevoflurane Preconditioning Downregulates GRIA1 Expression to Attenuate Cerebral Ischemia–Reperfusion-Induced Neuronal Injury - Ye Li; Zhi Liang; Shuyan Lei; Xiaoning Wu; Tao Yuan; Kai Ma; Kui Chi (Neurotoxicity Research, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Co-application of biochar and microbial inoculants increases soil phosphorus and potassium fertility and improves soil health and tomato growth - Wei Yang; Yingnan Zhao; Yang Yang; Minshuo Zhang; Xiaoxi Mao; Yanjie Guo; Xiangyu Li; Bu Tao; Yongzhi Qi; Li Ma; Wenju Liu; Bowen Li; et al. (Journal of Soils and Sediments, 2023)

Study on corrosion behavior of two superalloys under two extreme atmospheres - Haoxiang Li; Bin Du; Wei Zheng; Huaqiang Yin; Xuedong He; Tao Ma; Xingtuan Yang (Annals of Nuclear Energy, 2023)

Deep focus-extended darkfield imaging for in situ observation of marine plankton - Tao Chen; Jianping Li; Wenqi Ma; Guannan Guo; Zhenyu Yang; Zhenping Li; Jianping Qiao (Frontiers in Marine Science, 2023)
Darkfield imaging can achieve in situ observation of marine plankton with unique advantages of high-resolution, high-contrast and colorful imaging for plankton species identification, size measurement and abundance estimation. However, existing underwater darkfield imagers have very shallow depth-of-field, leading to inefficient seawater sampling for plankton observation. We develop a data-driven method that can algorithmically refocus planktonic objects in their defocused darkfield images, equivalently achieving focus-extension for their acquisition imagers. We devise a set of dual-channel imaging apparatus to quickly capture paired images of live plankton with different defocus degrees in seawater samples, simulating the settings as in in situ darkfield plankton imaging. Through a series of registration and preprocessing operations on the raw image pairs, a dataset consisting of 55 000 pairs of defocused-focused plankter images have been constructed with an accurate defocus distance label for each defocused image. We use the dataset to train an end-to-end deep convolution neural network named IsPlanktonFE, and testify its focus-extension performance through extensive experiments. The experimental results show that IsPlanktonFE has extended the depth-of-field of a 0.5× darkfield imaging system to ~7 times of its original value. Moreover, the model has exhibited good content and instrument generalizability, and considerable accuracy improvement for a pre-trained ResNet-18 network to classify defocused plankton images. This focus-extension technology is expected to greatly enhance the sampling throughput and efficiency for the future in situ marine plankton observation systems, and promote the wide applications of darkfield plankton imaging instruments in marine ecology research and aquatic environment monitoring programs.

Study on spatial divergence of rural resilience and optimal governance paths in oasis: the case of Yongchang County in the Hexi Corridor of China - Libang Ma; Tianmin Tao; Ziyan Li; Shanshan Wu; Wenbo Zhang (Environment, Development and Sustainability, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Effect of hydrodynamics on the transformation of nitrogen in river water by regulating the mass transfer performance of dissolved oxygen in biofilm - Mei Pan; Haizong Li; Xiangyun Han; Guixiang Quan; Weixing Ma; Qingyuan Guo; Xuan Li; Bairen Yang; Cheng Ding; Yuxi Chen; Tao Yun; Jiaojiao Qin; et al. (Chemosphere, 2023)

Exploring the detailed spatiotemporal characteristics of PM2.5: Generating a full-coverage and hourly PM2.5 dataset in the Sichuan Basin, China - Siwei Zhai; Yi Zhang; Jingfei Huang; Xuelin Li; Wei Wang; Tao Zhang; Fei Yin; Yue Ma (Chemosphere, 2023)

Kinetics study and recycling strategies in different stages of full-component pyrolysis of spent LiNixCoyMnzO2 lithium-ion batteries - Ren Tao; Peng Xing; Huiquan Li; Zhigen Cun; Chenye Wang; Shengyue Ma; Zhenhua Sun (Waste Management, 2023)

Enhanced high-salinity brines treatment using polyamide nanofiltration membrane with tunable interlayered MXene channel - Ao Wang; Hang Xu; Jiawei Fu; Tao Lin; Jun Ma; Mingmei Ding; Li Gao (Science of The Total Environment, 2023)

Generation of hydroxyl radicals via activation of Cr(VI) by UVA-LED for rapid decontamination: The important role of Cr(V) - Cui Huang; Tao Yang; Mingwei Li; Jiamin Mai; Sisi Wu; Juan Li; Guobiao Ma; Changyu Liu; Jianbo Jia; Jun Ma (Journal of Hazardous Materials, 2023)

Peer-to-peer energy sharing with demand-side management for fair revenue distribution and stable grid interaction in the photovoltaic community - Fuyou Zhao; Zhenpeng Li; Dengjia Wang; Tao Ma (Journal of Cleaner Production, 2023)

Combined calcium pretreatment and ultrasonic/microwave drying to dehydrate black chokeberry: Novel mass transfer modeling and metabolic pathways of polyphenols - Rui Zhu; Juan Shen; Chung Lim Law; Xiaoxuan Ma; Dandan Li; Yongbin Han; Hossein Kiani; Sivakumar Manickam; Yang Tao (Innovative Food Science & Emerging Technologies, 2023)

Mechanism research on hydrogen production from catalytic pyrolysis of waste tire rubber - Zhaoying Li; Li Tao; Qirong Yang; Lei Chen; Hao Qi; Xinru Ma; Haoxi Ben (Fuel, 2023)

Fixing zein at the fibrillar carboxymethyl cellulose toward an amphiphilic nano-network - Ying Wan; Jian Li; Jitong Ma; Yanan Li; Ren Wang; Zhengxing Chen; Tao Wang (Food Chemistry, 2023)

Socio-demographic characteristics and inequality in exposure to PM2.5: A case study in the Sichuan basin, China - Jingfei Huang; Xuelin Li; Yi Zhang; Siwei Zhai; Wei Wang; Tao Zhang; Fei Yin; Yue Ma (Environmental Pollution, 2023)

Energy management of the grid-connected residential photovoltaic-battery system using model predictive control coupled with dynamic programming - Bin Zou; Jinqing Peng; Rongxin Yin; Zhengyi Luo; Jiaming Song; Tao Ma; Sihui Li; Hongxing Yang (Energy and Buildings, 2023)

Constructing anti-scaling and anti-wetting polyvinyl alcohol layers through spray-coating with improved water permeability in membrane distillation - Wei Cheng; Peizhi Wang; Xiaolei Zhang; Ji Li; Yiwen Luo; Wenjuan Zhang; Jun Ma; Tao Zhang (Desalination, 2023)

Bioregulation of FeNi LDH morphology and electronic structure to highly promote electrocatalytic oxygen evolution - Guang Li; Chang Liu; Yun Yang; Xiuwen Pan; Tao Wu; Feng Zeng; Enyang Ma; Qing Qu; Lei Li (Chemical Engineering Journal, 2023)

Ambient-stable MXene with superior performance suitable for widespread applications - Xuesong Li; Xiaofei Ma; Huankai Zhang; Ni Xue; Qian Yao; Tao He; Yi Qu; Jian Zhang; Xutang Tao (Chemical Engineering Journal, 2023)

Engineering a protective surface layer to resist membrane scaling and scale-induced wetting in membrane distillation for the treatment of hypersaline wastewater - Peizhi Wang; Wei Cheng; Xiaolei Zhang; Ji Li; Jun Ma; Tao Zhang (Chemical Engineering Journal, 2023)

Smartphone bioelectronic drug with visual colorimetric sensor and bulk nanoencapsulation optogenetic bacteria for chronic kidney disease theragnostics - Meihui Cui; Wei Ling; Lili Zhang; Yayang Li; Jing Liu; Tao Sun; Binglin Ma; Shenjunjie Lu; Huizhuo Pan; Gaoju Pang; Yingying Zhang; Shufang Zhang; et al. (Chemical Engineering Journal, 2023)

Effects of dietary chitosan on the growth, health status and disease resistance of golden pompano (Trachinotus ovatus) - Wei Yu; Yukai Yang; Haimin Chen; Qicun Zhou; Yanwa Zhang; Xiaolin Huang; Zhong Huang; Tao Li; Chuanpeng Zhou; Zhenhua Ma; Qiaer Wu; Heizhao Lin (Carbohydrate Polymers, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Effects of combined application of nitrogen, phosphorus, and potassium fertilizers on tea (Camellia sinensis) growth and fungal community - Sheng Tang; Jingjie Zhou; Wankun Pan; Tao Sun; Mengjiao Liu; Rui Tang; Zijing Li; Qingxu Ma; Lianghuan Wu (Applied Soil Ecology, 2023)

Long-Term Observations of Hypoxia off the Yangtze River Estuary: Toward Prediction and Operational Application - Xiaobo Ni; Feng Zhou; Dingyong Zeng; Dewang Li; Tao Zhang; Kui Wang; Yunlong Ma; Qicheng Meng; Xiao Ma; Qianjiang Zhang; Daji Huang; Jianfang Chen (Oceanography, 2023)
Dissolved oxygen (DO) is essential for the survival of most aquatic organisms. Hypoxia, defined as a DO concentration of less than 2 mg L–1, is a significant issue for ecosystems in estuaries and coastal waters and is one of the top themes of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030). An area off the Yangtze River Estuary (YRE), China, annually develops one of the world ocean’s largest hypoxic areas. Observations collected by ship since 1999, and by long-term sensors since 2009, show that DO concentration in this region has been both declining and greatly fluctuating.

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Dominant complementation of biological pathways in maize hybrid lines is associated with heterosis - Tao Zhou; Rabail Afzal; Muhammad Haroon; Yuting Ma; Hongwei Zhang; Lin Li (Planta, 2022)

Hsa_circ_0006732 regulates colorectal cancer cell proliferation, invasion and EMT by miR-127-5p/RAB3D axis - Tao Yang; Jufeng Sun; Wei Wang; Dongsheng Li; Xianxu Yang; Ang Jia; Yinda Ma; Zhongkai Fan (Molecular and Cellular Biochemistry, 2022)

Analysis of near-field strong motion observations and damages of Menyuan earthquake on 8 January 2022 based on dense MEMS stations - Dongwang Tao; Jianqi Lu; Qiang Ma; Jilong Li; Wen Peng; Shanyou Li (Journal of Seismology, 2022)

Improved lithium-ion batteries with coral-like anodes made of recycled spherical porous silicon coated with nitrogen-doped carbon - Zhao Zhang; Fengshuo Xi; Xiuhua Chen; Shaoyuan Li; Wenhui Ma; Zhao Ding; Tao Qu; Yongnian Dai; Rong Deng (Environmental Chemistry Letters, 2022)

Correction to: Non-normal distribution of radon and residual radon and short-term abnormal precursors of residual radon before major earthquakes - Xiaobing Jin; Junwei Bu; Guilan Qiu; Li Ma; Zhongming Chen; Tao Chen; Junwei Wu; Bo Pan; Hai Ji; Jingxuan Tian; Xiaoxiao Wu; Zhipeng Li; et al. (Earth Science Informatics, 2022)

Non-normal distribution of radon and residual radon and short-term abnormal precursors of residual radon before major earthquakes - Xiaobing Jin; Junwei Bu; Guilan Qiu; Li Ma; Zhongming Chen; Tao Chen; Junwei Wu; Bo Pan; Hai Ji; Jingxuan Tian; Xiaoxiao Wu; Zhipeng Li; et al. (Earth Science Informatics, 2022)

Complete genome sequence of a novel mitovirus isolated from the fungus Fusarium equiseti causing potato dry rot - Xiaofang Zhang; Siwei Li; Zhihao Ma; Qingnian Cai; Tao Zhou; Xuehong Wu (Archives of Virology, 2022)

Biodiversity of freshwater ciliates (Protista, Ciliophora) in the Lake Weishan Wetland, China: the state of the art - Zhe Wang; Yong Chi; Tao Li; Wenya Song; Yunfeng Wang; Tong Wu; Gongaote Zhang; Yujie Liu; Honggang Ma; Weibo Song; Khaled A. S. Al-Rasheid; Alan Warren; et al. (Marine Life Science & Technology, 2022)

Expansion of Quiescent Hematopoietic Stem Cells under Stress and Nonstress Conditions in Mice - Sen Zhang; Yao Ma; Lisha Wang; Xialin Li; Yan Dong; Jinhong Wang; Tao Cheng; Fang Dong; Hideo Ema (Stem Cell Reviews and Reports, 2022)

Ambient gaseous pollutant exposure and incidence of visual impairment among children and adolescents: findings from a longitudinal, two-center cohort study in China - Li Chen; Jing Wei; Tao Ma; Di Gao; Xijie Wang; Bo Wen; Manman Chen; Yanhui Li; Jun Jiang; Lijuan Wu; Weiming Li; Xiangtong Liu; et al. (Environmental Science and Pollution Research, 2022)

Construction and characterization of microsatellite markers for the Neptune whelk, Neptunea cumingii - Peizhen Ma; Tao Zhang; Haizhou Li; Haiyan Wang (Molecular Biology Reports, 2022)

Effect of Zn2+-Cu2+ combined heavy metal on mechanical properties and microstructure of clayey soil - Qiang Ma; Nian-ze Wu; Heng-lin Xiao; Wen-tao Li; Jun-chen Xiang (Journal of Mountain Science, 2022)

A Critical Role for γCaMKII in Decoding NMDA Signaling to Regulate AMPA Receptors in Putative Inhibitory Interneurons - Xingzhi He; Yang Wang; Guangjun Zhou; Jing Yang; Jiarui Li; Tao Li; Hailan Hu; Huan Ma (Neuroscience Bulletin, 2022)

Transport of phosphorus in runoff and sediment with surface runoff from bare purple soil during indoor simulated rainfall - Xiao Ma; Jie Yang; Xiang-jun Zhou; Hong-tao Wu; Qiao Xiong; Ye Li (Journal of Mountain Science, 2022)

lncRNAs MALAT1 and LINC00657 upstream to miR-214-3p/BMP2 regulate osteogenic differentiation of human mesenchymal stem cells - Jun Li; He Zhuang; Zhe Wang; Jun Cai; Xinqiang Ma; Wenxiang Chen; Xibing Jiang; Dongsheng Zhao; Wangjun Hou; Yewei Tao (Molecular Biology Reports, 2022)

Multi-GNSS real-time precise point positioning using BDS-3 global short-message communication to broadcast corrections - Tao Geng; Zhuang Ma; Xin Xie; Jun Tao; Tianjun Liu; Qile Zhao; Juanjuan Li (GPS Solutions, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

The seed primer and biofertilizer performances of living Chlorella pyrenoidosa on Chenopodium quinoa under saline-alkali condition - Chen Ma; Hongli Cui; Chenggang Ren; Jianchao Yang; Zhengyi Liu; Tao Tang; Chunli Ji; Chunhui Zhang; Jinai Xue; Runzhi Li (Journal of Applied Phycology, 2022)

Application of galactinol to tomato enhances tolerance to cold and heat stresses - Yudong Liu; Li Zhang; Jian Ma; Sida Meng; Chunpeng Pang; Xiaomeng Zhao; Huidong Zhang; Shou Wang; Tao Xu; Yi He; Yufeng Liu; Mingfang Qi (Horticulture, Environment, and Biotechnology, 2022)

Early-life educational attainment, APOE ε4 alleles, and incident dementia risk in late life - Hao Ma; Tao Zhou; Xiang Li; Demetrius Maraganore; Yoriko Heianza; Lu Qi (GeroScience, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

One-century sedimentary record, sources, and ecological risk of polycyclic aromatic hydrocarbons in Dianchi Lake, China - Xiaohua Ma; Hao Yang; Changchun Huang; Tao Huang; Shuaidong Li (Environmental Science and Pollution Research, 2022)

Insight into the dynamic microbial community and core bacteria in composting from different sources by advanced bioinformatics methods - Yabin Zhan; Yuan Chang; Yueyue Tao; Hao Zhang; Yongfeng Lin; Jie Deng; Tiantian Ma; Guochun Ding; Yuquan Wei; Ji Li (Environmental Science and Pollution Research, 2022)

An imputed whole-genome sequence-based GWAS approach pinpoints causal mutations for complex traits in a specific swine population - Guorong Yan; Xianxian Liu; Shijun Xiao; Wenshui Xin; Wenwu Xu; Yiping Li; Tao Huang; Jiangtao Qin; Lei Xie; Junwu Ma; Zhiyan Zhang; Lusheng Huang (Science China Life Sciences, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Predicting acupuncture efficacy for functional dyspepsia based on routine clinical features: a machine learning study in the framework of predictive, preventive, and personalized medicine - Tao Yin; Hui Zheng; Tingting Ma; Xiaoping Tian; Jing Xu; Ying Li; Lei Lan; Mailan Liu; Ruirui Sun; Yong Tang; Fanrong Liang; Fang Zeng (EPMA Journal, 2022)

Complete genome sequence of a novel partitivirus infecting the phytopathogenic fungus Alternaria tenuissima - Xiangyu Wang; Zhihao Ma; Rong Li; Tao Zhou; Can Zhao; Xuehong Wu (Archives of Virology, 2022)

Near-epicenter weather conditions several hours before strong earthquakes (Ms ≥ 6) - Tao Chen; Lei Li; Xiao-Xin Zhang; Qi-Ming Ma; Wen Li; Shuo Ti; Han Wu; Ren-Kang Li; Jing Luo; Jian-Feng Su (Natural Hazards, 2022)

Nitric Oxide Signaling Pathway in Ventral Tegmental Area is Involved in Regulation of 7,8-Dihydroxyflavone on Alcohol Consumption in Rats - Qing Gao; Tao Yang; Xin-Xin Li; Jun-Wei Xiong; Wei Ma; Yan-Min Xu; Yong Liu; Hong-Yan Zhang; Qi-Yu Wang; Hong-Xuan Wang; Ying Peng; Xiao-Feng Zhu; et al. (Molecular Neurobiology, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Trends in the impact of socioeconomic developments on polycyclic aromatic hydrocarbon concentrations in Dianchi Lake - Xiaohua Ma; Hao Yang; Shuaidong Li; Changchun Huang; Tao Huang; Hongbin Wan (Environmental Science and Pollution Research, 2022)

Identification and genomic characterization of a novel polymycovirus from Alternaria alternata causing watermelon leaf blight - Guoping Ma; Chunyan Wu; Yuting Li; Yiran Mi; Tao Zhou; Can Zhao; Xuehong Wu (Archives of Virology, 2022)

The in vitro and in vivo anti-inflammatory activities of triterpene saponins from Clematis florida - Na-Na Yang; Yi-Fan Zhang; Hai-Tao Zhang; Xin-Hua Ma; Jin-Huang Shen; Peng Li; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2021)

Assessing rice lodging using UAV visible and multispectral image - Minglu Tian; Songtao Ban; Tao Yuan; Yanbao Ji; Chao Ma; Linyi Li (International Journal of Remote Sensing, 2021)

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

Distinct phylogeographic structures and evolutionary histories of wild medicinal Salvia miltiorrhiza Bunge plant populations in the mountains of Central China - Xiaoguo Wang; Tao Ma; Ying Yun; Yan Li; Jing Zhang; Hongyan Liang; Xitian Yang (Genetic Resources and Crop Evolution, 2021)

The unevenness in observed daily precipitation in mainland China - Guocan Wu; Yun Li; Tao Li; Zhanshan Ma; Chunming Shi (Theoretical and Applied Climatology, 2021)

Evolutionary origin of a tetraploid Allium species on the Qinghai–Tibet Plateau - Minjie Li; Zeyu Zheng; Juncheng Liu; Yongzhi Yang; Guangpeng Ren; Dafu Ru; Shangzhe Zhang; Xin Du; Tao Ma; Richard Milne; Jianquan Liu (Molecular Ecology, 2021)
Extinct taxa may be detectable if they were ancestors to extant hybrid species, which retain their genetic signature. In this study, we combined phylogenomics, population genetics and fluorescence in situ hybridization (GISH and FISH) analyses to trace the origin of the alpine tetraploid Allium tetraploideum (2 n = 4 x = 32), one of the five known members in the subgenus Cyathophora . We found that A. tetraploideum was an obvious allotetrapoploid derived from ancestors including at least two closely related diploid species, A. farreri and A. cyathophorum , from which it differs by multiple ecological and genomic attributes. However, these two species cannot account for the full genome of A. tetraploideum , indicating that at least one extinct diploid is also involved in its ancestry. Furthermore, A. tetraploideum appears to have arisen via homoploid hybrid speciation (HHS) from two extinct allotetraploid parents, which derived in turn from the aforementioned diploids. Other modes of origin were possible, but all were even more complex and involved additional extinct ancestors. Our study together highlights how some polyploid species might have very complex origins, involving both HHS and polyploid speciation and also extinct ancestors.

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Design and Evaluation of a Novel Transversal Double-bud Sugarcane Planter with Seed Pre-cutting - Jia-Qin Zhong; Li-Min Tao; Shang-Ping Li; Fang-Lan Ma; Yuan-Ling Chen (Sugar Tech, 2021)

Do foreign direct investment and environmental regulation improve green technology innovation? An empirical analysis based on panel data from the Chinese manufacturing industry - Shi-Chun Xu; Yun-Fan Li; Jing-Nan Zhang; Yan Wang; Xiao-Xue Ma; Hong-Yu Liu; Hai-Ning Wang; Yuan Tao (Environmental Science and Pollution Research, 2021)

Experimental study on permeability and porosity evolution of host rock with varying damage degrees in excavation damaged area under real-time ultra-high temperature and triaxial stress/seepage pressure condition - Tao Meng; Erbing Li; Yongbin Xue; Jiwei Ma; Wen Liu; Liang Xufeng (Bulletin of Engineering Geology and the Environment, 2021)

Autophagy induced by H. pylori VacA regulated the survival mechanism of the SGC7901 human gastric cancer cell line - Juan Luo; Luyan Bai; Jun Tao; Yu Wen; Mingke Li; Yunzhen Zhu; Sufeng Luo; Guangyu Pu; Lanqing Ma (Genes & Genomics, 2021)
Background Vacuolating cytotoxin (VacA) is an important virulence factor of Helicobacter pylori ( H. pylori ). It was previously believed that VacA can trigger the cascade of apoptosis on mitochondria to lead to cell apoptosis. Recently, it was found that VacA can induce autophagy. However, the molecular mechanism by which VacA induces autophagy is largely unknown. Objective We aimed to explore the molecular mechanism of autophagy induced by H. pylori in gastric cancer cells and the effect of autophagy on the survival of gastric cancer cells. Methods The autophagy of human gastric cancer cell line SGC7901 was detected by Western blot and RT-PCR in the treatment of VacA protein of H. pylori . The relationship between autophagy and reactive oxygen species (ROS) in the proliferation of gastric cancer cells were studied by gene expression silences (siRNA) and CM-H2DCFDA (DCF) staining. Results The results showed that VacA protein secreted by H. pylori in the supernatant stimulated autophagy in SGC7901 cells. After VacA protein treatment, the mRNA expressions of BECN1, ATG7 and PIK3C3, were up-regulated. ATG7 silencing by siRNA inhibited VacA-induced autophagy. Furthermore, our data demonstrated that VacA protein increased ROS levels. Addition of the antioxidant N -acetyl- l -cysteine (NAC) suppressed the levels of ROS, leading to inhibition of autophagy. Conclusions H. pylori VacA is a key toxin that induces autophagy by increased ROS levels. And our findings demonstrated that VacA significantly inhibited proliferation in SGC7901 cells.

Exposure to antibiotics and mental disorders in children: a community-based cross-sectional study - Jingjing Zhang; Kaiyong Liu; Liang Sun; Linsheng Yang; Xinji Liu; Yitian Zhu; Rong Wei; Zhongxiu Jin; Li Wang; Ying Ma; Sufang Wang; Annuo Liu; et al. (Environmental Geochemistry and Health, 2021)

Effects of drought and heat on the productivity and photosynthetic characteristics of alpine meadow plants on the Qinghai-Tibetan Plateau - Li Ma; Zhong-hua Zhang; Bu-qing Yao; Zhen Ma; Xiao-tao Huang; Bing-rong Zhou; Man-hou Xu; Jing Guo; Hua-kun Zhou (Journal of Mountain Science, 2021)

The impact of land use and land cover change on regional climate over East Asia during 1980–2010 using a coupled model - Fuqiang Cao; Li Dan; Zhuguo Ma; Tao Gao (Theoretical and Applied Climatology, 2021)

Nanoemulgel for Improved Topical Delivery of Desonide: Formulation Design and Characterization - Qiuyan Ma; Jing Zhang; Bohong Lu; Huaqing Lin; Rajib Sarkar; Tao Wu; Xuee Li (AAPS PharmSciTech, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Redox-dependent regulation of end-binding protein 1 activity by glutathionylation - Miao Chen; Jian Wang; Yang Yang; Tao Zhong; Peng Zhou; Huixian Ma; Jingrui Li; Dengwen Li; Jun Zhou; Songbo Xie; Min Liu (Science China Life Sciences, 2021)

Dysregulation of circulating follicular helper T cells in type 2 diabetic patients with diabetic retinopathy - Honghua Yu; Baoyi Liu; Guanrong Wu; Zijing Du; Qiaowei Wu; Xiaomin Zeng; Yu Xiao; Ying Fang; Ling Yuan; Suihong Ma; Tao Li (Immunologic Research, 2021)

Urine concentrations of perfluoroalkyl acids in children and contributions of dietary factors: a cross-sectional study from Shanghai, China - Juan Li; Jiafan Li; Yuning Ma; Bo Chen; Xirui Wang; Xianting Jiao; Yihui Jin; Zhemin Shen; Tao Yuan; Xiaodan Yu (Environmental Science and Pollution Research, 2021)

Effects of poor plumage conditions on egg production, antioxidant status and gene expression in laying hens - Junying Li; Chengjie Zhang; Ruiyu Ma; Renrong Qi; Yi Wan; Wei Liu; Tao Zhao; Yan Li; Kai Zhan (Tropical Animal Health and Production, 2021)

Design of the bionic wheel surface based on the friction characteristics of ostrich planta - Hao Pang; Hua Zhang; Rui Zhang; Wenchao Dong; Tao Li; Songsong Ma; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Long Non-coding RNA MALAT1 Upregulates ZEB2 Expression to Promote Malignant Progression of Glioma by Attenuating miR-124 - Hongyu Cheng; Haikang Zhao; Xin Xiao; Qian Huang; Wen Zeng; Bo Tian; Tao Ma; Dan Lu; Yulong Jin; Yuqian Li (Molecular Neurobiology, 2021)

The Biological Role of Optimized Recombinant Oral Long-Acting Glucagon Like Peptide-1 and Its Impact on the Expression of Genes Associated with Glucose Metabolism of Diabetes - Shan He; Jie Zhang; Tao Wang; Ping Wu; Jianyun Liu; Minggang Li; Baicheng Ma (International Journal of Peptide Research and Therapeutics, 2021)

Quantifying clay mineral sources in marine sediments by using end-member mixing analysis - Tao Li; Guanqiang Cai; Chaowen Wang; Kai Liang; Shengzhong Ma; Weidong Luo (Geo-Marine Letters, 2021)

Spatial distribution of atmospheric bioaerosols in Beijing, Hangzhou and Wuhan, China - Xuezheng Ma; Qi Zhang; Keyang Liu; Liping Zhang; Manman Zhang; Xin Zhao; Chunya Zhou; Jinke Li; Ming Cheng; Lili Li; Kongxin Hu; Jinsong Li; et al. (Aerobiologia, 2021)

Estimation of rice plant potassium accumulation based on non-negative matrix factorization using hyperspectral reflectance - Jingshan Lu; Wanyu Li; Minglei Yu; Xiangbin Zhang; Yong Ma; Xi Su; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Precision Agriculture, 2021)

The Association Between Trace Elements Exposure and the Cognition in the Elderly in China - Ling Gu; Jinhui Yu; Yong Fan; Sufang Wang; Linsheng Yang; Kaiyong Liu; Qunan Wang; Guimei Chen; Dongmei Zhang; Ying Ma; Li Wang; Annuo Liu; et al. (Biological Trace Element Research, 2021)

7,8-Dihydroxyflavone Alleviates Anxiety-Like Behavior Induced by Chronic Alcohol Exposure in Mice Involving Tropomyosin-Related Kinase B in the Amygdala - Na Wang; Xing Liu; Xin-Tong Li; Xin-Xin Li; Wei Ma; Yan-Min Xu; Yong Liu; Qing Gao; Tao Yang; Hongxuan Wang; Ying Peng; Xiao-Feng Zhu; et al. (Molecular Neurobiology, 2021)

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

Transdermal Delivery of Salmon Calcitonin Using a Dissolving Microneedle Array: Characterization, Stability, and In vivo Pharmacodynamics - Lu Zhang; Yingying Li; Fang Wei; Hang Liu; Yushuai Wang; Weiman Zhao; Zhiyong Dong; Tao Ma; Qingqing Wang (AAPS PharmSciTech, 2021)

The Beneficial Effects of Aluminum on the Plant Growth in Camellia japonica - Yuanjiao Liu; Jingyu Tao; Jing Cao; Yaping Zeng; Xi Li; Jun Ma; Zhuo Huang; Mingyan Jiang; Lingxia Sun (Journal of Soil Science and Plant Nutrition, 2020)

Large Deformation Mechanism and Three-Level Control Technology of Entry Retaining in Three-Soft Thick Coal Seams - Zimin Ma; Zhibiao Guo; Haohao Wang; Jinzhu Hu; Tao Li; Jing Chen (Geotechnical and Geological Engineering, 2020)

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

Complete genome sequence of a novel recombinant avian leukosis virus isolated from a three-yellow chicken - Tao Sun; Ximei Wang; Wei Han; Xiaoling Ma; Weili Yin; Baohai Fang; Xiao Lin; Yang Li (Archives of Virology, 2020)

Sulfur isotopic compositions of sulfides along the Southwest Indian Ridge: implications for mineralization in ultramafic rocks - Teng Ding; Chunhui Tao; Ágata Alveirinho Dias; Jin Liang; Jie Chen; Bin Wu; Dongsheng Ma; Rongqing Zhang; Jia Wang; Shili Liao; Yuan Wang; Weifang Yang; et al. (Mineralium Deposita, 2020)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Optogenetic Activation of Dopamine Receptor D1 and D2 Neurons in Anterior Cingulate Cortex Differentially Modulates Trigeminal Neuropathic Pain - Sufang Liu; Hui Shu; Joshua Crawford; Yajing Ma; Changsheng Li; Feng Tao (Molecular Neurobiology, 2020)

Mitochondrial Transplantation Attenuates Brain Dysfunction in Sepsis by Driving Microglial M2 Polarization - Chaoying Yan; Zhi Ma; Hongli Ma; Qing Li; Qian Zhai; Tao Jiang; Zhanqin Zhang; Qiang Wang (Molecular Neurobiology, 2020)

Safe utilization and zoning on natural selenium-rich land resources: a case study of the typical area in Enshi County, China - Tao Yu; Wanling Hou; Qingye Hou; Wenjun Ma; Xueqi Xia; Yutong Li; Beizhan Yan; Zhongfang Yang (Environmental Geochemistry and Health, 2020)

Identification and validation of stable quantitative trait loci for grain filling rate in common wheat (Triticum aestivum L.) - Yu Lin; Xiaojun Jiang; Yang Tao; Xilan Yang; Zhiqiang Wang; Fangkun Wu; Shihang Liu; Caixia Li; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; et al. (Theoretical and Applied Genetics, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Genome-wide identification and expression analysis of the CLC superfamily genes in tea plants (Camellia sinensis) - Anqi Xing; Yuanchun Ma; Zichen Wu; Shouhua Nong; Jiaojiao Zhu; Hua Sun; Jing Tao; Bo Wen; Xujun Zhu; Wanping Fang; Xiaocheng Li; Yuhua Wang (Functional & Integrative Genomics, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Research on NO and SO2 removal using TiO2-supported iron catalyst with vaporized H2O2 in a catalytic oxidation combined with absorption process - Zijian Song; Ben Wang; Wu Yang; Tao Chen; Wei Li; Chuan Ma; Lushi Sun (Environmental Science and Pollution Research, 2020)

A conjugated mTOR/MEK bifunctional inhibitor as potential polypharmacological anticancer agent: the prototype compound discovery - Qiangqiang Tao; Fang Fang; Jiaming Li; Yong Wang; Can Zhao; Jingtai Liang; Xiaodong Ma; Hao Wang (Medicinal Chemistry Research, 2020)

Association Between the Change of Serum Copper and Ischemic Stroke: a Systematic Review and Meta-Analysis - Mijuan Zhang; Wei Li; Yan Wang; Tao Wang; Minjiang Ma; Chune Tian (Journal of Molecular Neuroscience, 2020)

Association of Blood Lead Levels with the Risk of Depressive Symptoms in the Elderly Chinese Population: Baseline Data of a Cohort Study - Yong Fan; Jie Sheng; Chunmei Liang; Linsheng Yang; Kaiyong Liu; Qunan Wang; Dongmei Zhang; Ying Ma; Xiude Li; Shaoyu Xie; Hongjuan Cao; Sufang Wang; et al. (Biological Trace Element Research, 2020)

GABAergic Abnormalities Associated with Sensorimotor Cortico-striatal Community Structural Deficits in ErbB4 Knockout Mice and First-Episode Treatment-Naïve Patients with Schizophrenia - Chengcheng Zhang; Peiyan Ni; Yikang Liu; Yang Tian; Jinxue Wei; Bo Xiang; Liansheng Zhao; Xiaojing Li; Xiaohong Ma; Wei Deng; Wanjun Guo; Rongjun Ni; et al. (Neuroscience Bulletin, 2020)

NOD1 inhibits proliferation and enhances response to chemotherapy via suppressing SRC-MAPK pathway in hepatocellular carcinoma - Xiaomin Ma; Yumin Qiu; Lihui Zhu; Yunxue Zhao; Yueke Lin; Dapeng Ma; Zhenzhi Qin; Caiyu Sun; Xuecheng Shen; Tao Li; Lihui Han (Journal of Molecular Medicine, 2020)

The variation of motor-related brain structure and its relation to abnormal motor behaviors in end-stage renal disease patients with restless legs syndrome - Junya Mu; Xiaohui Liu; Shaohui Ma; Tao Chen; Xueying Ma; Peng Li; Dun Ding; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2020)

Role of autumn Arctic Sea ice in the subsequent summer precipitation variability over East Asia - Yang Liu; Yali Zhu; Huijun Wang; Yongqi Gao; Jianqi Sun; Tao Wang; Jiehua Ma; Alla Yurova; Fei Li (International Journal of Climatology, 2020)
This study explored the interannual relationship between autumn Arctic sea ice concentration (SIC) and the subsequent summer precipitation over East Asia (EASP). Since the late‐1990s, the declining SIC in the Kara–Laptev Seas has been significantly correlated with EASP as well as extremely positive anomalies in northern China and intensely negative anomalies in central‐eastern East Asia. However, there was a weak correlation between autumn SIC and EASP before the late‐1990s. Furthermore, the anomalous precipitation pattern in summer and its connection with autumn SIC variability can be explained by the seasonal persistence of continental processes (snow depth and soil moisture) into the spring. In particular, a decreasing SIC was connected with simultaneously positive and negative precipitation anomalies over northeastern China and the Siberian region, respectively, since the late‐1990s and tends to produce corresponding soil moisture anomalies over the Eurasian continent. Declining SIC also favours increased snow depth anomalies in winter over northeastern East Asia. These anomalous signals of surface processes can persist from winter into the subsequent spring, making the connection between the autumn SIC and EASP possible. The Community Earth System Model Large Ensemble simulations further verified these physical processes. More detailed mechanism for this relationship needs to be stressed in further work by numerical simulations. The results have important implications for extending the seasonal prediction validity of EASP. Moreover, before the late‐1990s, SIC‐related circulation anomalies shifted westward and northward as negative precipitation anomalies developed over west Siberia in autumn. As a result, anomalous dry soil conditions in Siberia persisted into the subsequent spring and then led to wetter‐than‐normal conditions through locally negative soil moisture–precipitation feedback before the late‐1990s.

Evidence for the paternal mitochondrial DNA in the crucian carp-like fish lineage with hybrid origin - Shi Wang; Ni Jiao; Lu Zhao; Meiwen Zhang; Pei Zhou; Xuexue Huang; Fangzhou Hu; Conghui Yang; Yuqin Shu; Wuhui Li; Chun Zhang; Min Tao; et al. (Science China Life Sciences, 2020)

Atmospheric mercury accumulation rate in northeastern China during the past 800 years as recorded by the sediments of Tianchi Crater Lake - Tao Zhan; Xin Zhou; Wenhan Cheng; Xiaoqing He; Luyao Tu; Xiaoyan Liu; Junyi Ge; Yuanyun Xie; Jun Zhang; Yongfa Ma; E Li; Yansong Qiao (Environmental Science and Pollution Research, 2020)

Interaction Between Variations in Dopamine D2 and Serotonin 2A Receptor is Associated with Short-Term Response to Antipsychotics in Schizophrenia - Liansheng Zhao; Huijuan Wang; Yamin Zhang; Jinxue Wei; Peiyan Ni; Hongyan Ren; Gang Li; Qiang Wang; Gavin P Reynolds; Weihua Yue; Wei Deng; Hao Yan; et al. (Neuroscience Bulletin, 2019)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Integrated 3D bioprinting-based geometry-control strategy for fabricating corneal substitutes - Bin Zhang; Qian Xue; Han-yi Hu; Meng-fei Yu; Lei Gao; Yi-chen Luo; Yang Li; Jin-tao Li; Liang Ma; Yu-feng Yao; Hua-yong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Energy Consumption, Carbon Emissions and Global Warming Potential of Wolfberry Production in Jingtai Oasis, Gansu Province, China - Yaolin Wang; Quanlin Ma; Yingke Li; Tao Sun; Hujia Jin; Chuanyan Zhao; Eleanor Milne; Mark Easter; Keith Paustian; Hoi Wen Au Yong; John McDonagh (Environmental Management, 2019)
During the last decade, China's agro-food production has increased rapidly and been accompanied by the challenge of increasing greenhouse gas (GHG) emissions and other environmental pollutants from fertilizers, pesticides, and intensive energy use. Understanding the energy use and environmental impacts of crop production will help identify environmentally damaging hotspots of agro-production, allowing environmental impacts to be assessed and crop management strategies optimized. Conventional farming has been widely employed in wolfberry ( Lycium barbarum ) cultivation in China, which is an important cash tree crop not only for the rural economy but also from an ecological standpoint. Energy use and global warming potential (GWP) were investigated in a wolfberry production system in the Yellow River irrigated Jingtai region of Gansu. In total, 52 household farms were randomly selected to conduct the investigation using questionnaires. Total energy input and output were 321,800.73 and 166,888.80 MJ ha −1 , respectively, in the production system. The highest share of energy inputs was found to be electricity consumption for lifting irrigation water, accounting for 68.52%, followed by chemical fertilizer application (11.37%). Energy use efficiency was 0.52 when considering both fruit and pruned wood. Nonrenewable energy use (88.52%) was far larger than the renewable energy input. The share of GWP of different inputs were 64.52% electricity, 27.72% nitrogen (N) fertilizer, 5.07% phosphate, 2.32% diesel, and 0.37% potassium, respectively. The highest share was related to electricity consumption for irrigation, followed by N fertilizer use. Total GWP in the wolfberry planting system was 26,018.64 kg CO 2 eq ha −1 and the share of CO 2 , N 2 O, and CH 4 were 99.47%, 0.48%, and negligible respectively with CO 2 being dominant. Pathways for reducing energy use and GHG emission mitigation include: conversion to low carbon farming to establish a sustainable and cleaner production system with options of raising water use efficiency by adopting a seasonal gradient water pricing system and advanced irrigation techniques; reducing synthetic fertilizer use; and policy support: smallholder farmland transfer (concentration) for scale production, credit (small- and low-interest credit) and tax breaks.

Two new sesquiterpenoids from the marine-sediment-derived fungus Trichoderma harzianum P1-4 - Sheng-Tao Fang; Ying-Jie Wang; Xin-Yue Ma; Xiu-Li Yin; Nai-Yun Ji (Natural Product Research, 2019)

The effect of substrate grain size on burrowing ability and distribution characteristics of Perinereis aibuhitensis - Tao Sun; Chun’e Liu; Xingzuo Li; Dongzhengyang An; Hairui Yu; Zheng Ma; Feng Liu (Acta Oceanologica Sinica, 2019)

White Matter Abnormalities in Major Depression Biotypes Identified by Diffusion Tensor Imaging - Sugai Liang; Qiang Wang; Xiangzhen Kong; Wei Deng; Xiao Yang; Xiaojing Li; Zhong Zhang; Jian Zhang; Chengcheng Zhang; Xin-min Li; Xiaohong Ma; Junming Shao; et al. (Neuroscience Bulletin, 2019)

Exosomes from patients with Parkinson’s disease are pathological in mice - Chao Han; Nian Xiong; Xingfang Guo; Jinsha Huang; Kai Ma; Ling Liu; Yun Xia; Yan Shen; Jie Li; Haiyang Jiang; Luxi Wang; Shiyi Guo; et al. (Journal of Molecular Medicine, 2019)

Synoptic-scale atmospheric circulation anomalies associated with summertime daily precipitation extremes in the middle–lower reaches of the Yangtze River Basin - Fuqiang Cao; Tao Gao; Li Dan; Zhuguo Ma; Xiaolong Chen; Liwei Zou; Lixia Zhang (Climate Dynamics, 2019)

Assessment of slope construction risk uncertainty based on index importance ranking - Daming Lin; Ping Chen; Jilei Ma; Yun Zhao; Tao Xie; Renmao Yuan; Lin Li (Bulletin of Engineering Geology and the Environment, 2019)

Contribution of methylation regulation of MpDREB2A promoter to drought resistance of Mauls prunifolia - Xuewei Li; Yinpeng Xie; Liyuan Lu; Mingjia Yan; Nan Fang; Jidi Xu; Liping Wang; Yan Yan; Tao Zhao; Steve van Nocker; Fengwang Ma; Dong Liang; et al. (Plant and Soil, 2019)

Age-Related Reduction in Cortical Thickness in First-Episode Treatment-Naïve Patients with Schizophrenia - Yin Lin; Mingli Li; Yi Zhou; Wei Deng; Xiaohong Ma; Qiang Wang; Wanjun Guo; Yinfei Li; Lijun Jiang; Xun Hu; Nanyin Zhang; Tao Li (Neuroscience Bulletin, 2019)

A female attractant for the blue gum chalcid, Leptocybe invasa (Hymenoptera: Eulophidae), from host plant (DH 201-2: Eucalyptus grandis × Eucalyptus tereticornis) - Tao Ma; Laijiao Lan; Na Lin; Lifei Zheng; Zhaohui Sun; Yizhen Li; Xiujun Wen (Arthropod-Plant Interactions, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Development of a duplex reverse transcription recombinase-aided amplification assay for respiratory syncytial virus incorporating an internal control - Juju Qi; Xinna Li; Yi Zhang; Xinxin Shen; Guowei Song; Jing Pan; Tao Fan; Ruihuan Wang; Lixin Li; Xuejun Ma (Archives of Virology, 2019)

Insights from avian influenza surveillance of chickens and ducks before and after exposure to live poultry markets - Mei Li; Xin Yin; Lizheng Guan; Xia Zhang; Guohua Deng; Tao Li; Pengfei Cui; Yong Ma; Yujie Hou; Jianzhong Shi; Hualan Chen (Science China Life Sciences, 2019)

The Influence of Large Scale Phosphate Mining on the Water Quality of the Huangbaihe River Basin in China: Dominant Pollutants and Spatial Distributions - Gebrehiwet Legese Reta; Xiaohua Dong; Bob Su; Xiaonong Hu; Huijuan Bo; Hao Wan; Ji Liu; Yinghai Li; Tao Peng; Haibo Ma; Kai Wang; Shijin Xu (Mine Water and the Environment, 2019)

Testing the role of genetic variation of the MC4R gene in Chinese population in antipsychotic-induced metabolic disturbance - Yamin Zhang; Hongyan Ren; Qiang Wang; Wei Deng; Weihua Yue; Hao Yan; Liwen Tan; Qi Chen; Guigang Yang; Tianlan Lu; Lifang Wang; Fuquan Zhang; et al. (Science China Life Sciences, 2019)

Landslide integrated characteristics and susceptibility assessment in Rongxian county of Guangxi, China - Li-ping Liao; Ying-yan Zhu; Yan-lin Zhao; Hai-tao Wen; Yun-chuan Yang; Li-hua Chen; Shao-kun Ma; Ying-zi Xu (Journal of Mountain Science, 2019)

Identification and Characterization of EDT1 Conferring Drought Tolerance in Rice - Tao Wu; Mingxing Zhang; Hongjia Zhang; Kai Huang; Mojun Chen; Chen Chen; Xue Yang; Zhao Li; Haoyuan Chen; Zhiming Ma; Xunming Zhang; Wenzhu Jiang; et al. (Journal of Plant Biology, 2019)

A new actinomycin Z analogue with an additional oxygen bridge between chromophore and β -depsipentapeptide from Streptomyces sp. KIB-H714 - Miao Dong; Pei Cao; Ya-Tuan Ma; Jianying Luo; Yijun Yan; Rong-Tao Li; Sheng-Xiong Huang (Natural Product Research, 2019)

Effects of different green manure treatments on soil apparent N and P balance under a 34-year double-rice cropping system - Xi Hong; Chao Ma; Jusheng Gao; Shiming Su; Tao Li; Zunchang Luo; Ran Duan; Yanan Wang; Lingyu Bai; Xibai Zeng (Journal of Soils and Sediments, 2019)

Spatiotemporal variation of atmospheric nitrated polycyclic aromatic hydrocarbons in semi-arid and petrochemical industrialized Lanzhou City, Northwest China - Panliang Liu; Yuanli Ju; Yaojie Li; Zhanxiang Wang; Xiaoxuan Mao; Hongmei Cao; Chenhui Jia; Tao Huang; Hong Gao; Jianmin Ma (Environmental Science and Pollution Research, 2019)

L-3-n-Butylphthalide reduces ischemic stroke injury and increases M2 microglial polarization - Fangfang Li; Qingfeng Ma; Haiping Zhao; Rongliang Wang; Zhen Tao; Zhibin Fan; Sijia Zhang; Guangwen Li; Yumin Luo (Metabolic Brain Disease, 2018)

Correction to: Fine mapping of powdery mildew resistance gene Pm4e in bread wheat (Triticum aestivum L.) - Khan Nasr Ullah; Na Li; Tao Shen; Peisi Wang; Wenbin Tang; Shengwei Ma; Zhimeng Zhang; Haiyan Jia; Zhongxin Kong; Zhengqiang Ma (Planta, 2018)

Fine mapping of powdery mildew resistance gene Pm4e in bread wheat (Triticum aestivum L.) - Khan Nasr Ullah; Na Li; Tao Shen; Peisi Wang; Wenbin Tang; Shengwei Ma; Zhimeng Zhang; Haiyan Jia; Zhongxin Kong; Zhengqiang Ma (Planta, 2018)

Differential expression of miR-let7a in hair follicle cycle of Liaoning cashmere goats and identification of its targets - Tao Ma; Jianping Li; Qian Jiang; Sufang Wu; Huaizhi Jiang; Qiaoling Zhang (Functional & Integrative Genomics, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Abnormal interaction between cognitive control network and affective network in patients with end-stage renal disease - Junya Mu; Tao Chen; Qianqian Liu; Dun Ding; Xueying Ma; Peng Li; Anmao Li; Mingxia Huang; Zengjun Zhang; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

The levels of polycyclic aromatic hydrocarbons (PAHs) in human milk and exposure risk to breastfed infants in petrochemical industrialized Lanzhou Valley, Northwest China - Li Wang; Aiping Liu; Yuan Zhao; Xi Mu; Tao Huang; Hong Gao; Jianmin Ma (Environmental Science and Pollution Research, 2018)

Fast local wavenumber (FLW) method for the inversion of magnetic source parameters - Guo-Qing Ma; Yan-Bo Ming; Jiang-Tao Han; Li-Li Li; Qing-Fa Meng (Applied Geophysics, 2018)

Particulate and gaseous pollutants in a petrochemical industrialized valley city, Western China during 2013–2016 - Xi Zhou; Tingjun Zhang; Zhongqin Li; Yan Tao; Feiteng Wang; Xin Zhang; Chunhai Xu; Shan Ma; Ju Huang (Environmental Science and Pollution Research, 2018)

Neurocognitive Graphs of First-Episode Schizophrenia and Major Depression Based on Cognitive Features - Sugai Liang; Roberto Vega; Xiangzhen Kong; Wei Deng; Qiang Wang; Xiaohong Ma; Mingli Li; Xun Hu; Andrew J. Greenshaw; Russell Greiner; Tao Li (Neuroscience Bulletin, 2018)

Response of ammonia-oxidizing betaproteobacteria to short-term fertilization in a salt marsh in China - Yuexin Ma; Wei Tao; Jiao Liu; Changfa Liu; Jin Li; Jichen Liu (Journal of Oceanology and Limnology, 2018)

Spectral Characteristics of Autofluorescence in Renal Tissue and Methods for Reducing Fluorescence Background in Confocal Laser Scanning Microscopy - Yang Zhang; Yang Wang; Wei-Wei Cao; Ke-Tao Ma; Wei Ji; Zi-Wei Han; Jun-Qiang Si; Li Li (Journal of Fluorescence, 2018)

Npro His49 and Erns Lys412 mutations in pig bovine viral diarrhea virus type 2 synergistically enhance the cellular antiviral response - Jie Tao; Benqiang Li; Jinghua Chen; Chunling Zhang; Yufei Ma; Guoqiang Zhu; Huili Liu (Virus Genes, 2018)

Bioactive constituents from the whole plants of Leontopodium leontopodioides (Wild.) Beauv. - Qiu Chen; Jian Li; Jingya Ruan; Lu Qu; Hongyan Wei; Xiaoling Ma; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2018)

Colony formation by the green alga Chlorella vulgaris in response to the competitor Ceratophyllum demersum - Jing Dong; Yunni Gao; Mengyang Chang; Hanhui Ma; Kun Han; Xin Tao; Yan Li (Hydrobiologia, 2018)

Spatiotemporal pattern of gross primary productivity and its covariation with climate in China over the last thirty years - Yitong Yao; Xuhui Wang; Yue Li; Tao Wang; Miaogen Shen; Mingyuan Du; Honglin He; Yingnian Li; Weijun Luo; Mingguo Ma; Yaoming Ma; Yanhong Tang; et al. (Global Change Biology, 2018)
The uncertainties of China's gross primary productivity ( GPP ) estimates by global data‐oriented products and ecosystem models justify a development of high‐resolution data‐oriented GPP dataset over China. We applied a machine learning algorithm developing a new GPP dataset for China with 0.1° spatial resolution and monthly temporal frequency based on eddy flux measurements from 40 sites in China and surrounding countries, most of which have not been explored in previous global GPP datasets. According to our estimates, mean annual GPP over China is 6.62 ± 0.23 PgC/year during 1982–2015 with a clear gradient from southeast to northwest. The trend of GPP estimated by this study (0.020 ± 0.002 PgC/year 2 from 1982 to 2015) is almost two times of that estimated by the previous global dataset. The GPP increment is widely spread with 60% area showing significant increasing trend ( p GPP magnitudes but underestimated the temporal trend of GPP . The monsoon affected eastern China, in particular the area surrounding Qinling Mountain, seems having larger contribution to interannual variability ( IAV ) of China's GPP than the semiarid northwestern China and Tibetan Plateau. At country scale, temperature is the dominant climatic driver for IAV of GPP . The area where IAV of GPP dominated by temperature is about 42%, while precipitation and solar radiation dominate 31% and 27% respectively over semiarid area and cold‐wet area. Such spatial pattern was generally consistent with global GPP dataset, except over the Tibetan Plateau and northeastern forests, but not captured by most ecosystem models, highlighting future research needs to improve the modeling of ecosystem response to climate variations.

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Forced hot-air treatment against Bactrocera papayae (Diptera: Tephritidae) in papaya - Bo Liu; Baishu Li; Guoping Zhan; Tao Zha; Yuejin Wang; Chen Ma (Applied Entomology and Zoology, 2017)

Mechanism of Lycium barbarum polysaccharides on primary cultured rat hippocampal neurons - Peng Zhao; Ning-Tian Ma; Ren-Yuan Chang; Yu-Xiang Li; Yin-Ju Hao; Wen-Li Yang; Jie Zheng; Yang Niu; Tao Sun; Jian-Qiang Yu (Cell and Tissue Research, 2017)

A new three-band spectral index for mitigating the saturation in the estimation of leaf area index in wheat - Zhongsheng Cao; Tao Cheng; Xue Ma; Yongchao Tian; Yan Zhu; Xia Yao; Qi Chen; Shiyao Liu; Ziyu Guo; Qiaomei Zhen; Xin Li (International Journal of Remote Sensing, 2017)

Characterization of iron diagenesis in marine sediments using refined iron speciation and quantized iron(III)-oxide reactivity: a case study in the Jiaozhou Bay, China - Jing Tao; Weiwei Ma; Maoxu Zhu; Tie Li; Rujun Yang (Acta Oceanologica Sinica, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

230Th/238U dating of hydrothermal sulfides from Duanqiao hydrothermal field, Southwest Indian Ridge - Weifang Yang; Chunhui Tao; Huaiming Li; Jin Liang; Shili Liao; Jiangping Long; Zhibang Ma; Lisheng Wang (Marine Geophysical Research, 2017)

Response of microbial biomass and bacterial community composition to fertilization in a salt marsh in China - Yuexin Ma; Wei Tao; Changfa Liu; Jiao Liu; Zhiping Yang; Jin Li; Jichen Liu (Acta Oceanologica Sinica, 2017)

RBD and Neurodegenerative Diseases - Haiyang Jiang; Jinsha Huang; Yan Shen; Shiyi Guo; Luxi Wang; Chao Han; Ling Liu; Kai Ma; Yun Xia; Jie Li; Xiaoyun Xu; Nian Xiong; et al. (Molecular Neurobiology, 2017)

Spatial distribution of atmospheric PAHs and their genotoxicity in petrochemical industrialized Lanzhou valley, northwest China - Li Wang; Yuan Zhao; Xin Yi; Zhanxiang Wang; Yayi Yi; Tao Huang; Hong Gao; Jianmin Ma (Environmental Science and Pollution Research, 2017)

Early Cretaceous porphyry copper mineralization in Northeast China: the Changfagou example - Yong Zhang; Shu–Wen Xing; Chao Li; Shi–Fu Liang; Zheng–Tao Yu; Xiao–Hui Du; Yan Wang; Zeng–Jie Zhang; Yu–Bo Ma (International Geology Review, 2017)

T2 relaxation time measurements in the brains of scalded rats - Tao Jiang; Liqi Xie; Xin Lou; Dawei Li; Zhiye Chen; Huafeng Xiao; Lin Ma (Science China Life Sciences, 2017)

The Pivotal Role of Ca2+ Homeostasis in PBDE-47-Induced Neuronal Apoptosis - Shun Zhang; Yihu Chen; Xue Wu; Hui Gao; Rulin Ma; Chunyang Jiang; Gang kuang; Guodong Zhao; Tao Xia; Xiaofei Zhang; Rongrong Lei; Cheng Zhang; et al. (Molecular Neurobiology, 2016)

Field‐based evidence for copper contamination induced changes of antibiotic resistance in agricultural soils - Hang‐Wei Hu; Jun‐Tao Wang; Jing Li; Jun‐Jian Li; Yi‐Bing Ma; Deli Chen; Ji‐Zheng He (Environmental Microbiology, 2016)
Summary Bacterial resistance to antibiotics and heavy metals are frequently linked, suggesting that exposure to heavy metals might select for bacterial assemblages conferring resistance to antibiotics. However, there is a lack of clear evidence for the heavy metal‐induced changes of antibiotic resistance in a long‐term basis. Here, we used high‐capacity quantitative PCR array to investigate the responses of a broad spectrum of antibiotic resistance genes (ARGs) to 4–5 year copper contamination (0–800 mg kg −1 ) in two contrasting agricultural soils. In total, 157 and 149 unique ARGs were detected in the red and fluvo‐aquic soil, respectively, with multidrug and β‐ lactam as the most dominant ARG types. The highest diversity and abundance of ARGs were observed in medium copper concentrations (100–200 mg kg −1 ) of the red soil and in high copper concentrations (400–800 mg kg −1 ) of the fluvo‐aquic soil. The abundances of total ARGs and several ARG types had significantly positive correlations with mobile genetic elements (MGEs), suggesting mobility potential of ARGs in copper‐contaminated soils. Network analysis revealed significant co‐occurrence patterns between ARGs and microbial taxa, indicating strong associations between ARGs and bacterial communities. Structural equation models showed that the significant impacts of copper contamination on ARG patterns were mainly driven by changes in bacterial community compositions and MGEs. Our results provide field‐based evidence that long‐term Cu contamination significantly changed the diversity, abundance and mobility potential of environmental antibiotic resistance, and caution the un‐perceived risk of the ARG dissemination in heavy metal polluted environments.

First report of the melon stem rot disease in protected cultivation caused by Pseudomonas fluorescens - Chenghua Zhang; Tao Lin; Jufen Li; Guobin Ma; Yiwen Wang; Pinkuan Zhu; Ling Xu (Journal of Plant Diseases and Protection, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Experimental and numerical study on fracture propagation near open-hole horizontal well under hydraulic pressure - Shou Ma; Jianchun Guo; Lianchong Li; Yingjie Xia; Tao Yang (European Journal of Environmental and Civil Engineering, 2016)

Characteristics of Infrared Radiation of Coal Specimens Under Uniaxial Loading - Liqiang Ma; Hai Sun; Yao Zhang; Tao Zhou; Ke Li; Jinshuai Guo (Rock Mechanics and Rock Engineering, 2016)

Study on the photosynthetic characteristics of a Pyropia haitanensis red mutant cultured under different light intensities - Tao Zhang; Jiafu Li; Fei Ma; Zonggen Shen; Qinqin Lu; Jianyi Zhu (Journal of Applied Phycology, 2016)

Sources and potential health risk of gas phase PAHs in Hexi Corridor, Northwest China - Xiaoxuan Mao; Zhousuo Yu; Zhongyuan Ding; Tao Huang; Jianmin Ma; Gan Zhang; Jun Li; Hong Gao (Environmental Science and Pollution Research, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

The Adsorption and Desorption of Pb2+ and Cd2+ in Freeze–Thaw Treated Soils - Linhui Li; Jincai Ma; Meng Xu; Xu Li; Jiahui Tao; Guanzhu Wang; Jitong Yu; Ping Guo (Bulletin of Environmental Contamination and Toxicology, 2016)

Molecular cloning and expression analysis of the retinoid X receptor (RXR) gene in golden pompano Trachinotus ovatus fed Artemia nauplii with different enrichments - Qibin Yang; Panlong Zheng; Zhenhua Ma; Tao Li; Shigui Jiang; Jian G. Qin (Fish Physiology and Biochemistry, 2015)

Cancer risk of petrochemical workers exposed to airborne PAHs in industrial Lanzhou City, China - Li Wang; Yuan Zhao; Xianying Liu; Tao Huang; Yanan Wang; Hong Gao; Jianmin Ma (Environmental Science and Pollution Research, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Electrophysiological and behavioral responses of Diaphania glauculalis males to female sex pheromone - Tao Ma; Zhi Tao Liu; Yuan Yuan Zhang; Zhao Hui Sun; Yi Zhen Li; Xiu Jun Wen; Xiao Yang Chen (Environmental Science and Pollution Research, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Identification of Genes Involved in the Biosynthesis of Tripterygium wilfordii Hook.f. Secondary Metabolites by Suppression Subtractive Hybridization - Guo-peng Miao; Wei Li; Bin Zhang; Zhan-feng Zhang; Zhi-qing Ma; Jun-tao Feng; Xing Zhang; Chuan-shu Zhu (Plant Molecular Biology Reporter, 2015)

NMDAR-Mediated Hippocampal Neuronal Death is Exacerbated by Activities of ASIC1a - Su Gao; Yang Yu; Zhi-Yuan Ma; Hui Sun; Yong-Li Zhang; Xing-Tao Wang; Chaoyun Wang; Wei-Ming Fan; Qing-Yin Zheng; Chun-Lei Ma (Neurotoxicity Research, 2015)

Poloxamer 188 Attenuates Cerebral Hypoxia/Ischemia Injury in Parallel with Preventing Mitochondrial Membrane Permeabilization and Autophagic Activation - Chengliang Luo; Qianqian Li; Yuan Gao; Xi Shen; Lu Ma; Qiong Wu; Zufeng Wang; Mingyang Zhang; Ziqin Zhao; Xiping Chen; Luyang Tao (Journal of Molecular Neuroscience, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Apolipoprotein E gene polymorphisms associated with processing speed and executive functions in healthy Han Chinese - Cheng-Cheng Zhang; Hong-Yan Ren; Ming-Li Li; Qiang Wang; Wei Deng; Wan-Jun Guo; Wei Lei; Bo Xiang; Lian-Sheng Zhao; Xiao-Hong Ma; Yong-Gang Yao; Tao Li (Neuroscience Bulletin, 2015)

Short-term effects of multiple ozone metrics on daily mortality in a megacity of China - Tiantian Li; Meilin Yan; Wenjun Ma; Jie Ban; Tao Liu; Hualiang Lin; Zhaorong Liu (Environmental Science and Pollution Research, 2015)

Research to Improve the Efficiency of Double Stereo PCR Microfluidic Chip by Passivating the Inner Surface of Steel Capillary with NOA61 - Jian Wu; Wei Guo; Chunyan Wang; Kuanxin Yu; Ying Ma; Tao Chen; Yinghui Li (Cell Biochemistry and Biophysics, 2015)

Transient receptor potential vanilloid 4 inhibits rat HSC-T6 apoptosis through induction of autophagy - Lei Zhan; Yang Yang; Tao-Tao Ma; Cheng Huang; Xiao-Ming Meng; Lei Zhang; Jun Li (Molecular and Cellular Biochemistry, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

Histone methyltransferase G9a and H3K9 dimethylation inhibit the self-renewal of glioma cancer stem cells - Hong Tao; Haiying Li; Yanhuang Su; Danni Feng; Xilong Wang; Chun Zhang; Hui Ma; Qikuan Hu (Molecular and Cellular Biochemistry, 2014)

Production of lycopene by metabolically-engineered Escherichia coli - Tao Sun; Liangtian Miao; Qingyan Li; Guanping Dai; Fuping Lu; Tao Liu; Xueli Zhang; Yanhe Ma (Biotechnology Letters, 2014)

An inactivated recombinant rabies CVS-11 virus expressing two copies of the glycoprotein elicits a higher level of neutralizing antibodies and provides better protection in mice - Xiang-Hong Xue; Xue-Xing Zheng; Hua-Lei Wang; Jin-Zhu Ma; Ling Li; Wei-Wei Gai; Tie-Cheng Wang; Song-Tao Yang; Xian-Zhu Xia (Virus Genes, 2014)

Assessing spatial distribution, sources, and human health risk of organochlorine pesticide residues in the soils of arid and semiarid areas of northwest China - Tao Huang; Qiang Guo; Hui Tian; Xiaoxuan Mao; Zhongyuan Ding; Gan Zhang; Jun Li; Jianmin Ma; Hong Gao (Environmental Science and Pollution Research, 2014)

Study of photosynthetic characteristics of the Pyropia yezoensis thallus during the cultivation process - Tao Zhang; Jiafu Li; Fei Ma; Qinqin Lu; Zonggen Shen; Jianyi Zhu (Journal of Applied Phycology, 2014)

Participation of miR-200a in TGF-β1-mediated hepatic stellate cell activation - Xu Sun; Yong He; Tao-Tao Ma; Cheng Huang; Lei Zhang; Jun Li (Molecular and Cellular Biochemistry, 2014)

Mas-related G protein-coupled receptor D is coupled to endogenous calcium-activated chloride channel in Xenopus oocytes - Ren-Gong Zhuo; Xiao-Yun Ma; Pei-Lan Zhou; Xiao-Yan Liu; Kang Zhang; Xiao-Li Wei; Hai-Tao Yan; Jiang-Ping Xu; Jian-Quan Zheng (Journal of Physiology and Biochemistry, 2014)

Effects of cannabinoid receptor type 2 on endogenous myocardial regeneration by activating cardiac progenitor cells in mouse infarcted heart - YaBin Wang; Sai Ma; Qiang Wang; WenXing Hu; DongJuan Wang; XiuJuan Li; Tao Su; Xing Qin; XiaoTian Zhang; Ke Ma; JiangWei Chen; LiZe Xiong; et al. (Science China Life Sciences, 2014)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

The influence of high glucose on the Cip/Kip family expression profiles in HRECs - Jingyi Tian; Hongjie Ma; Yan Luo; Andina Hu; Shaofen Lin; Tao Li; Kai Guo; Jing Li; Meng Cai; Shibo Tang (Journal of Molecular Histology, 2013)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Genetic phylogeography and maternal lineages of 18 Chinese black goat breeds - Tao Zhong; Qian Jun Zhao; Li Li Niu; Jie Wang; Peng Fei Jin; Wei Zhao; Lin Jie Wang; Li Li; Hong Ping Zhang; Yue Hui Ma (Tropical Animal Health and Production, 2013)

Reducing basal salicylic acid enhances Arabidopsis tolerance to lead or cadmium - Siyuan Tao; Lihong Sun; Chunyan Ma; Linlin Li; Guangzhe Li; Lin Hao (Plant and Soil, 2013)

β-Arrestin-2 inhibits preference for alcohol in mice and suppresses Akt signaling in the dorsal striatum - Haohong Li; Yezheng Tao; Li Ma; Xing Liu; Lan Ma (Neuroscience Bulletin, 2013)

Gridded inventories of historical usage for selected organochlorine pesticides in Gansu Province, China - Tao Huang; Xiangyang Li; Chongguo Tian; Xianming Yang; Li Wang; Yuan Zhao; Jianmin Ma; Hong Gao (Environmental Science and Pollution Research, 2013)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

Effects of morphine on associative memory and locomotor activity in the honeybee (Apis mellifera) - Yu Fu; Yanmei Chen; Tao Yao; Peng Li; Yuanye Ma; Jianhong Wang (Neuroscience Bulletin, 2013)

Effects of Land-Use and Climate Change on Hydrological Processes in the Upstream of Huai River, China - Peng Shi; Xinxin Ma; Yuanbing Hou; Qiongfang Li; Zhicai Zhang; Simin Qu; Chao Chen; Tao Cai; Xiuqin Fang (Water Resources Management, 2013)

The viability, melanophore and embryo genesis of first- and second-generation hybrids between Paralichthys olivaceus and P. dentatus - Juan Sui; Qinghua Liu; Zhizhong Xiao; Daoyuan Ma; Shihong Xu; Tao He; Yifan Liu; Yongshuang Xiao; Jun Li (Marine Biology Research, 2013)

DNA polymerase beta promoter mutations affect gene transcription, translation and the sensitivity of esophageal cancer cells to cisplatin treatment - Tao Wang; Wenqiao Zang; Yunyun Ma; Min Li; Xiaoyan Xuan; Na Wang; Rui Wu; Yuebai Li; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

Function of the anal sacs and mid-gut in mitochondrial sulphide metabolism in the echiuran worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Li-Tao Zhang; Xiao-Li Shi; Ying-Ping Dong (Marine Biology Research, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Cloning and characterization of SCIRR69: a novel transcriptional factor belonging to the CREB/ATF family - Zhenlian Ma; Haiping Que; Yanli Ni; Haiyan Huang; Yong Liu; Tao Liu; Xin Li; Qihong Sun; Shaojun Liu (Molecular Biology Reports, 2012)

Acarbose Bioequivalence: Exploration of New Pharmacodynamic Parameters - Min Zhang; Jin Yang; Lei Tao; Lingjun Li; Pengcheng Ma; John Paul Fawcett (The AAPS Journal, 2012)

The complete mitochondrial genome of the butterfly Apatura metis (Lepidoptera: Nymphalidae) - Min Zhang; Xinping Nie; Tianwen Cao; Juping Wang; Tao Li; Xiaonan Zhang; Yaping Guo; Enbo Ma; Yang Zhong (Molecular Biology Reports, 2012)

Cyclic fluid shear stress promotes osteoblastic cells proliferation through ERK5 signaling pathway - Peng Li; Yan-chao Ma; Xiao-yun Sheng; Hai-tao Dong; Hua Han; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2012)

Ontogeny of the digestive tract and enzymes in rock bream Oplegnathus fasciatus (Temminck et Schlegel 1844) larvae - Tao He; Zhizhong Xiao; Qinghua Liu; Daoyuan Ma; Shihong Xu; Yongshuang Xiao; Jun Li (Fish Physiology and Biochemistry, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

Polymorphisms of coding region of BMPR-IB gene and their relationship with litter size in sheep - Mingxing Chu; Lihua Jia; Yingjie Zhang; Mei Jin; Hongquan Chen; Li Fang; Ran Di; Guiling Cao; Tao Feng; Qianqian Tang; Yuehui Ma; Kui Li (Molecular Biology Reports, 2011)

Interleukin-21 as a potential therapeutic target for systemic lupus erythematosus - Jing Li; Hai-Feng Pan; Han Cen; Jing Tian; Yan Ma; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2011)

Tetanic contractions impair sarcomeric Z-disk of atrophic soleus muscle via calpain pathway - Xiao-Wu Ma; Quan Li; Peng-Tao Xu; Lin Zhang; Hui Li; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Population genetic structure and phylogeographical pattern of rice grasshopper, Oxya hyla intricata, across Southeast Asia - Tao Li; Min Zhang; Yanhua Qu; Zhumei Ren; Jianzhen Zhang; Yaping Guo; K. L. Heong; Bong Villareal; Yang Zhong; Enbo Ma (Genetica, 2011)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Genetic analysis of porcine circovirus type 2 (PCV2) strains isolated between 2001 and 2009: genotype PCV2b predominate in postweaning multisystemic wasting syndrome occurrences in eastern China - Wenliang Li; Xianwei Wang; Tao Ma; Zhixin Feng; Yufeng Li; Ping Jiang (Virus Genes, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Monoamine transporter gene polymorphisms affect susceptibility to depression and predict antidepressant response - Wenjiao Min; Tao Li; Xiaohong Ma; Zhengyu Li; Tao Yu; Dong Gao; Bo Zhang; Yang Yun; Xueli Sun (Psychopharmacology, 2009)

Purification and cDNA Cloning of a Cadmium-Binding Metallothionein from the Freshwater Crab Sinopotamon henanense - Wen-Li Ma; Tao Yan; Yongji He; Lan Wang (Archives of Environmental Contamination and Toxicology, 2009)

Rapid discrimination of H5 and H9 subtypes of avian influenza viruses and Newcastle disease virus by multiplex RT-PCR - Hao-tai Chen; Jie Zhang; De-hui Sun; Ji-le Zhang; Xue-peng Cai; Xiang-tao Liu; Yao-zhong Ding; Li-na Ma; Sheng-hai Yang; Lei Jin; Yongsheng Liu (Veterinary Research Communications, 2008)

Fibronectin-mediated activation of Akt2 protects human ovarian and breast cancer cells from docetaxel-induced apoptosis via inhibition of the p38 pathway - Hui Xing; Yang Cao; Danhui Weng; Wenming Tao; Xiaohong Song; Wei Wang; Li Meng; Gang Xu; Jianfeng Zhou; Shixuan Wang; Ding Ma (Apoptosis, 2008)

Seasonal and spatial character of PCBs in a chemical industrial zone of Shanghai, China - Jing Ma; Jinping Cheng; Haiyun Xie; Xiaofang Hu; Wei Li; Jin Zhang; Tao Yuan; Wenhua Wang (Environmental Geochemistry and Health, 2007)

TNFα-initiated oxidative/nitrative stress mediates cardiomyocyte apoptosis in traumatic animals - Shuzhuang Li; Ling Tao; Xiangying Jiao; Huirong Liu; Yue Cao; Bernard Lopez; Rong-Hua Luan; Theodore Christopher; Xin L. Ma (Apoptosis, 2007)

Heat shock proteins and p53 play a critical role in K+ channel-mediated tumor cell proliferation and apoptosis - Xiaobing Han; Fang Wang; Weixing Yao; Hui Xing; Danhui Weng; Xiaohong Song; Gang Chen; Ling Xi; Tao Zhu; Jianfeng Zhou; Gang Xu; Shixuan Wang; et al. (Apoptosis, 2007)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Genetic dissection of plant height by molecular markers using a population of recombinant inbred lines in maize - Tang Ji-hua; Teng Wen-tao; Yan Jian-bing; Ma Xi-qing; Meng Yi-jiang; Dai Jin-rui; Li Jian-Sheng (Euphytica, 2007)

Role of ERK1/2 in the anti-apoptotic and cardioprotective effects of nitric oxide after myocardial ischemia and reperfusion - D.-Y. Li; L. Tao; H. Liu; T. A. Christopher; B. L. Lopez; X. L. Ma (Apoptosis, 2006)

Climatic analyses on increasing dust storm frequency in the springs of 2000 and 2001 in Inner Mongolia - Tao Gao; Lijuan Su; Qingxia Ma; Haiying Li; Xicang Li; Xiao Yu (International Journal of Climatology, 2003)
To study the climatic contribution to dust storm increases in Inner Mongolia in recent years, an analysis has been conducted of such factors in the last 40 years as annual and spring (March–May) precipitation, temperature, cold waves and strong gusty winds. In addition, such factors have been studied statistically regarding their impact upon atmospheric circulation with regard to the zonal circulation of Asia, the deep trough over East Asia and the geopotential height of Qinghai–Xizang Plateau. This study shows that the increased occurrences of dust storms likely result from a decrease in annual precipitation during 1999–2001; the precipitation recorded proved to be constantly below average, especially in spring. In addition, warmer temperatures with frequent cold‐air outbreaks created unstable atmospheric stratification, thus leading to more gales and subsequently, more dust storms. In the springs of 2000 and 2001, large‐scale atmospheric circulations provided the conditions for increased occurrences of dust storms due to stronger zonal circulation and a more westerly positioned trough over East Asia that became more intense in the winters. Furthermore, geopotential height over the Qinghai–Xizang Plateau seems to have an opposite trend as against dust storm frequency tendency. El Niño–southern oscillation activity might be an indirect factor. Copyright © 2003 Royal Meteorological Society